Multiscale insights into the phase-dependent sintering of Fe2O3 and Fe3O4 under chemical looping conditions - Guanshan Liu; Yang Lei; Yayong Zhang; Huijun Ge; Tao Zhang; Rui Tan; Mudi Wu; Shiwei Ma; Mingwu Tan; Tao Song (Fuel, 2027)

Aromatic carbon from low-temperature biochar enhances bacterial phosphorus solubilization under saline-alkaline stress - Ziyi Ge; Shiyun Gan; Jiayi Li; Ziyue Xu; Siyu Wang; Xu Su; Yixuan Chen; Li Lin; Song Gao; Jun Meng (Bioresource Technology, 2027)

High-salinity composite organic wastewater electrochemical treatment: A Janus system coupling high-valent iron oxidation with atomic hydrogen-mediated reductive detoxification - Jiayi He; Ge Song; Guanyu Liu; Chaohui Zhang; Jiangli Sun; Jiatong Zhang; Minghua Zhou (Water Research, 2026)

Explainable machine learning and Pareto optimization enable data-driven design of COF-TFN nanofiltration membranes for desalination - Shengnan Hao; Yulin Ge; Zhu Fan; Xiaoman Zhang; Zhanlin Ji; Dalei Song; Yingchao Dong (Desalination, 2026)

Wastewater nutrients valorization into biostimulant via engineered polyphosphate-accumulating bacterium - Xiaotong Ge; Xue Li; Zihao Fan; Xin Wang; Mengmeng Wang; Jingyun Yin; Xiaohua Song; Liyu Pan; Yuhu Zheng; Liuyan Yang (Bioresource Technology, 2026)

Research on the optical properties of secondary organic aerosols based on laboratory simulations: progress and prospects - Shudan Wei; Junling Li; Yufei Song; Yushi Gong; Maofa Ge; Hong Li; Wei Wei (Atmospheric Research, 2026)

A SASP-related four-gene signature associated with intervertebral disc degeneration: integrated bioinformatics analysis and validation of pinocembrin as a therapeutic candidate - Ge-Liang Yao; Shi-Jiang Wang; Ying Zhang; Jia-Ming Liu; Hong-Hai Song; Zhi-Li Liu (Molecular Biology Reports, 2026)

DNA methylation is associated with phenotypic divergence between the dermatophytes Trichophyton rubrum and Trichophyton violaceum - Ge Song; Meijie Zhang; Xiaodong She; Xiaofang Li; Weida Liu; Guanzhao Liang (Brazilian Journal of Microbiology, 2026)

Unsupervised anomaly detection of nuclear power plant based on reconstruction with memory module - Song Xu; Yuantao Yao; Shaoxuan Wang; Meisheng He; Daochuan Ge; Jie Yu (Annals of Nuclear Energy, 2026)

Root accumulation and efficient translocation of steroids in mangrove plants: Implications for an overlooked coastal reservoir - Ji-Xun Chen; Nian-Nian Wu; Shan Liu; Yuan Liu; Qin-Ge Zhou; Qing-Song Yang; Juan Ling; Xiao-Fang Huang; Yan-Kuan Tian; Chang-Gui Pan; Xiang-Rong Xu (Marine Pollution Bulletin, 2026)

Untargeted serum lipidomics reveals lipid metabolic disturbances and identifies candidate lipid biomarkers in acute diquat poisoning - Xinxin Huang; Xunan Kan; Lei Xiao; Chuanguang Han; Ge Li; Quan Xia; Qianli Zou; Qinhai Ma; Shuai Song (Toxicology and Applied Pharmacology, 2026)

The ferric Iron uptake transcriptional regulator (Fur) governs virulence and stress responses in Listeria monocytogenes and serves as a target for novel food safety interventions - Aiyun Li; Haonan Xu; Ruofei Song; Ge Song; Arshad Qandeel; Qiyu Cao; Xiaohui Zhang; Tongxin Ge; Wenxin Wang; Yiyang Li; He Sun; Jinxuan Gui; et al. (Food Research International, 2026)

Long-term particulate matter exposure and coronary inflammation: A large-scale cohort study assessed by pericoronary fat attenuation index - Yuan Xu; Yi Zhang; Ge Guo; Xin Meng; Jing Wei; Yuanyuan Fan; Jiageng Cai; Cencen Wu; Zhulan Cai; Penghui Zhao; Yuwen Ruan; Zhaowei Yin; et al. (Environmental Pollution, 2026)

From perception to governance: Knowledge-enhanced intelligence for smart sustainable buildings - Shuangxue Liu; Hongbin Xie; Yuzhen Lei; Jiaxing Zhao; Jiaxue Liu; Ge Song; Liyu Zhang; Weiyao Yang; Xuan Song; Haoran Zhang (Energy and Buildings, 2026)

Probabilistic whole life cycle greenhouse gas displacement factors for timber frame house external walls - William Horan; David Styles; Song Ge; Patrick J. McGetrick; Michael Quilligan (Building and Environment, 2026)

Connectivity and function determine whether ponds act as sources or sinks of nonpoint-source phosphorus - Xiaofen Bai; Chen Lin; Ke Song; Wenlan Feng; Junfeng Xiong; Siyu Ge; Wanqian Yu; Jianchun Chen; Yijun Tong (Journal of Hydrology, 2026)

Defining system-level sustainability thresholds: a life cycle emergy assessment for vertical greening in the built environment - Junxue Zhang; Yuyang Wang; Xiaoting Zhai; Ashish T.Asutosh; Yingnan Li; Ge Song; Weidong Wu; Ziyi Men (Energy and Buildings, 2026)

Monomer sequence governs the anti-inflammatory activity of chitooligosaccharides - Siqi Zhu; Minmin Hu; Anbang Li; Wentong Hao; Xiangyun Ge; Haoyue Yang; Yupeng Li; Jingwen Li; Song Liu; Ronge Xing; Pengcheng Li; Kecheng Li (Carbohydrate Polymers, 2026)

Integrated sludge resources hierarchical recovery: enhancing VFAs production through pilot scale liquid-state anaerobic fermentation by sludge residues-based biochar - Jing Zhang; Dong-Shan Yang; Jia-Yu Yang; Yun-Yi Song; Nan Wu; Tian Pu; Ge Zhu; Hong-Bo Liu; He Liu (Bioresource Technology, 2026)

Biochar enhances soil carbon in iron-rich red soil but fails in calcareous fluvo-aquic soil: Mineral protection outweighs microbial turnover - Wanyi Fang; Peipei Li; Ge Song; Na Deng; Siyi Liu; Tianran Sun; Limei Zhang (Agriculture, Ecosystems & Environment, 2026)

Precisely engineering transglycosidases as robust biocatalysts toward glycoside reformation for innovative food processing - Jiawei Tang; Ao Li; Mengxiao Tang; Feiyin Ge; Lingyun Hu; Xiaodan Song; Xingyuan Liu; Hao Shi; Zhongbiao Tan (Critical Reviews in Food Science and Nutrition, 2026)

Hydrological controls dominate greenhouse gas emissions in aquatic–terrestrial ecotones under extreme weather - Jingyun Yin; Wenbin Bian; Ke Xu; Liyu Pan; Di He; Chenyu Wang; Xiaohua Song; Xiaotong Ge; Chenyuan Kong; Yuhu Zheng; Hongqiang Ren; Mengmeng Wang; et al. (Journal of Environmental Sciences, 2026)

Highly efficient discovery of CYP1B1 inhibitors from licorice as novel anti-fibrotic agents via integrating interdisciplinary methodologies - Ziwei Li; Yumeng Hao; Ya Yang; Jingxuan Lei; Feng Zhang; Yunqing Song; Hao Yin; Ziru Dai; Shenglan Qi; Yongbin Cao; Guangbo Ge (Toxicology and Applied Pharmacology, 2026)

Integrating emergy accounting with ecosystem-based coastal defence: An eco-coastal engineering framework for sustainability assessment of hybrid infrastructure - Junxue Zhang; Moran Yu; Hairuo Wang; Yan Gong; Haobing Wang; Xiaoting Zhai; Ashish T. Asutosh; Yingnan Li; Ge Song; Weidong Wu; Ziyi Men; Minghui Yang; et al. (Ocean Engineering, 2026)

A review of machine learning applications in inland and nearshore water color remote sensing: from preprocessing to object detection and parameter estimation - Jiarui Shi; Zuchuan Li; Ge Liu; Chong Fang; Zhidan Wen; Yingxin Shang; Hui Tao; Sijia Li; Qiang Wang; Zijin Wang; Kaishan Song (Journal of Hydrology, 2026)

Functional differentiation of active hydrogen on Pd/Cu catalysts for efficient electrocatalytic nitrate reduction to ammonia - Chunhong Fu; Chaohui Zhang; Jiangli Sun; Huizhong Wu; Ge Song; Minghua Zhou (Journal of Hazardous Materials, 2026)

ENSO impacts the scales of cyanobacterial bloom in Lake Taihu, China - Liyu Pan; Lian Xue; Mengmeng Wang; Di He; Xiaohua Song; Jingyun Yin; Xiaotong Ge; Guangwei Zhu; Bensheng You; Qing Cao; Hao Lu; Liuyan Yang (Journal of Environmental Management, 2026)

Preference-guided land-use optimization and trade-off coordination under different development goals from a township zoning perspective: A case study of rural Qiqihar, China - Yujin Zhou; Ge Liu; Kaishan Song; Shidi Shao; Yang Li; Bingqian Han; Jipeng Zhang (Journal of Cleaner Production, 2026)

A multifunctional hybrid delivery system of sodium alginate-based nanoparticles-hydrogel beads “double fence” effect for pea peptide - Guocong Ma; Mingwu Qiao; Dan Hai; Yan Ma; Ge Bai; Peijun Zhao; Xianqing Huang; Xinyu Sun; Lianjun Song (Food Chemistry, 2026)

Investigating Microbial Communities and Metabolic Dynamics in Jiupei from Cellars of Different Ages: An Integrated Amplicon and Metabolomic Analysis of Mianrou-Style Baijiu - Longyun Zhang; Chun Pu; Congzhi Zhang; Fengxue Guo; Jiaojiao Song; Xiangyang Ge; Yan Xu (Food Bioscience, 2026)

Heterologous expression and functional characterization of Bacillus subtilis natto MenA in Escherichia coli and its role in Vitamin K2 Biosynthesis - Said Nawab; Chuanchao Wu; Zhangbing Ge; Wei Tao; Yuqi Li; Yuexin Ma; Yaqing Zhao; Jie Song; Yi-Feng Jiang; Yan Liu (Food Bioscience, 2026)

Preparation of high-strength elastic bigel with dual network structure to stabilize astaxanthin for low-fat food filling - Siqi Song; Xueqian Li; Fengyu Bai; Jiajia Bai; Kuiyou Wang; A.M. Abd El-Aty; Peng Ge; Mingqian Tan (Food Hydrocolloids, 2026)

Study on the sustainability, resilience and co-governance of rural biomass energy systems: Based on an integrated perspective of ecology-community-culture-technology - Guorui Fan; Junxue Zhang; Zheheng Chen; Ashish T. Asutosh; Yingnan Li; Ge Song; Weidong Wu; Ziyi Men (Biomass and Bioenergy, 2026)

Investigation of changes in microbial communities and metabolites for the nutrient re-utilization of fermented agricultural wastes in watermelon - Tong-Lu Wei; Yan-Ge Li; Mao-Song Pei; Hai-Nan Liu; Xue-Jie Zhu; Zhong-Hou Zhu; Da-Long Guo (Biomass and Bioenergy, 2026)

A bidirectional spatiotemporal cross-domain fusion model for TSM retrieval in inland waters - Chen Wang; Huimin Lu; Ge Liu; Dongmei Lü; Shizhuo Liu; Bingqian Han; Yang Li; Kaishan Song (Journal of Oceanology and Limnology, 2026)

A Sea Surface Salinity error correction model integrating physical models and complex environmental influences - Yanling Han; Wenbin Zhao; Qinqin Sun; Ge Song; Ping Ma; Yun Zhang; Chuanxiang Hua; Shouqi Cao (International Journal of Remote Sensing, 2026)

Deep learning-based surrogate model for predicting structural capacity of self-centering shear walls - Ge Song; Yankun Zhu (Bulletin of Earthquake Engineering, 2026)

Rule-based 10 m resolution mapping of winter wheat in the Nile Delta based on growth rate difference under fuzzy phenology - Yonghao Wu; Bingxue Zhu; Sijia Li; Belal Elleithy; Ahmed Elshal; Bassant Raafat; Ge Liu; Duo Wu; Xin Ye; Kaishan Song (International Journal of Remote Sensing, 2026)

A Wind Data Quality Control Algorithm Utilizing Deep Learning-Based Association Test Rules - Ruidi Ma; Song Gao; Fan Jiang; Bo Yu; Haoqiang Tian; Yanchen Song; Yong Ge; Dianjun Ren; Chenxu Wang (Journal of Marine Science and Engineering, 2026)
Harnessing the powerful learning and modeling capabilities of artificial intelligence, this study introduces a deep learning-driven wind data quality control algorithm that employs correlation verification rules. By constructing a Dual-Track Information Fusion Network (DTF-Net), it captures local temporal variations in wind speed via the temporal track and uncovers physical coupling relationships among temperature, pressure, wind direction, and other variables through the global track. Integrating dynamic three-standard-deviation spike detection with 3δ-RMSE spatial validation based on deep learning predictions, the algorithm enables multi-dimensional collaborative anomaly detection in the absence of neighboring stations. Experimental findings demonstrate that the proposed method achieves Mean Absolute Errors (MAE) of 0.217, 0.398, and 0.462 for 1 h, 12 h, and 24 h wind speed forecasts, respectively, representing a 3.8–61.3% reduction compared to general-purpose models like AutoFormer, ITransformer, and FiLM. The anomaly detection rate for quality control ranges from 0.33% to 9.20%, effectively identifying data aberrations during buoy maintenance, equipment failures, and abrupt changes in short-term weather patterns. This study leverages the powerful learning and modeling capabilities of artificial intelligence to establish a novel and easily understandable intelligent quality-control paradigm for sparse ocean observation networks, providing direct practical value for improving the quality of marine meteorological data assimilation.

WeedsDetectNet: A green attention and adaptive joint feature fusion network for weed detection in agricultural fields - Baoquan Ge; Zhenhong Jia; Ao Guo; Wei Chen; Jiajia Wang; Sensen Song; Gang Zhou (Crop Protection, 2026)

Erratum to “Untargeted serum lipidomics reveals lipid metabolic disturbances and identifies candidate lipid biomarkers in acute diquat poisoning” [Toxicology and Applied Pharmacology 516 (2026) 117995] - Xinxin Huang; Xunan Kan; Lei Xiao; Chuanguang Han; Ge Li; Quan Xia; Qianli Zou; Qinhai Ma; Shuai Song (Toxicology and Applied Pharmacology, 2026)

Spatial decoupling of electron donation and oxygen capture for efficient endogenous oxygen-driven electrosynthesis of 1O2 in water remediation - Xifeng Lu; Pei Su; Jingxuan Zhao; Xuedong Du; Ge Song; Boxuan Cui; Kexin Chen; Qingrui Zhang; Minghua Zhou (Science Bulletin, 2026)

Loss of eIF3m aggravates myocardial ischemia/reperfusion injury via enhancing nitrative damage and inhibiting glycolytic reprogramming - Zilun Wei; Yongchao Zhao; Daile Jia; Rifeng Gao; Weidong Xiong; Xiaolei Sun; Xinyu Weng; Bowen Liu; Shuai Song; Wei Luo; Jian Cui; Kai Hu; et al. (Science Bulletin, 2026)

A stochastic multi-physics framework integrating thermo-electrochemical-microbial dynamics for lifecycle corrosion prediction and risk quantification of subsea pipelines - Yungen He; Ge Song; Shuang Ma; Yajing Liu; Yanhui Hu; Rongsheng Lin; Jiangen Tao (Ocean Engineering, 2026)

Climatic variability characteristics of the western coast of the Bohai Bay during the early-middle Holocene - Ran Zhang; Hanfei You; Ying Wang; Xiuyun Sun; Bing Li; Yawen Ge; Zhen Zhang; Hongyu Song; Yuecong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The paradox of rural depopulation and built-up growth: Insights from two decades of settlement change in China (2000–2020) - Yujin Zhou; Jipeng Zhang; Ge Liu; Kaishan Song; Bingxue Zhu; Sijia Li; Shidi Shao; Yang Li; Bingqian Han (Land Use Policy, 2026)

Divergent drivers of winter PM2.5 pollution in representative cities of the Sichuan Basin: Insights from observation and machine learning - Zhihan Rao; Hongli Tao; Li Zhou; Weigang Wang; Song Liu; Bin Luo; Wei Zhang; Pan Cao; Jianjun Li; Fumo Yang; Maofa Ge (Journal of Hazardous Materials, 2026)

Leachate treatment reduces but does not eliminate antibiotic resistance gene contamination: Associations between Pseudomonadota and resistome persistence in treated leachate - Yue Sun; Xian-Ge Wang; Xiao-Jun Chen; Zhen Zhou; Yue-Jun Huang; De-Shuo Wang; Bei-Dou Xi; Xiao-Song He (Journal of Hazardous Materials, 2026)

Interface and defect engineering of hierarchical Ti3C2/Co@CeO2-NCNT nanocomposite for ultrasensitive electrochemical determination of pesticide bithionol - Zhifang Liu; Yuyi Song; Kunxiang Deng; Caiyu Ge; Xiang Ye; Xinyi Li; Yixi Xie; Pengcheng Zhao; Junjie Fei (Journal of Hazardous Materials, 2026)

Molecular Evidence for Distinct Coastal Dissolved Organic Matter Responses to Nitrogen and Phosphorus Enrichment - Xin Guo; Junfeng Chen; Xiao Chen; Lianbao Zhang; Gang Li; Hongwei Ren; Bokun Chen; Yubin Hu; Ge Xu; Dingxi Zhang; Chen He; Quan Shi; et al. (Journal of Environmental Sciences, 2026)

Enhancement of ursolic acid (UA), an active ingredient in hawthorn, on the uptake and metabolism of 2,3,5,4′-tetrahydroxystilbene-2-O-β-D-glucoside (THSG) derived from Polygonum multiflorum - Runlu Li; Simin Ren; Yunhong Zhao; Ni An; Jingwu Song; Feng Guan; Jian Ge (Food Research International, 2026)

Feeding 10 billion people in 2050 with cropland expansion limitation: From remote sensing to smart agriculture - Sijia Li; Xiuliang Jin; Qiangzi Li; Xiang Wang; Bingxue Zhu; Zhaohua Liu; Ge Liu; Kaishan Song (European Journal of Agronomy, 2026)

CNN-BiLSTM with attention mechanism and soil-aware dynamic EI-D thresholds for extreme rainfall-induced landslide early warning in subtropical mountains - Weifeng Xiao; Guangchong Yao; Ge Liu; Kaishan Song; Zhenghui Xiao; Luguang Luo (Environmental Modelling & Software, 2026)

Advances in Alzheimer’s disease: mechanistic insights and therapeutic targets - Yu-Juan Jia; Yi-Jun Ge; Bowei Li; Ying Yang; Huaqiu Chen; Jie Liu; Jun-Hong Guo; Jin-Tai Yu; Ke-Qiang Ye; Jian-Zhi Wang; Weihong Song; Yan-Jiang Wang (Science China Life Sciences, 2026)

Regionalizing the vertically generalized production model (VGPM) for Sentinel-2 estimation of phytoplankton primary productivity in turbid inland waters - Ting Song; Yanjuan Xu; Hujun Zhang; Bingchuan Zhu; Ling Li; Dongyang Cheng; Ge Liu (Journal of Oceanology and Limnology, 2026)

Primer-programmed circular template generation enables padlock-free rolling circle amplification for low-background CRISPR-based pathogen detection - Yemin Han; Haotian Yu; Manman Lv; Mengqing Cheng; Weihao Li; Houyang Ge; Song Gao; Lu Yin; Qinyu Ge; Xinping Xu; Yan Huang; Longhua Sun; et al. (Analytica Chimica Acta, 2026)

The transformation of China's iron and steel industry under carbon constraints: A balance between economy, emission reduction and technical feasibility - Hua Tong; Jun Liu; Yu Wang; Haowen An; Ge Song; Yating Hou; Xiaolong Tang; Honghong Yi (Journal of Environmental Sciences, 2026)

Bio-inspired multifunctional smooth lubricant-infused surface for residue-free, antimicrobial, and real-time freshness-monitoring food packaging - Jiajia Bai; Siqi Song; Xueqian Li; A.M. Abd El-Aty; Peng Ge; Mingqian Tan (Food Research International, 2026)

Chemometrics-guided lipidomics for quality assessing of vegetable oils during repetitive deep-frying - Gongshuai Song; Ziming Xu; Yangcheng Ge; Xuanyi Wang; Danli Wang; Tinglan Yuan; Ling Li; Mengna Zhang; Jinyan Gong (Food Control, 2026)

Lignin degradation enhancement in poultry manure and maize residue composting via flax retting waste liquid and biochar: Dominant microbial generalist species mediated - Tong Yang; Xiujun Tu; Xuan Tang; Yuhao Guo; Yueyi Liu; Zhenchao Wu; Hao Zhang; Ying Yang; Shuo Li; Weige Yao; Jinyu Du; Tingting Xu; et al. (Food and Bioproducts Processing, 2026)

A facile computational framework for predicting dynamic filtration performance of compressed coarse filter media using geometric compression and numerical simulation - Yuhai Yan; Junjie Zhang; Huimin Ge; Yunyan Chen; Zhibin Wang; Li Xi; Haibo Wu; Xiangyu Jin; Chen Huang; Yu Song (Building and Environment, 2026)

Spatial and environmental niche differentiation facilitates sympatric macaques' coexistence in montane-canyon landscapes: Implications for conservation - Wei Zhou; Yuan Wang; Deyan Ge; Qisen Yang; Gang Song; Jilong Cheng; Tian Tian; Yu Zhang; Jinbo Xu; Ying Liu; Weibo Wang; Xiaochuan Wang; et al. (Biological Conservation, 2026)

ATP-dependent binding cassette transporter ClABCI6 promotes the expression of citrus yellow vein clearing virus via inhibiting salicylic acid pathway - Yaqin Song; Wen Ge; Cuiyun Lei; Yijie Li; Yang Han; Jiedan Xiao; Xinghua Qiao; Shixue Hu; Yan Zhou; Binghai Lou (Journal of Plant Research, 2026)

Enhanced tropospheric delay retrieval using baseline-constrained multi-antenna shipborne GNSS with common ZTD parameter in the western Pacific - Zhitao Wang; Shuli Song; Maorong Ge; Yuze Yang; Zhifan Yan; Weili Zhou; Chao Huang; Xiangxiang He; Guoqiang Jiao; Zhu Wang (GPS Solutions, 2026)

Prediction of the joint toxicity of microplastics and organic pollutants on algae based on machine learning - Jing Lu; Yang Song; Bin Hou; Ge Guo; Yating Jia (Marine Pollution Bulletin, 2026)

Decoupled recovery of phosphorus and iron from sewage sludge via electrochemical anaerobic fermentation - Yuhan Zhang; Ge Song; Yu Cheng; Yaoyihan Luo; Chengzhi Hu (Water Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Conversion of waste activated sludge into high-quality denitrification carbon source via moderate pretreatment: Performance, mechanisms, and environmental benefits evaluation - Yifan Sun; Ge Song; Shunan Zhao; Fangzhou Wang; Kai Zhao; Wenwei Li; Ruiping Liu (Resources, Conservation and Recycling, 2026)

Monitoring algal blooms in eutrophic inland lakes using OLCI: Overcoming cloud and sun-glint effects on low-quality imagery - Bingqian Han; Shaojing Wang; Long Fei; Kaishan Song; Ge Liu; Yue Ma; Shidi Shao; Yang Li; Yujin Zhou; Jipeng Zhang (Journal of Hazardous Materials, 2026)

Glycation regulation between dual-natural milk-derived proteins and fucoidan by dielectric barrier discharge-cold plasma and its potential for delivery of astaxanthin - Yangcheng Ge; Yingcong Yang; Zhen Xu; Gongshuai Song; Mengna Zhang; Jinyan Gong (Innovative Food Science & Emerging Technologies, 2026)

Cold plasma-modified goat milk casein/Chinese yam polysaccharide/chitosan composite films: Structural, functional, and preservative properties for fresh pork - Shunan Song; Jiaqing Song; Jiadi Liu; Qing Lei; Conghui Li; Wupeng Ge; Jiaying Zhang (Food Chemistry, 2026)

Effects of pulsed electric field and cold plasma treatments on goat milk: A study based on microflora, quality, flavor and protein digestion - Zhi Cao; Zhengshi Chang; Ning Song; Yanhui Yang; Wupeng Ge; Lili Zhao (Food Control, 2026)

Amyloid-based molecular entangled hybrid network towards ultra-stiffness protein aerogel - Weiqiang Wang; Xiaoqing Song; Jiaying Qiu; Xuan Wang; Dongdong Hu; Jiajia Gao; Honghua Ge (Chemical Engineering Journal, 2026)

Arbuscular mycorrhizal fungi hypha shape atrazine degradation ability of microbiota by increasing soil aggregation - Yang Sun; Hongyang Pan; Ge Song; Sisi Chen; Alexander V. Kurakov; Fuqiang Song; Jing Wang; Xiaoxu Fan (Mycorrhiza, 2026)

River–Coast Connectivity Controls Ecosystem Services and Blue Carbon of Coastal Nature-Based Solutions: An Integrated Study Coupling Emergy–Carbon Footprint Accounting and Neural Network Modeling - Junxue Zhang; Yan Gong; Hairuo Wang; Ashish T. Asutosh; Ge Song; Weidong Wu; Xiaoting Zhai (Journal of Marine Science and Engineering, 2026)
This study develops an integrated framework combining emergy analysis, carbon footprint accounting, and long short-term memory neural network modeling to investigate the effects of nature-based solutions on coastal ecosystem services and blue carbon functions from the perspective of river–coast connectivity. Three transects along a connectivity gradient were established in the Yellow River Delta, a typical large river delta in temperate China, covering riparian zones, estuarine transition areas, intertidal wetlands, and seagrass beds, with multi-source data collected over three consecutive hydrological years. Emergy–carbon coupling analysis based on this case study indicates that the high-connectivity transect shows a higher emergy yield ratio and net carbon sink compared to the low-connectivity transect, with salt marshes being most sensitive to connectivity change. Threshold analysis, specific to this delta, identifies a three-phase response pattern of carbon burial rate with increasing sediment connectivity, and reveals that wave attenuation efficiency declines notably when hydrological connectivity falls below approximately 0.5, although this value may vary across different coastal settings. A higher sea level rise rate raises the critical connectivity level required to maintain carbon sink function. The long short-term memory neural network trained on observational data achieves better prediction accuracy for blue carbon accumulation rates than traditional statistical methods, and SHAP value analysis suggests the possible existence of synergistic effects among connectivity dimensions. Based on these findings, three optimization strategies including tiered restoration, a dynamic pathway, and spatial configuration are proposed as case-specific recommendations for the Yellow River Delta. Framework-based simulations indicate the potential for connectivity-informed strategy adjustments to improve restoration efficiency under local conditions. This study concludes that river–coast connectivity represents an important lever regulating the ecological benefits of nature-based solutions, but emphasizes that all quantitative thresholds and benefit magnitudes reported here are case-specific estimates that require recalibration when applied to other coastal systems.

Status quo of remote sensing of CDOM for global inland waters - Xiaodi Wang; Kaishan Song; Zhidan Wen; Ge Liu; Xiangfei Yu; Jipin Liu; Yingxin Shang (Journal of Oceanology and Limnology, 2026)

PG-DyMamba: a physics-guided dynamic graph Mamba network for significant wave height prediction - Fan Jiang; Yinzhu Zang; Ruidi Ma; Bo Yu; Hui Li; Song Gao; Yong Ge; Dianjun Ren (Frontiers in Marine Science, 2026)
Accurate prediction of Significant Wave Height (SWH) is vital for marine engineering safety, yet balancing computational efficiency with physical consistency in long-sequence modeling remains a challenge for data-driven approaches. To address this, we propose the Physics-Guided Dynamic Graph Mamba Network (PG-DyMamba). By integrating oceanographic priors such as windwave relations, our Physics-Aware Graph Learner adaptively captures time-varying multivariate dependencies. Concurrently, the Mamba architecture processes long historical sequences with linear complexity. To ensure physical plausibility, the model employs a composite loss function based on energy conservation and fluid smoothness, effectively constraining predictions to adhere to fundamental physical laws. Empirical evaluations on Australia, NDBC, and North Sea datasets confirm that PG-DyMamba outperforms state-of-the-art baselines. Notably, the model achieves a 19.2% MSE reduction in 48-step prediction horizon on the Australia dataset, demonstrating its robustness for operational marine applications.

Adsorption mechanisms and weathered surface effects in the neutral flotation separation of feldspar from quartz using a mixed anionic/cationic system - Yuhao He; Yuhan Song; Xiaohui Li; Ge Zhu; Lu Xiang; Zijie Ren (Minerals Engineering, 2026)

Scalable molten salt electrochemical siliconizing tailors texture in silicon steel for superior electromagnetic properties - Xinrui Wang; Zheng Huang; Junqing Zhang; Jingya Xu; Mingyong Wang; Jianbang Ge; Yiwa Luo; Dongbai Sun; Weili Song; Zhe Wang; Shuqiang Jiao (Journal of Cleaner Production, 2026)

Phosphoric acid-mediated 3D honeycomb-structured g-C3N4 as a high-performance support for ultrafine Pt nanoparticles in phenol hydrogenation - Shiyu Wang; Shuai Wang; Mingmei Ge; Yang Zhao; Hua Song; Huan Wang (Fuel, 2026)

Multi-platform volatile profiling analysis was used to reveal the characteristics and influence mechanism of flavor metabolites in irradiated beef - Shuang Pang; Dandan Wu; Xinchen Jin; Yufan Tong; Suyang Weng; Ge Yan; Enxi Song; Ju Zhang; Xin Lü (Food Research International, 2026)

A multi-level Monte Carlo tree search method for configuration generation in crystalline systems - Xiaoxu Li; Ge Xu; Huajie Chen; Xingyu Gao; Haifeng Song (Computer Physics Communications, 2026)

Band filling mediated D-band center shift in palladium hydride to improve hydrogen evolution electrocatalysis - Seung Joon Choi; Song Jin; Ali Mohammadi; Min Ho Seo; Jing-Li Luo; Ge Li (Chemical Engineering Journal, 2026)

ABC transporter BrABCG12 mutation results in tender green glossy leaves in Chinese cabbage - Zhichao Gong; Gengxing Song; Chengchuang Huang; Xiaoli Tang; Yanru Ge; Jie Ren; Hui Feng (Theoretical and Applied Genetics, 2026)

Intrinsic Brain Activity Alterations in Disorders of Consciousness: A Parallel Resting-State fMRI Analysis at 7 Tesla - Xufei Tan; Yuan Sun; Ge Li; Shanshan Song; Shanshan Wu; Jian Gao (Brain Topography, 2026)

A Systematic Review of the Application of Chinese Satellite Observations for Water Quality Remote Sensing - Bingqian Han; Muhammad Bilal; Muhammad Usman; Meng Mu; Kaishan Song; Ge Liu; Zhidan Wen; Yingxin Shang; Chong Fang; Sijia Li; Shidi Shao; Yang Li; et al. (Chinese Geographical Science, 2026)

Responses of ecological stability in subtropical coastal phytoplankton communities to varying N:P ratios under present and future scenarios - Jichen Chen; Yonglong Xiong; Jingke Ge; Xin Zhao; Yuan Feng; Xu Li; Chi Song; Xiao Yang; Rui Zhang; Jin-Yu Terence Yang; Wuchang Zhang; Shengyao Sun; et al. (Water Research, 2026)

Global inland waters trophic status from space observation: scientific advances and future challenges - Lili Lyu; Pierre-Andre Jacinthe; Nan Lin; Dongmei Lyu; Ge Liu; Sijia Li; Chong Fang; Hui Tao; Hao Yu; Zuchuan Li; Kaishan Song (Water Research, 2026)

Global trends in coastal aquaculture ponds: navigating seafood demand and ecological conservation - Dehua Mao; Duanrui Wang; Ming Wang; Hong Yang; Julian R. Thompson; Xiangming Xiao; Yujia Zhang; Kaishan Song; Chunying Ren; Juhua Luo; Ling Luo; Ge Liu; et al. (Science Bulletin, 2026)

Improved U-Net with enhanced spatiotemporal features for Chlorophyll-A concentration prediction in the Zhoushan fishery - Yanling Han; Yizhuo Cai; Ping Ma; Ge Song; Jing Wang; Yun Zhang; Shuhu Yang; Zhonghua Hong (Remote Sensing Applications: Society and Environment, 2026)

Nutrient accumulation and redox conditions shape lake bacterial communities: A dual-medium assessment of closed coal-mining subsidence versus natural lakes - Shuo Li; Lei Zhang; Wen Ge; Yijie An; Ting Song; Feng Xu; Hua Cai (Journal of Environmental Chemical Engineering, 2026)

Seasonal dynamics of aqueous phase from hydrothermal carbonization of waste activated sludge: Unraveling composition, ecological risks, and resource opportunities - Tingting Yang; Ninghui Song; Xue Zhang; Yanqi Shi; Ping Li; Mingzhu Zhang; Feng Ge (Journal of Cleaner Production, 2026)

The effect of metakaolin on the properties of MSWI fly ash-slag binder: Compressive strength and chloride ions immobilization - Junjie Zhang; Zhaocheng Guo; Ge Zhang; Ting Zhang; Xuefeng Song (Journal of Environmental Management, 2026)

Enhancement of nutrient removal in a novel simultaneous nitrification, denitrification and phosphorus removal system via phosphorus recovery regulation under carbon limited condition - Ge Cao; Siyuan Zhai; Dong Ni; Jinxin Song; Jiaojiao Niu; Yingxin Zhao (Journal of Environmental Chemical Engineering, 2026)

Promoting the formation of β-lactoglobulin amyloid fibrils induced by cold plasma treatment: self-assembly mechanism, emulsifying properties, and stability - Gongshuai Song; Tian Zhao; Yingcong Yang; Yangcheng Ge; Wei Tang; Taijiao Xiang; Danli Wang; Tinglan Yuan; Ling Li; Yong Cheng; Mengna Zhang; Jinyan Gong (Food Research International, 2026)

Dityrosine induces myocardial injury via Ang II-MAPK-Nrf2 pathway-mediated oxidative stress, mitochondrial dysfunction, and fibrosis in mice - Yin-Yi Ding; Jia Chen; Yuxin Wang; Zhenyu Gu; Tianyuan Song; Yujun Ge; Tianming Xuan; Oushan Tang; Qing Shen; Keyun Cheng (Food and Chemical Toxicology, 2026)

Plasma-induced microcracked stretchable strain sensor array for multifunctional wireless sensing in smart tires - Xiaopeng Du; Xiaona Wang; Shaojie Yuan; Da Chen; Hongen Qu; Xiaoqian Hou; Bing Yao; Chuang Su; Xingyu Ma; Yuhao Cai; Tong Zhang; Ge Song; et al. (Chemical Engineering Journal, 2026)

Synergistic promotion of diabetic wound healing by glucose-responsive functional chitosan-based composite nanohydrogels - Runze Yang; Jiale Sun; Guanglan Peng; Mingcai Wu; Chengen Guan; Jianping Yang; Zeyuan Wang; Wanzhen Li; Longbao Zhu; Jun Wang; Zuchun Zhao; WeiWei Zhang; et al. (Carbohydrate Polymers, 2026)

Dynamic vegetation responses to climate change and human activities in the eastern North China region over the past 3,500 years: Pollen record from the Caofeidian Wetland - Shiyao Chai; Ying Wang; Rongrong Wang; Hongyu Song; Ran Zhang; Xiangyue Kong; Yunfei Yang; Yawen Ge; Bing Li; Yuecong Li (CATENA, 2026)

Observational Attribution-Constrained Projections of Area-Averaged Annual Mean Temperature Change over China - Hong Yin; Ge Song; Huanping Wu; Jing Wang (Journal of Meteorological Research, 2026)

Integrating machine learning and prioritization to decipher the partitioning and risk of tire-derived chemicals in highly populated coastal regions - Nian-Nian Wu; Yuan Liu; Shan Liu; Ji-Xun Chen; Qin-Ge Zhou; Xiang-Rong Xu; Qing-Song Yang; Juan Ling; Jian-Liang Zhao (Water Research, 2026)

Metagenomic and cytotoxicity insights into the migration behavior and pathogenic potential of multi-medium microorganisms in a wastewater treatment plant - Wenwen Wang; Song Zhang; Yanjie Wang; Jingyun Ge; Lin Li (Water Research, 2026)

Late Holocene temperature changes in eastern North China reconstructed from branched glycerol dialkyl glycerol tetraethers (brGDGTs) - Hongyu Song; Ying Wang; Huaying Wang; Can-Ge Li; Yuecong Li; Bing Li; Yawen Ge; Rongrong Wang; Xiuyun Sun; Ran Zhang; Hanfei You; Changhong Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Fate and risk of pesticides in drinking water: From source to tap using a comprehensive analysis and prioritization approach - Tingting Yang; Feng Ge; Yuan Hong; Yixuan Wang; Gang Zhou; Huimin Chen; Ninghui Song; Ping Li (Journal of Environmental Sciences, 2026)

Insight into the enhancement mechanism of cold plasma treatment promotes binding for improving the properties of starch-pectin complex - Zejia Zhou; Yuan Jiang; Sihan Cheng; Jingru He; Fenglin Song; Xiangzhen Ge (Food Hydrocolloids, 2026)

A top-down approach in developing embodied carbon caps: Case study of the Irish residential sector - Song Ge; David Styles; Conan O’Ceallaigh; Patrick J. McGetrick (Energy and Buildings, 2026)

Dipole-engineered pyridinium iodide passivation for efficient Sn-Pb and all-perovskite tandem solar cells - Ciyu Ge; Chenwei Ni; Qi Xu; Bokai Hao; Wei Ai; Chengjie Deng; Peiyan Zhang; Xinzhi Zu; Hongyan Lu; Zeyu Zhang; Weijun Ke; Haisheng Song; et al. (Chemical Engineering Journal, 2026)

“Internal-external” synergistic strategy with engineered ADSCs by apoptotic bodies and antioxidant hydrogel mitigate pyroptosis and reshape the ADSCs-microglia axis for spinal cord injury recovery - Maolin Qin; Lufeng Yao; Haiqing Wang; Le Zou; Jiawei He; Mengqi Jin; Xinrui Huang; Zichang Wu; Zhuoyang Song; Suhong Lu; Dong Peng; Kailiang Zhou; et al. (Chemical Engineering Journal, 2026)

Dynamic role of polystyrene microplastics in fouling evolution and structure-performance relationships among floc characteristics, cake layer structure and filtration performance of pre-coagulated low-pressure membrane processes - Meng Chen; Jun Nan; Ziyao Wang; Langrun Song; Zhencheng Ge; Fengmin Li (Chemical Engineering Journal, 2026)

Visualizing application of RUBY-MAT system in maize genetic transformation and gene expression pattern detection - Tengfei Jia; Shuai Zhao; Xiangyu Zhang; Yingxue Li; Kuan Cheng; Xuehui Qian; Mingli Song; Wenjing Ge; Qian Liu; Haoyue Xu; Fashuai Li; Jinhua Hu; et al. (Plant Cell Reports, 2026)

Comparative Mechanical Behavior of Marine Clay Under Axisymmetric and Plane Strain Conditions - Bingheng Liu; Lingwei Kong; Jianqun Zhu; Yong Wang; Guofang Xu; Pei Ge; Li Zhao; Song Yu; Zhiguo Feng (Geotechnical and Geological Engineering, 2026)

Interaction mechanisms and coordinated development strategies of resource-based urban expansion and ecosystem health under ecological debt constraints: Evidence from China’s yellow river basin - Wei Zheng; Ge Song; Zhaoyang Cai (Environment, Development and Sustainability, 2026)

W-MTD: A Weather-Robust and Lightweight Maritime Target Detection Method Based on Knowledge Distillation for USVs - Mengying Ge; Yiji Zhou; Qiuyang Zhang; Zhou Ni; Wei Song (Journal of Marine Science and Engineering, 2026)
Maritime target detection under complex adverse weather conditions (e.g., fog, rain, and low light) is crucial for Unmanned Surface Vehicle (USV) navigation. However, achieving high detection accuracy and efficiency remains challenging due to coupled environmental interference and limited computing resources. In this paper, we propose W-MTD, a task-specific distillation framework designed for weather-robust and lightweight maritime target detection based on knowledge distillation. Building upon the Fine-grained Distribution Refinement (D-FINE) detection model, this method constructs a dual-path knowledge distillation framework tailored for maritime scenes. Through the synergistic optimization of feature similarity constraints and decoupled distillation, it facilitates multi-level knowledge transfer from a teacher model to a lightweight student model, mitigating feature degradation caused by model compression. A multi-scenario augmentation strategy is designed to balance convergence across different weather conditions. Experiments show that W-MTD’s student model improves detection accuracy by 7.0–13.9% under three adverse weather conditionscompared to the baseline teacher model trained solely on clear weather data while maintaining comparable clear-weather performance. With only 4 M parameters and 7 GFLOPs, the student model demonstrates favorable performance and efficiency compared to other real-time detectors, indicating its potential suitability for USV deployment.

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

New U-series and coupled ESR/U-series dating of Xujiayao (northern China), the type site for Homo juluensis - Qingfeng Shao; Fagang Wang; Junyi Ge; Jean-Jacques Bahain; Pierre Voinchet; Guilan Hu; Xinrui Jin; Rainer Grün; Christopher J. Bae; Xing Song (Quaternary Science Reviews, 2026)

Exogenous melatonin alleviates heat stress-induced metabolic slowdown affecting broiler growth by improving lipid metabolism - Fei Song; Binglin Wang; Xin Kang; Aige Han; Huiyuan Rui; Xiangyang Xu; Yi Guo; Ming Ge; Xiaowen Jiang; Wenhui Yu (Journal of Thermal Biology, 2026)

Energy-efficient chlorine-mediated paired electrocatalysis for simultaneous H2O2 production and coal chemical wastewater purification - Jiana Jing; Yingying Du; Chunhong Fu; Jiangli Sun; Ge Song; Minghua Zhou (Journal of Hazardous Materials, 2026)

Inhibitors Enable Rapid Start-up and Stable Operation of Partial Nitrification: Effects, Mechanisms and Challenges - Yun Song; Xiaoyu Han; Shujun Zhang; Liang Zhang; Bo Wang; Da Kang; Zheng Ge; Yongzhen Peng (Journal of Environmental Sciences, 2026)

Satellite images reveal reduced lake chlorophyll concentration and eutrophication in China - Sijia Li; Xiangming Xiao; Ge Liu; Zhidan Wen; Chong Fang; Yingxin Shang; Hui Tao; Lele Zhang; Yong Li; Qiang Wang; Haoyun Zhou; Kaishan Song (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Pinus Knraiensis Nut skin derived CNC reinforced antibacterial chitosan/gum arabic films incorporating Ocimum gratissimum L. essential oil for packaging beef - Ruixuan Wang; Guangjun Xia; Yuchen Wang; Song Zhang; Zhenying Ge; Lu Yin; Duanduan Zhao; Zhiyan Jin; Hongyan Xu (Food Chemistry, 2026)

Genome-wide identification of MYC transcription factors in Chrysanthemum morifolium and CmMYC25 promotes petal anthocyanin accumulation - Wenhao Xia; Yuxi Wang; Ge Zhao; Jialin Peng; Xiuge Li; Yukun Li; Yuhe Tian; Aiping Song; Sumei Chen; Fadi Chen; Li-Jie Zhou (Plant Cell Reports, 2026)

Rational design of fused-ring-modified rhodamine chemosensors for salicylic acid detection: its mechanistic insights and biological application - Mei-Hong Ge; A-Ling Tang; Feng Gao; Shuai Tan; Wei Niu; Xiang Zhou; Song Yang (Molecular Diversity, 2026)

Cav-1 deficiency induces cardiac dysfunction via the AdipoR1-AMPK-mTOR autophagy pathway - Ziyu An; Libo Liu; Xin Zhao; Lijun Zhang; Xueyao Yang; Huan Zhang; Changjiang Ge; Jinfan Tian; Xiantao Song (Inflammation Research, 2026)

Application of a zoning approach in marine ecosystem health assessments: A case study of Jiaozhou Bay (China) - Zihui Ge; Yongquan Yuan; Zaixing Wu; Aiquan Dai; Xiuxian Song; Zhiming Yu (Ocean & Coastal Management, 2026)

Deep learning-based predication of the input energy spectra for self-centering systems - Ge Song; Lili Xing (Soil Dynamics and Earthquake Engineering, 2026)

Recovery of C, N, and P from waste activated sludge by enzymatic anaerobic fermentation: Stoichiometry and metatranscriptomics analysis - Ge Song; Shunan Zhao; Kai Zhao; Ruiping Liu; Chengzhi Hu; Mark C.M. van Loosdrecht (Resources, Conservation and Recycling, 2026)

Naringenin as a bioactive preservative: Coordinated suppression of ethylene biosynthesis and cell wall disassembly delays apple senescence during storage - Ming-Fei Qiao; Peng-Liang Han; Meng-Meng Wei; Zhao-Peng Nie; Song Zhang; Wen-Yan Wang; Hai-Bo Wang; Tian-Ge Chu; Ze Chen; Quan Sun; Da-Gang Hu (Postharvest Biology and Technology, 2026)

Highly oxidized germacrane-type sesquiterpenoid dimers from Elephantopus tomentosus L.: Structural characterization, DFT calculation and anti-hepatoma potential - Zi-Hao Ge; Si-Hui Mi; Wen-Long Kou; Guo-Dong Yao; Bin Lin; Jian Wang; Ming Bai; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2026)

Genomic insights into origin of African rice: Implications for crop domestication - Song Ge (Molecular Plant, 2026)

Physicochemical controls on Mo mineralisation of the Caosiyao porphyry deposit, northern North China Block - Jialu Song; Fan Yang; Zhenyu Qin; Leon Bagas; Yingjie Li; Xiaoyu Ge; Likun Yang (Journal of Geochemical Exploration, 2026)

A novel method for remote sensing phycocyanin leveraging optical classification and an integrated machine learning algorithm - Shizhuo Liu; Chong Fang; Kaishan Song; Ge Liu; Zhidan Wen; Yingxin Shang; Sijia Li; Hui Tao; Zhaojiang Yan; Lili Lyu; Yunfeng Lyu (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

From origin tracing, processing, to quality regulation: Molecular mechanism advances in medicinal foods research by integrating multi-omics tools - Jian-Hang Cai; Guan-Dong Fang; Yan Zhang; Jie Song; Jia-Yi Weng; Xue-Mei Ge; Issoufou Amadou; Xiang-Rong Cheng (Food Bioscience, 2026)

Precision screening of Lactobacillus with potential anti-allergenic using dual cell model - Xiang-Ge Xin; Yue Meng; Zai-Chen Li; Jun Xi; Jun Meng; Chang-He Ding; Dong-Ge Zheng; Ling-Guang Du; Shu-Song Wang (Food Bioscience, 2026)

Inhaled General Anesthetics in Alzheimer’s Disease Progression: Divergent Effects, Underlying Mechanisms, and Future Perspectives - Luoman Yang; Ge Song; Emily Parker; Luodan Yang (Molecular Neurobiology, 2026)

Influence of Grouting Pipe Lifting Rate on Vacuum Preloading Performance for Dredged Sludge - Zhou Changchen; Jin Fangyi; Xu Li; Li Dawei; Ni Junfeng; Yan Shuaixin; Xu Mintao; Han Song; Ge Bin; Wu Yehu; Zhang Ye (Geotechnical and Geological Engineering, 2026)

Differential evolution with bi-strategy co-deployment framework and diversity improvement - Liangliang Sun; Zhenghao Song; Ge Guo; Yucheng Zhang; Natalja Matsveichuk; Yuri Sotskov (Swarm and Evolutionary Computation, 2025)

Estimating the energy dissipation demand of self-centering shear walls considering diverse seismic scenarios - Ge Song; Lili Xing (Soil Dynamics and Earthquake Engineering, 2025)

Corrigendum to “Ecosystem sustainability of rice and aquatic animal co-culture systems and a synthesis of its underlying mechanisms” [Science of the Total Environment, 880 (2023) 163314] - Lei Ge; Yu Sun; Yujie Li; Luyao Wang; Guanqing Guo; Lili Song; Cui Wang; Guogan Wu; Shuangxi Li; Peng Li (Science of The Total Environment, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Seasonal and diurnal variations of pCO2 from reservoirs and lakes in Northeast China - Shiwei Liu; Zhidan Wen; Ge Liu; Yingxin Shang; Junbin Hou; Hui Tao; Chong Fang; Sijia Li; Xiangfei Yu; Jiarui Han; Jiping Liu; Kaishan Song (Journal of Hydrology, 2025)

Comparative assessment of real-world vehicle particulate emissions: Brake wear versus exhaust emissions - Changyu Wang; Chenyu Song; Wenfeng Xie; Aihong Li; Wanyi Chen; Yitu Lai; Sheng Su; Yachao Wang; Yunshan Ge (Journal of Cleaner Production, 2025)

Effects of Cr(VI) shock on microbial metabolic pathways: From simultaneous nitrification and denitrification to complete chromium reduction - Jiaojiao Niu; Jinxin Song; Qian Wang; Ge Cao; Xin Yuan; Chunfang Chao; Jinshuang Zhang; Marjangul Nuramkhaan; Yingxin Zhao (Journal of Environmental Chemical Engineering, 2025)

Smart Fe3O4-Zn NPs nanoplatforms: Integrated antibacterial activity, biofilm eradication, and magnetic propulsion for medical catheter blockage - Yuhan Ji; Xuechao Shi; Shuxian Hou; Jiaqin Huang; Jun Ge; Zhiru Tao; Xinxin Liu; Guanglei Feng; Shujie Li; Yao Xiao; Yimei Wang; Fei Ge; et al. (Journal of Environmental Chemical Engineering, 2025)

Synergistic photothermal-magnetic nanoplatform: Recyclable TEG-SPIONs for ultra-efficient pathogen elimination in medical wastewater - Fei Ge; Yimei Wang; Jun Ge; Guoqiang Yang; Xinxin Liu; Shuxian Hou; Xuechao Shi; Yao Xiao; Shujie Li; Weiwei Zhang; Wanzhen Li; Ping Song; et al. (Journal of Environmental Chemical Engineering, 2025)

Combining functional fucoidan with zein to enhance the adhesion and differentiation of myoblast cells - Wanli Xiong; Yi Zhou; Miaomiao Chai; Yawen Chen; Wenjing Dai; Lu Wang; Chengxin Ge; Wen-song Tan; Yan Zhou (Food Research International, 2025)

Quantitative phosphoproteomic-based insights into dephosphorylation-enhanced myofibrillar protein degradation via mitochondrial apoptosis modulation - Qing Lei; Shunan Song; Yangyu Su; Wupeng Ge; Jiaying Zhang (Food Chemistry, 2025)

A comprehensive story of pea peptides and pea polyphenols: Research status, existing problems, and development trends - Xinyu Sun; Guocong Ma; Dan Hai; Ge Bai; Qi Guo; Tianlin Wang; Xianqing Huang; Lianjun Song (Food Chemistry, 2025)

Biochar alleviates ammonium-induced suppression of methane uptake in a subtropical forest soil - Jiashu Zhou; Yanfei Dong; Caixian Tang; Zhenhui Jiang; Xinzhang Song; Mouliang Xiao; Hua Qin; Yunying Fang; Xiaokai Zhang; Tida Ge; Yu Luo; Shuokang Liu; et al. (Chemical Engineering Journal, 2025)

Gold nanoparticles recovered from e-waste by one-dimensional covalent organic framework for highly efficient reduction of nitrophenols - Wenping Yao; Bangdi Ge; Yuze Chen; Wenyu Jiao; Hao Han; Xiaowei Song; Zhiqiang Liang (Chemical Engineering Journal, 2025)

Bipolar reduction for efficient gold extraction from dilute Au(S2O3)23− solution at low cell voltage - Yumeng Liang; Wei Lian; Chang Liu; Peng Chen; Jianbang Ge; Chun Zhan; Jianbo Li; Shaoxian Song; Feifei Jia (Chemical Engineering Journal, 2025)

Enhanced production of sabinene by engineered Saccharomyces cerevisiae from corn hydrolysates - Lijuan Liu; Laibo Song; Chang Qi; Xiaohe Cao; Shiyong Huang; Ge Zhang; Guoqiang Chen; Xiao men; Haibo Zhang (Brazilian Journal of Microbiology, 2025)

DOM from eco-friendly fertilizers increases soil potential pathogen risk and shapes specific microbial populations under sprinkler and drip irrigation - Jinluo Fan; Rui Song; Heng Luo; Haijun Wu; Dongming Wu; Jun Wang; Yanqun Guo; Shuailing Hou; Mingguang Luo; Guoliang Ren; Hui Deng; Jiwei Luo; et al. (Applied Soil Ecology, 2025)

Inter‐Decadal Changes of Indian Ocean Dipole Around the Early 1980s and the Related Atmospheric and Oceanic Processes - Ge Song; Rongcai Ren (International Journal of Climatology, 2025)
This study demonstrates a significant inter‐decadal change of Indian Ocean Dipole (IOD) around the early 1980s and its connection to Pacific Decadal Oscillation (PDO). The changes of IOD include an initiation advancing and an increase in the occurrence of IOD events, particularly negative IOD events. Associated is an inter‐decadal strengthening of the coupling between IOD and sub‐surface IOD (Sub‐IOD) since the boreal spring season of IOD years. All these inter‐decadal changes coincide with the phase transition of PDO around the early 1980s, which has exerted its influence through atmospheric and oceanic pathways. On the one hand, negative/positive PDO forces easterly/westerly anomalies over the tropical Indian Ocean (TIO) by modulating Walker circulation, which is responsible for the increase in the occurrence of positive/negative IOD events. On the other hand, through the Indonesian Through Flow, PDO forced oceanic Rossby waves propagate westward from the Pacific to the Indian Ocean which contributes to deepening/shoaling the thermocline in the southwestern Indian Ocean. The inter‐decadal steepening of the TIO thermocline around the early 1980s, together with the strengthening of the surface westerly anomalies, gives rise to the strengthening of the vertical coupling between IOD and Sub‐IOD since the spring, which is mainly responsible for the inter‐decadal initiation advancing of IOD events. Though the initiation advancing of IOD events in the Coupled Model Inter‐comparison Project phase 6 (CMIP6) simulations is not as obvious as that in the reanalysis data, the linkage between positive PDO and the initiation advancing of negative IOD events also can be reproduced.

Prediction and sensitivity analysis of hysteretic energy spectra for self-centering systems using artificial neural network considering Chinese seismic scenarios - Ge Song; Lili Xing (Soil Dynamics and Earthquake Engineering, 2025)

Small lakes, big improvements: a multi-decadal assessment of policy and climate impacts on chlorophyll-a in China - Sijia Li; Hong Yang; Ge Liu; Dehua Mao; Zongming Wang; Haiqing Liao; Lele Zhang; Haoyun Zhou; Meichen Ji; Kaishan Song (Science Bulletin, 2025)

Wind-driven nearshore wave downscaling based on a coupled deep learning model - Miao Yu; Zhifeng Wang; Hongli Ge; Dalei Song (Ocean Engineering, 2025)

Flash roasting for phase transformation of α-spodumene coupled with sulfuric acid pressure leaching to enhance lithium extraction - Dongqi Song; Wei Chen; Qingkang Yan; Yu Liu; Ge Kuang; Hui Guo; Guosheng Li; Yijun Cao (Minerals Engineering, 2025)

An improved model based on lattice Boltzmann method for the simulation of water and salt migration in unsaturated soils - Chao Shen; Guo Tian; Shen Wei; Dongwei Zhang; Ge Song (Journal of Hydrology, 2025)

Schwertmannite maintains effective stabilization of arsenic in flooded paddy soil: Insights from a two-season rice experiment and underlying mechanisms - Ru Wang; Yang Song; Yinglin Guo; Nan Ge; Xiaomeng Wang; Lixiang Zhou; Guanyu Zheng (Journal of Hazardous Materials, 2025)

Enhanced insecticidal activity and bioavailability of thiacloprid from pH-responsive porous MPN(Fe)@ZIF-8 nanocarrier - Miao Wang; Donghui Xu; Ying Zhang; Jie Zhou; Zhihao Lin; Yiming Zhao; Xin Ding; Bin Sheng; Xiaobin Wen; Xiao Song; Ge Chen; Xiaomin Xu; et al. (Journal of Cleaner Production, 2025)

Hydrogen and methane production from hydrothermal wastewater via two-stage anaerobic fermentation: Impact of typical toxic components in wastewater - Ruikun Wang; Gaoke Song; Yehong Zhang; Zherui Ma; Junhui Hu; Zhenghui Zhao; Qianqian Yin; Lichao Ge (Journal of Environmental Management, 2025)

Unraveling the effect of ultrasound-assisted alkali treatment on β-lactoglobulin-flavonoids covalent complex system formation and its potential for lipophilic bioactive compounds delivery - Gongshuai Song; Haina Hou; Tian Zhao; Nengliang Jiang; Qing Ge; Danli Wang; Tinglan Yuan; Ling Li; Jinyan Gong (Food Chemistry, 2025)

Optimizing water management in water-saving and drought-resistant rice cultivation reduces methane emissions with enhanced net economic benefits - Keda Jin; Yuting Yang; Kaifu Song; Jing Ma; Yujiao Dong; Zhenke Zhu; Tida Ge; Shihua Lv; Guangbin Zhang; Hua Xu (Field Crops Research, 2025)

Association of ambient fine particulate matter (PM2.5) and its constituents with risk of pulmonary nodules in a lung cancer screening project - Xinyuan Ge; Ci Song; Chen Zhu; Yang Ding; Maojie Liu; Juan Yang; Chan Tian; Jiahao Zhang; Lili Wu; Lingying Zhu; Lei Shi; Xiangdong Cheng; et al. (Environmental Research, 2025)

Flexural performance of concrete beams hybrid reinforced with bundled stainless steel bars and BFRP bars - Yi Zheng; Zeyang Sun; Shichao Song; Liuzhen Yao; Jin Chen; Yu Tang; Hanbin Ge (Engineering Structures, 2025)

Amino acid functionalized carbon sheet network with confinement effect for capacitive desalination and supercapacitor - Chengyan Ge; Jing Huang; Jiani Wang; Yini Song; Jianping Zeng; Dawei Wang; Yujing Zheng; Guiyun Yu; Yong Dai; Yue Lian (Desalination, 2025)

Dual-stage reverse-dialysis-engineered cartilage-biomimetic hydrogels: Highly resilient anti-swelling double-layer architectures - Zheng-Feng Zhang; Mei-Yan Ling; Xiao-Rui Ge; Jia-Ying Chen; Bei Zhang; Xiao-Hui Yao; Peng Song; Wei-Guo Zhao; Dong-Yang Zhang; Jun Wang (Chemical Engineering Journal, 2025)

High performance wide-bandgap perovskite solar cells based on bulk and top surface dual passivation - Chuanliang Chen; Lixin Song; Yansong Ge; Yangruiyi Gao; Lishuai Huang; Weiqing Chen; Wei Ai; Chen Wang; Guojia Fang (Chemical Engineering Journal, 2025)

Damaged mitochondria targeted copper doped carbon dots as a fluorescent probe hitchhike on circulated neutrophils for precise treatment of ischemic stroke - Ge Zhang; Yan Sun; Fang Li; Yong Liu; Mengdi Sun; Mingzhu Song; Ruizhen Lv; Jia Dong; Yijie Shi; Liang Zhao (Chemical Engineering Journal, 2025)

Cracking the code of CO2 Photoreduction: Band engineering in BN for methane selectivity - Zhen Ge; Pengxin Pu; Haisong Feng; Mengjie Yu; Guanyi Zhang; Tianyong Liu; Xin Song; Shiquan Zhao; Lei Wang; Yusen Yang; Yibo Dou; Min Wei; et al. (Chemical Engineering Journal, 2025)

New insights to sustainable utilization of cultivated land: a synergistic path for coordinating competition of cultivated land utilization for crops based on multiple stakeholders - Zhaoyang Cai; Ge Song; Ruiqing Su; Yue Wang (Environment, Development and Sustainability, 2025)

Managing urban parks to unlock carbon sequestration potential: Active LiDAR and machine learning approach - Xiaoli Jia; Peihao Song; Yang Liu; Ruizhen He; Guohang Tian; Shidong Ge; Yakai Lei (Urban Forestry & Urban Greening, 2025)

Enhancing spatiotemporal coverage of satellite-derived high-resolution NO2 data with a super-resolution model - Maolin Zhang; Siwei Li; Jia Xing; Ge Song; Shuangliang Li; Jiaxin Dong; Shuxin Zheng; Ge Han; Jie Yang (Remote Sensing of Environment, 2025)

Assessment of environmental and health impacts during 3D printing of candidate polymeric materials for space additive manufacturing - Junling Li; Yi Liu; Chao Peng; Qifan Liu; Wei Zhao; Mingyuan Liu; Xinyu Du; Yongyin Yan; Yufei Song; Kaihui Xia; Chun Chen; Haijie Zhang; et al. (Journal of Hazardous Materials, 2025)

Occurrence, removal and ecotoxicological assessment of halogenated dissolved organic matter in waste leachates - Xian-Ge Wang; Wei He; Xiao-Song He; Xu Cao; Yue Sun; Xian-Jiang Zeng (Journal of Hazardous Materials, 2025)

Integrated machine learning model for prediction of nutrients contents and maturity in rural organic solid wastes aerobic composting - Hao Peng; Lan Mu; Yingjin Song; Hong Su; Yadong Ge; Zhanjun Cheng; Rundong Li; Guanyi Chen (Journal of Environmental Chemical Engineering, 2025)

Asynchronous modes of paleofire occurrence in eastern monsoonal China since the LGM - Menglin Song; John Dodson; Scott Mooney; Ge Shi; Hong Yan (Global and Planetary Change, 2025)

Vegetation-driven differences in soil CO2 emissions and carbon-sequestering microbiomes of estuarine salt marsh and mangrove wetlands - Lin Wang; Yangyang Xie; Weiqi Wang; Yuan Li; Ning Hou; Rongbin Yin; Zhaoliang Song; Jordi Sardans; Maoquan Ge; Yiyang Liao; Derrick Y.F. Lai; Josep Peñuelas (Environmental Research, 2025)

Branched ligand-functionalized immuno-evasive PEGylation (BLIP) platform: Breaking through accelerated blood clearance and chemoresistance barriers with dual-targeting RNAi-chemotherapy synergy - Mengyang Liu; Ruijuan Xing; Ge Chen; Yuxiang Liang; Lu Huang; Yumeng Xi; Yue Li; Shifei Zhang; Yanan Sun; Yupin Song; Jintao Hao; Kexin Cong; et al. (Chemical Engineering Journal, 2025)

Potential tuning of polycrystalline piezoelectric component for effective energy-band structure and markedly enhanced H2 yield of photocatalytic component - Xinxin Jin; Yingshuang Zhang; Xiao Li; Peng Liu; Qinghao Ge; Zhihao Zhao; Xingzhang Li; Lige Gong; Zhiping Zhang; Dan Li; Feng-Ming Zhang; Limin Dong; et al. (Chemical Engineering Journal, 2025)

Dual-functional berberine-magnolol co-assembled nanoparticles inhibit Fusarium graminearum growth and mycotoxin production - Chenguo Li; Wei He; Yao Cui; Shimin Wu; Qing'ao Song; Ying Li; Jimin Guo; Xizhen Ge; Pingfang Tian (Pesticide Biochemistry and Physiology, 2025)

Occurrence, molecular transformation and prioritizing environmental risks of organic nitrogen in aqueous phase from hydrothermal carbonization of waste activated sludge - Tingting Yang; Lichao Tan; Jiaqi Ge; Xue Zhang; Gang Zhou; Ping Li; Ninghui Song; Feng Ge (Journal of Hazardous Materials, 2025)

Short-chain chlorinated paraffins at environmentally relevant doses disrupt glucose homeostasis and insulin signaling by macrophage-mediated inflammation - Ying-Wen Mu; Wen-Huan Yao; Hui Li; Cui-Li Zhang; Yan-Jing Zhang; Xiu-Ning Zhang; Ge Song; Xiu-Lan Zhao; Tao Zeng (Journal of Hazardous Materials, 2025)

Metabolomic profiling unveils biochemical dynamics in spontaneously fermented grape leaf by-products: towards sustainable agricultural waste valorization - Jia-Lin Xing; Yun-Lu Song; Yan-Ge Li; Lu Yang; Ke-Ying Duan; Ding-Ding Zuo; Jing Zhang; Hai-Nan Liu; Tong-Lu Wei; Mao-Song Pei; Da-Long Guo (Food Bioscience, 2025)

Thiazole-fused thiazoliniums with ketone warheads as covalent inhibitors targeting Cys44 of SARS-CoV-2 3CLpro - Qizhen Cao; Zhaoqin Zhang; Guanghao Zhu; Sanfeng Dong; Xue Sun; Yuqing Song; Ya Zhang; Tingting Cai; Xinben Zhang; Yong Zhang; Zhijian Xu; Ruisheng Xiong; et al. (Chemico-Biological Interactions, 2025)

Fe3O4 nanoparticles promote methanogenesis in propionate acclimated system - Fangzhou Wang; Ge Song; Mou Zhang; Shunan Zhao; Tuo Wang; Kai Zhao; Xin Wang; Ruiping Liu (Bioresource Technology, 2025)

Little evidence suggests microplastics negatively impact embryo growth of a viviparous shark Prionace glauca - Huachen Gao; Yujing Ge; Wei Song; Yi Gong; Jiangfeng Zhu (Aquatic Toxicology, 2025)

Identification and characterization of the miR396f-GRF10 module in phase transition of Lilium - Meiqi Song; Ping Lu; Yue Yin; Xuewei Zhang; Wei Ge; Kezhong Zhang (Planta, 2025)

A practice guideline for therapeutic drug monitoring of mycophenolic acid for solid organ transplants - Shuang Liu; Hongsheng Chen; Zaiwei Song; Qi Guo; Xianglin Zhang; Bingyi Shi; Suodi Zhai; Lingli Zhang; Liyan Miao; Liyan Cui; Xiao Chen; Yalin Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2025)
Mycophenolic acid (MPA), the active moiety of both mycophenolate mofetil (MMF) and enteric-coated mycophenolate sodium (EC-MPS), serves as a primary immunosuppressant for maintaining solid organ transplants. Therapeutic drug monitoring (TDM) enhances treatment outcomes through tailored approaches. This study aimed to develop an evidence-based guideline for MPA TDM, facilitating its rational application in clinical settings. The guideline plan was drawn from the Institute of Medicine and World Health Organization (WHO) guidelines. Using the Delphi method, clinical questions and outcome indicators were generated. Systematic reviews, Grading of Recommendations Assessment, Development, and Evaluation (GRADE) evidence quality evaluations, expert opinions, and patient values guided evidence-based suggestions for the guideline. External reviews further refined the recommendations. The guideline for the TDM of MPA (IPGRP-2020CN099) consists of four sections and 16 recommendations encompassing target populations, monitoring strategies, dosage regimens, and influencing factors. High-risk populations, timing of TDM, area under the curve (AUC) versus trough concentration ( C 0 ), target concentration ranges, monitoring frequency, and analytical methods are addressed. Formulation-specific recommendations, initial dosage regimens, populations with unique considerations, pharmacokinetic-informed dosing, body weight factors, pharmacogenetics, and drug–drug interactions are covered. The evidence-based guideline offers a comprehensive recommendation for solid organ transplant recipients undergoing MPA therapy, promoting standardization of MPA TDM, and enhancing treatment efficacy and safety.

Production of phytoliths and phytoc in above- and belowground parts of common reed (Phragmites australis) in a riverine wetland of the Yellow River Delta, China - Li Zhang; Wenyi Sheng; Huijia Song; Lele Liu; Weihua Guo; Yuzhi Wang; Changzi Ge (Journal of Soils and Sediments, 2025)

Integrative analysis of copper dysregulation and cuproptosis in postnatal hematopoiesis - Liyun Chen; Qian Wu; Chaohui Lin; Zijun Song; Yunxing Su; Chaodong Ge; Xue Wang; Hongbing Luo; Rong Wang; Yanfang Wang; Junxia Min; Fudi Wang (Science Bulletin, 2025)

Thermodynamic and kinetic studies of CO2 hydrate stability in complex deep-oceanic environments - Lei Zhang; Ziming Yang; Yang Ge; Bingbing Chen; Huiru Sun; Yongchen Song; Mingjun Yang (Process Safety and Environmental Protection, 2025)

Effects of reversing the light-dark cycle on growth performance and intestinal health in heat-stressed broilers - Huiyuan Rui; Xiangyang Xu; Fei Song; Aige Han; Meiwei Lv; Xin Kang; Ming Ge; Xiaowen Jiang; Wenhui Yu (Journal of Thermal Biology, 2025)

Sparingly-soluble CaCO3 promotes plant growth and arsenic accumulation in As-hyperaccumulator Pteris vittata: Oxidative stress and gene expression in As metabolisms - Yu-Fei Yang; Shu-Fen Xiao; Chun-Yan Hu; Qian-Yu Zhou; Chen-Jing Liu; Song-Ge Deng; Lena Q. Ma (Journal of Hazardous Materials, 2025)

The influence of mineralogical characteristics and pH on uranium extraction via in-situ leaching: Preliminary case analysis of the Hadatu uranium deposit, China - Peng Qiao; Shengqing Xiong; Liangquan Ge; Hao Song; Huijie Yu; Yihan Yang; Ruyi Wang; Shihu Kang; Yiru Zhou; Yuanqing Fan (Hydrometallurgy, 2025)

Rare earth ions-reinforced polycationic gel polymer electrolytes for enhancing ionic conductivity and zinc anode interface stability in flexible zinc-air batteries - Hang Zhang; Jianrong Liang; Ziran You; Ying Gao; Yachu Song; Junjie Ge; Yanhao Duan; Xingchen Yan; Da Lei; Chuanling Si; Zhengzheng Li (Chemical Engineering Journal, 2025)

Integrating genome assembly, structural variation map construction and GWAS reveal the impact of SVs on agronomic traits of Brassica napus - Nian Wang; Xianshuai Song; Lieqiong Kuang; Ze Tian; Kaifeng Wang; Keqi Li; Lan Ge; Yu Wu; Xinfa Wang; Xiaoling Dun; Hanzhong Wang (Theoretical and Applied Genetics, 2025)

Groundwater level response to river seepage variations in the lower reaches of the Yellow River, China - Jinting Huang; Zhan Yang; Qiu Lv; Jiawei Wang; Ge Song; Qiang Wang (Hydrogeology Journal, 2025)

Effects of MicroRNA-19b Carried by Endothelial Microparticles on the Phenotypic Switching of Vascular Smooth Muscle Cells and the Working Mechanism - Yuxia Cui; Junxian Song; Ting Ge; Manyan Wu; Chongyou Lee; Hong Chen (Bulletin of Experimental Biology and Medicine, 2025)

AMF and biochar reshape the bacterial network in rhizosphere soil of Ricinus communis under chromium (Cr) stress and improve soil quality - Yuqiang Wen; Ruotong Wu; Tianle Xu; Ranran Cao; Ge Song; Dandan Qi; Wei Chang; Kun Li; Yuan Ping; Mengmeng Zhang; Xiaoxu Fan; Fuqiang Song (Journal of Hazardous Materials, 2025)

Reutilization of steel slag (SS) in super sulfate cement (SSC): A comparative study of SS dosage and carbonation treatment on strength development, hydration behavior and sustainable development - Xiaowei Ge; Xiaowei Gu; Jianping Liu; Ge Song; Shaoqian Liu; Xu Wang; Shenyu Wang; Ziyang Hu; Hao Wang; Moncef L. Nehdi (Environmental Research, 2025)

Influence of operation sequences on phosphorus enrichment by polyphosphate accumulating organisms biofilm: Performance, phosphorus transfer and phosphate metabolism in biofilm - Ge Song; Zhen Bi; Yuqing Liu; Yong Huang (Environmental Research, 2025)

SLC39A10 is a key zinc transporter in T cells and its loss mitigates autoimmune disease - Yichang Shao; Qingdian Mu; Rong Wang; Hongbin Luo; Zijun Song; Pengfei Wang; Jingshu Song; Chaodong Ge; Jiyan Zhang; Junxia Min; Fudi Wang (Science China Life Sciences, 2025)

High-resolution VOCs measurements and photochemical impact analysis for typical solid waste base in summer - Shuwei Zhang; Song Gao; Pengjie Yuan; Zekai Yang; Yajing Ma; Xiang Ge; Lipeng Liu; Zheng Jiao; Tronganh Nguyen (Air Quality, Atmosphere & Health, 2025)

Study on the carbon emission reduction potential of rural domestic waste based on life cycle approach in Hubei Province, China - Zhongcheng Zhang; Kaiwei Huang; Jiafu Zhang; Jun Xiao; Haiyu Peng; Xiaodong Ge; Hui Zhang; Mingwei Song (Environmental Science and Pollution Research, 2025)

Paired electrocatalysis for simultaneous anodic oxidation of tetracycline and cathodic nitrate reduction to ammonia - Chunhong Fu; Huizhong Wu; Jiangli Sun; Ge Song; Minghua Zhou (Journal of Hazardous Materials, 2025)

Effect of anion on anaerobic digestion of sewage sludge: Methane production and microbial characterization - Min Yang; B. Hasaer; Guanghui Wang; Xueyi Li; Ge Song; Kai Zhao; Ruiping Liu (Journal of Environmental Chemical Engineering, 2025)

Edible starch-based films modified by fruit and vegetable juices: Preparation, performance evaluation and seasoning bag design - Xinyu Sun; Guocong Ma; Xiaoling Tian; Dan Hai; Yan Ma; Ge Bai; Lianjun Song; Qinghua Yang; Xianqing Huang (Food Packaging and Shelf Life, 2025)

Associations between urinary antibiotics exposure and semen parameters among adult men: A biomonitoring-based cross-sectional study - Qunshan Shen; Lei Ge; Yuqi Zhou; Yang Liu; Ruiyang Hu; Menglong Geng; Xiaojin He; Yunxia Cao; Bing Song (Environmental Pollution, 2025)

Flexible, scalable, and bifunctional MOF-based nanofibrous membranes with gems-on-string structure for simultaneous efficient water evaporation and pollution remediation - Song Ge; Jun Song; Jichao Zhang; Xiu-Li Yang; Ming-Hua Xie (Chemical Engineering Journal, 2025)

Global trends in staphylococcus aureus-related lower respiratory infections from 1990 to 2021: findings from the 2021 global burden of disease report - Hong Chen; Shuang Song; Rui Cui; Yong-Wang Feng; Peng Ge (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Monitoring phycocyanin in global inland waters by remote sensing: Progress and future developments - Chong Fang; Kaishan Song; Zhaojiang Yan; Ge Liu (Water Research, 2025)

Dual pathways of carbon neutrality in urban green spaces: assessment and regulatory strategies - Yuan Feng; Chenyu Fang; Xiaoli Jia; Peihao Song; Lin Zhou; Xin Xu; Kun Wang; Ruizhen He; Nan Guo; Shidong Ge (Sustainable Cities and Society, 2025)

Contamination, multimedia partitioning, and priority list of steroids and their metabolites in coastal regions of the Greater Bay Area, China - Qin-Ge Zhou; Shan Liu; Yuan Liu; Nian-Nian Wu; Qing-Song Yang; Heng-Xiang Li; Xiang-Rong Xu; Juan Ling (Process Safety and Environmental Protection, 2025)

Strategies optimization to improve environmental benefit of chicken manure anaerobic digestion in China: Insight from life cycle assessment - Fangzhou Wang; Shunan Zhao; Yizhu Sun; Ge Song; Yifan Sun; Kai Zhao; Ruiping Liu; Yu-You Li (Journal of Cleaner Production, 2025)

Cyanidin-3-glucoside improves cognitive impairment in naturally aging mice by modulating the gut microbiota and activating the ERK/CREB/BDNF pathway - Yuyu Chen; Wentao Qi; Wenting Peng; Wei Fang; Ge Song; Yanling Hao; Yong Wang (Food Research International, 2025)

Sustained superiority of biochar over straw for enhancing soil biological-phosphorus via the mediation of phoD-harboring bacteria in subtropical Moso bamboo forests - Zhenhui Jiang; Tony Vancov; Yunying Fang; Caixian Tang; Wenyi Zhang; Mouliang Xiao; Xinzhang Song; Jiashu Zhou; Tida Ge; Yanjiang Cai; Bing Yu; Jason C. White; et al. (Forest Ecology and Management, 2025)

Super hybrid rice improved yield by increasing spikelet amount and efficiency under optimized density-nitrogen cultivation - Jialin Ge; Xu Chen; Xiaowei Song; Huanhe Wei; Qigen Dai (Field Crops Research, 2025)

Combination of NRPS/PKS tuning and morphological engineering enhanced iturin A production in Bacillus amyloliquefaciens - Zheng-Jie Hou; Hai-Meng Lai; Kai-Ge Song; Dun-Ju Wang; Qiu-Man Xu; Jing-Sheng Cheng (Chemical Engineering Journal, 2025)

Synergistic Na-S modified Fe-Cu catalysts for efficient CO2 hydrogenation to higher alcohols - Ruwei Yao; Yang Yu; Bin Wu; Yueyin Song; Qinqin Niu; Congming Li; Jian Wei; Qingjie Ge (Chemical Engineering Journal, 2025)

Island-shaped micro-cracks evolution in ultrathin film enables ultra-sensitive for strain sensors under high temperatures - Ge Wang; Yifan Zhao; Ziang Wang; Jian Wang; Song Wang; Yaxin Zhang; Kun Zheng; Feng Han; Chenying Wang; Zhuangde Jiang (Chemical Engineering Journal, 2025)

Efficient waste polyester plastics recycling in organic–inorganic acid catalytic system - Guohao Xu; Haobin Ge; Kai He; Zhaopeng Sun; Xinyue He; Jichang Liu; Bingjie Zhou; Yulin Deng; Jianfei Song; Wei Liu (Chemical Engineering Journal, 2025)

Biomedical data and AI - Hao Xu; Shibo Zhou; Zefeng Zhu; Vincenzo Vitelli; Liangyi Chen; Ziwei Dai; Ning Yang; Luhua Lai; Shengyong Yang; Sergey Ovchinnikov; Zhuoran Qiao; Sirui Liu; et al. (Science China Life Sciences, 2025)

Emulation of Schrödinger dynamics with metamaterials - Zhao-Xian Chen; Wan-Ge Song; Guang-Chen He; Xiao-Meng Zhang; Ze-Guo Chen; Haitan Xu; Emil Prodan (Science Bulletin, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Optimization and identification of key process parameters for in-situ leaching of uranium in the Barun uranium deposit, China - Peng Qiao; Yuanqing Fan; Shengqing Xiong; Liangquan Ge; Yixuan Yao; Ruyi Wang; Hao Song; Huijie Yu; Xiaoping Ren; Zengjie Gui (Ore and Energy Resource Geology, 2025)

Large-scale metabolomic landscape of edible maize reveals convergent changes in metabolite differentiation and facilitates its breeding improvement - Chunhui Li; Zhiyong Li; Baishan Lu; Yaxing Shi; Senlin Xiao; Hui Dong; Ruyang Zhang; Hui Liu; Yanyan Jiao; Li Xu; Aiguo Su; Xiaqing Wang; et al. (Molecular Plant, 2025)

Corrigendum to “High leucine bioavailability improves beef quality by altering serum metabolism in beef cattle” [Meat Science volume 220 (2025) 109693] - Jishan An; Xiangchao Zhao; Yang Song; Huitian He; Zuo Wang; Xinyi Lan; Yu Ge; Lei Liu; Anwei Cheng; Weijun Shen; Fachun Wan (Meat Science, 2025)

Photochemical properties and toxicity of fluoroquinolone antibiotics impacted by complexation with metal ions in different pH solutions - Shengkai Cao; Peng Zhang; Heming Song; Linke Ge; Junfeng Niu (Journal of Environmental Sciences, 2025)

Study on the mechanism of pseudo-interpenetrating network enhancing recyclable VES-CO2 foam system and the key performance as fracturing fluid - Nanxin Zheng; Jingyi Zhu; Zhaozhong Yang; Chao Song; Xiaogang Li; Yufeng Long; Liangping Yi; Jianlin Lai; Jingnan Ge (Fuel, 2025)

Comprehensive evaluation of low-carbon cementitious materials prepared with industrial by-product calcium carbide residue (CCR) as alkali source - Xiaowei Ge; Xiaowei Gu; Ge Song; Jianping Liu; Shenyu Wang; Ziyang Hu; Xu Wang; Zhihang Hu; Hao Wang (Environmental Research, 2025)

Bilateral energy level tuning for efficient inverted perovskite solar cells - Xinhang Cai; Xianzhao Wang; Yuting Song; Haoyu Ge; Aijun Li; Qingyuan Zhao; Ziyan Liu; Naoyuki Shibayama; Yisong Zheng; Xiao-Feng Wang (Chemical Engineering Journal, 2025)

Assembly of allophycocyanin from individual subunits: involvement of apo-form in the formation of trimers - Daria V. Bodunova; Daniil A. Gvozdev; Olesya V. Bukach; Svetlana V. Sidorenko; Kristina V. Perfilova; Li Yu; Song Qin; Nikolai N. Sluchanko; Baosheng Ge; Eugene G. Maksimov (Photosynthesis Research, 2025)

Full-Scale Numerical Simulation of a Free-Running Cruise Ship in Heavy Head Sea Conditions - Shenwei Ge; Ji Zeng; Kewei Song; Junrui Jia (Journal of Marine Science and Engineering, 2025)
For a cruise ship in heavy sea conditions, self-propulsion performance prediction is important for ensuring its safety. In this study, a numerical simulation approach that models the free running of a ship is presented, and a full-scale small cruise ship is verified using a ship model experiment. Based on this method, a free-running cruise ship encountering six kinds of wave conditions was simulated, and the characteristics of the ship’s motion, added resistance, and propeller loading were analyzed. The results demonstrated that the free-running approach can simulate the self-propelled motion of a full-scale ship, and that it converges more quickly than the traditional self-propulsion simulation method. The ship’s speed, heave, pitch, and thrust fluctuated when it moved through the waves, and λ/Lwl had a greater influence on the amplitude of these fluctuations than did H/Lwl. Furthermore, the propeller loading exhibited a sharp increase, and the maximum loading coefficient exceeded 500%, which may pose a safety risk.

Mechanical Evaluation of Casing in Multiple Thermal Recovery Cycles for Offshore Heavy Oil Wells - Yuxian He; Yongpeng Song; Shenghua Hu; Hangming Liu; Xianchi Ge (Journal of Marine Science and Engineering, 2025)
China’s offshore heavy oil resources are abundant but underutilized. Circulating steam stimulation enhances production while increasing casing failure risks in thermal recovery wells. Accurately assessing casing performance after repeated thermal cycles is crucial for ensuring wellbore integrity. This paper presents tensile and creep experiments on TP110H casing under cyclic temperatures. The temperature distribution within the “casing-cement sheath-stratum” system is derived using heat transfer theory. Stress and displacement equations are established based on thick-walled cylinder theory and thermo-elasticity. Thermal coupling analysis assesses casing stress in straight, inclined, and sidetrack well sections. Key factors, including steam injection pressure, in situ stress, cement modulus, and prestress, are analyzed for their effects on cumulative strain below the packer. Strain-based methods evaluate casing safety. Results show that under thermal cycling at 350 °C, after 16 cycles, the casing’s elastic modulus, yield strength, and tensile strength decrease by 15.3%, 13.1%, and 10.1%, respectively, while the creep rate increases by 16.0%. Above the packer, the casing remains safe, but the lower section may be at risk. Using low-elasticity cement, higher steam injection pressure, and prestressing can help improve casing performance. This study provides guidance on enhancing casing safety and optimizing steam stimulation parameters.

Analysis of the effect of highway extra-long tunnel Accompanying vehicle lighting on driving behavior in horizontal curve − A driving simulation study - Hongcheng Ge; Cancan Song; Difei Jing; Wei Li; Ze Shi; Zhongyin Guo; Fangyan Zhang (Tunnelling and Underground Space Technology, 2025)

Effects of melatonin on the pharmacokinetics and amino acid metabolism profile of vigabatrin in rats - Qiang Zheng; Song-Lin Xu; Xin-Lin Guo; Chuan-Yu Wang; Meng-Die Ma; Jin-Fang Ge (Toxicology and Applied Pharmacology, 2025)

Nitrification inhibitor induced microbial NH4+-N immobilization improves maize nitrogen use efficiency in strong ammonia oxidation soil - Si-Yi Liu; Di Wu; Xiao-Tang Ju; Ju-Pei Shen; Yi Cheng; Na Deng; Xiao-Tong Song; Hong-Jie Di; Pei-Pei Li; Li-li Han; An-Hui Ge; Chuan-Fa Wu; et al. (Soil Biology and Biochemistry, 2025)

Enhancing panvascular medicine: unveiling the nexus of pan-cardio-oncology and expanding therapeutic frontiers - Yiqing Hu; You Zhou; Neng Dai; Shuai Song; Xin Zhao; Yongchao Zhao; Leilei Cheng; Hao Lu; Junbo Ge (Science Bulletin, 2025)

Widespread resistance of the apple aphid Aphis spiraecola to pyrethroids in China - Kang Wang; Yi You; Yunxiang Liu; Wenrong Xian; Yingying Song; You Ge; Xiaopeng Lu; Zhiqing Ma (Pesticide Biochemistry and Physiology, 2025)

Research on improved null space based unmanned surface vehicle formation maneuver control method for merchant ship escort - Yulei Liao; Yu Ge; Zhibin Song; Ruiwen Qian; Wei Yu; Yongtong Xu; Ye Li; Shuo Pang (Ocean Engineering, 2025)

Study on the main controlling factors on the differential accumulation of natural gas in multiple (ultra-)deeply-buried marine strata - Zezhang Song; Ziyu Zhang; Bing Luo; Wenjin Zhang; Changqi Liu; Xingwang Tian; Dailin Yang; Luya Wu; Bingfei Ge; Shigui Jin; Jiutao Yuan (Organic Geochemistry, 2025)

Solvent-free upcycling of agricultural plastic waste using in situ self-assembly metal nanoparticles co-doped microporous carbocatalyst for advanced transportation fuels - Ge Kong; Xiangru Yuan; Xiaojing Zhao; Jin Wang; Weizheng Zhong; Rongbin Qiu; Kai Song; Qing Cheng; Xuesong Zhang; Lujia Han (Journal of Hazardous Materials, 2025)

Enhanced biodegradation of monoaromatic hydrocarbons by a novel bacterial strain Pseudomonas viridilivida FB1 and biochar - Bing Hong; Wenli Zhu; Ting Wu; Hao Zhang; Huaiyu Ge; Tianyu Hu; Juan Zhao; Hua Fang; Chuanfu Song (Journal of Cleaner Production, 2025)

Satellite remote sensing of turbidity in Lake Xingkai using eight years of OLCI observations - Jian Li; Yang Li; Kaishan Song; Ge Liu; Shidi Shao; Bingqian Han; Yujin Zhou; Heng Lyu (Journal of Environmental Management, 2025)

Highly durable SLIPS with temperature-responsive switching for efficient anti-/deicing - Yucai Ge; Yuegan Song; Ke Li; Sensen Xuan; Lei Wang; Jiasong Liu; Guoqiang Li; Xiaopeng Wang; Jiaxin Yu; Yi Yang; Yuan Wang; Liang Chen; et al. (Chemical Engineering Journal, 2025)

A flexible, antifreezing, and long-term stable cellulose ionic conductive hydrogel via one-step preparation for flexible electronic sensors - Haiyue Miao; Yiyang Liu; Chongyang Zheng; Xiaojuan Huang; Yidan Song; Lulu Tong; Changwu Dong; Xiaobin Fu; Hailong Huang; Min Ge; Hongtao Liu; Yuan Qian (Carbohydrate Polymers, 2025)

A high-precision saltwater ice thickness and salinity detection method based on capacitive coupled planar microwave resonator - Han Shi; Mengjie Song; Junfeng Ge; Long Zhang; Xuan Zhang (Cold Regions Science and Technology, 2025)

Evaluation of enzyme activity predictions for variants of unknown significance in Arylsulfatase A - Shantanu Jain; Marena Trinidad; Thanh Binh Nguyen; Kaiya Jones; Santiago Diaz Neto; Fang Ge; Ailin Glagovsky; Cameron Jones; Giankaleb Moran; Boqi Wang; Kobra Rahimi; Sümeyra Zeynep Çalıcı; et al. (Human Genetics, 2025)

Hypoxia lowers cell carbon and nitrogen content and accelerates sinking of a marine diatom Thalassiosira pseudonana - Bokun Chen; Hui Song; Ge Xu; Hongli Ji; Xue Yang; Gang Li (Frontiers in Marine Science, 2025)
The positive or negative effect of a decrease in dissolved O 2 on the photophysiology of phytoplankton is determined by the duration of light exposure. To uncover the underlying mechanisms, the marine model diatom Thalassiosira pseudonana was cultured under three dissolved O 2 levels (8.0 mg L -1 , ambient O 2 ; 4.0 mg L -1 , low O 2 ; and 1.3 mg L -1 , hypoxia) to compare its growth, cell composition, and physiology between the light and dark periods. The results showed that the growth rate under ambient O 2 was 0.60 ± 0.02 day -1 , which was half of the growth rate during light period and 15-fold of the growth rate during dark period. Decreasing O 2 increased the growth rate during light period but decreased it during dark period and decreased the cell pigment content in both the light and dark periods. In the light, low O 2 increased cell carbon (C) content, while hypoxia decreased it, with the degree of increase and decrease being greater in the dark. Low O 2 had no significant effect on cell nitrogen (N) content, but hypoxia decreased it. Low O 2 had no significant effect on photosynthetic efficiency but decreased the dark respiration rate. In darkness, low O 2 had no significant effect on cell C loss rate but decreased N loss rate, leading to an increase in the POC/PON ratio. In addition, hypoxia exacerbated cell mortality and sinking, suggesting that diatom-derived carbon burial may be accelerated due to marine deoxygenation in the future.

Quantification of energy-dissipating capacity for self-centering shear walls considering variable loading sequences - Ge Song (Soil Dynamics and Earthquake Engineering, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

High leucine bioavailability improves beef quality by altering serum metabolism in beef cattle - Jishan An; Xiangchao Zhao; Yang Song; Huitian He; Zuo Wang; Xinyi Lan; Yu Ge; Lei Liu; Anwei Cheng; Weijun Shen; Fachun Wan (Meat Science, 2025)

Mitigating nitrobenzene toxicity in anaerobic digestion using hollow carbon spheres: Enhanced methane production via direct interspecies electron transfer - Shunan Zhao; Keyang Li; Shaoqing Zhu; Qianli Guo; Ge Song; Kai Zhao; Qianming Gong; Ruiping Liu (Journal of Water Process Engineering, 2025)

Influence mechanism of structure parameters for rotor-radial groove hydrodynamic cavitation reactor on cavitation and disinfection characteristics - Linhua Zhang; Lei Wang; Yongxing Song; Xiaotong Li; Yi Ge; Jingting Liu; Weibin Zhang (Journal of Environmental Chemical Engineering, 2025)

Large-scale rice mapping under spatiotemporal heterogeneity using multi-temporal SAR images and explainable deep learning - Ji Ge; Hong Zhang; Lijun Zuo; Lu Xu; Jingling Jiang; Mingyang Song; Yinhaibin Ding; Yazhe Xie; Fan Wu; Chao Wang; Wenjiang Huang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Synergistic effect of 2′-Fucosyllactose or galactooligosaccharide with Bifidobacterium bifidum DNG6 improves the intestinal barrier by modulating the SCFAs-TLR4/NF-κB cascade response in DSS-induced colitis in mice - Cui-Cui Sun; Yu-Qi Wang; Xin-Yu Wang; Guo-Fang Zhang; Hong-Fang Cao; Ge Song; Li-Bo Liu; Chun Li; Irina Valeryevna Boyarineva; Peng Du (Food Bioscience, 2025)

Influence of biodegradable microplastics on soil carbon cycling: Insights from soil respiration, enzyme activity, carbon use efficiency and microbial community - Dan Song; Guoqin Jin; Ziqi Su; Chaorong Ge; Haoxin Fan; Huaiying Yao (Environmental Research, 2025)

Research on building energy-saving based on GA-BP coupled improved multi-objective whale optimization algorithm - Zhimin Liu; Huijun Ge; Tao Song; Shiwei Ma (Energy and Buildings, 2025)

Intensifying bioconversion of rich-capsaicinoids food waste into fengycin by the tolerant-artificial consortium - Tian-Xu Duan; Kai-Ge Song; Hui-Zhong Sun; Wei Shang; Jing-Sheng Cheng (Chemical Engineering Journal, 2025)

Engineering the microenvironment in Ba-doped Fe catalyst with alkali metal promoters for enhanced CO2 hydrogenation to α-olefins - Joshua Iseoluwa Orege; Yang Yu; Jian Wei; Qixin Fan; Jixin Zhang; Lifei Song; Qingjie Ge; Jian Sun (Chemical Engineering Journal, 2025)

Correction: Exosomes derived from human exfoliated deciduous teeth ameliorate adult bone loss in mice through promoting osteogenesis - Jizhen Wei; Yeqing Song; Zhihao Du; Feiyan Yu; Yimei Zhang; Nan Jiang; Xuejun Ge (Journal of Molecular Histology, 2025)

Mechanism of acclimation to chronic intermittent hypoxia in the gills of largemouth bass (Micropterus salmoides) - Qiao Liu; Hong Wang; Jiayu Ge; Lipeng Guo; Rabia Tahir; Jie Luo; Kuo He; Haoxiao Yan; Xin Zhang; Quanquan Cao; Zhang Cheng; Liulan Zhao; et al. (Fish Physiology and Biochemistry, 2025)

Impacts of Spartina alterniflora invasion on soil carbon components of particulate and mineral-associated organic matter and soil organic matter mineralization in estuarine wetlands - Lin Wang; Yuan Li; Jie Hei; Weiqi Wang; Jordi Sardans; Zhihao Zhang; Fanjiang Zeng; Maoquan Ge; Yiyang Liao; Yunying Fang; Tony Vancov; Jiawei Gan; et al. (Applied Soil Ecology, 2025)

RETRACTED: Wang et al. Amplitude and Phase Computable Ocean Wave Real-Time Modeling with GPU Acceleration. J. Mar. Sci. Eng. 2022, 10, 1208 - Guigui Wang; Shihan Tan; Ge Song; Sheng Wang (Journal of Marine Science and Engineering, 2025)
The journal retracts the article titled “Amplitude and Phase Computable Ocean Wave Real-Time Modeling with GPU Acceleration” [...]

Counting wheat heads using a simulation model - Xiaoyong Sun; Tianyou Jiang; Jiming Hu; Zuojie Song; Yuheng Ge; Yongzhen Wang; Xu Liu; Jianhao Bing; Jinshan Li; Ziyu Zhou; Zhongzhen Tang; Yan Zhao; et al. (Computers and Electronics in Agriculture, 2025)

Using high CO2 concentrations to culture microalgae for lipid and fatty acid production: Synthesis based on a meta-analysis - Yuan Feng; Jingke Ge; Pau Loke Show; Chi Song; Liumiao Wu; Zengling Ma; Guang Gao (Aquaculture, 2025)

Earth's record-high greenness and its attributions in 2020 - Yulong Zhang; Jiafu Mao; Ge Sun; Qinfeng Guo; Jeffrey Atkins; Wenhong Li; Mingzhou Jin; Conghe Song; Jingfeng Xiao; Taehee Hwang; Tong Qiu; Lin Meng; et al. (Remote Sensing of Environment, 2025)

Tectono-sequence evolution of an extensional strike-slip composite basin, a case study of the Miaoxi'nan sub-sag in the eastern Bohai Bay Basin - Sheng Fu; Haifeng Yang; Lijun Song; Wei Zhou; Jiawang Ge; Yanqin Guo (Marine and Petroleum Geology, 2025)

Characteristic analysis and diagnosis method optimization of scroll compressor pressure pulsation signal under voltage fluctuation - Yanjie Zhao; Tonghe Zhang; Yongxing Song; Qiang Liu; Lin Liu; Ming Yu; Yi Ge (International Journal of Refrigeration, 2025)

Onboard measurements of organic vapor emissions from river vessels under various operational conditions - Mengxue Tong; Yanli Zhang; Mei Li; Qi Wang; Xiao Tian; Dan Zhang; Aoqi Ge; Wei Song; Xin Xiong; Yinong You; Yongjang Xu; Yihua Huang; et al. (Environmental Pollution, 2025)

Zr4+-doped PVA-based fiber films: Enhanced mechanical properties, degradability, and applications in green energy - Song Xue; Wenjing Qin; Changshun Gu; Mengyao Chen; Hanlin Zhai; Xiangchuan Zhao; Xinxin Li; Yanli Wang; Le Ge; Shengrong Li; Yixin Xu; Zeyu Ming; et al. (Chemical Engineering Journal, 2025)

Spatiotemporal distribution patterns of large and medium-sized mammals in a biodiversity hotspot: mplications for conservation - Wenqiang Hu; Xueyou Li; Kenneth Otieno Onditi; Hongjiao Wang; Wenyu Song; Zhechang Hu; Changzhe Pu; Mingjing Pu; Yun Xiong; Suhua Yang; Lin Zhu; Jianqiang Yin; et al. (Biological Conservation, 2025)

Dissecting the cell microenvironment of ovarian endometrioma through single-cell RNA sequencing - Jiangpeng Wu; Siyu Xia; Wenting Ye; Yan Sun; Jing Cai; Fubing Yu; Haiping Wen; Xiuwei Yi; Taikang Li; Mingwei Chen; Jiayun Chen; Ge Song; et al. (Science China Life Sciences, 2025)

Effect of different Hydrilla verticillata harvesting intensities on Vallisneria natans: Implications for restoring and managing submerged macrophytes - Xiaowen Lin; Xiaodong Wu; Daoya Liu; Xuguang Ge; Liang Chen; Zhenni Gao; Shixing Song; Chenxin Zhong; Zian Xiang (Plant and Soil, 2025)

Recovery of Coilia nasus resources after implementation of the 10-year fishing ban in the Yangtze River: implied from the Yangtze River Estuary and its adjacent sea areas - Shuyan Wang; Ying Xiong; Hushun Zhang; Dade Song; Yanping Wang; Hui Ge; Chengbin Zhang; Long Liang; Xiaming Zhong (Frontiers in Marine Science, 2024)
Introduction The implementation of the 10-year fishing ban in the Yangtze River has provided a crucial opportunity for the recovery of rare and endangered diadromous species, such as Coilia nasus . Methods In this study, we utilized electronic length–frequency analysis (ELEFAN) and length-based Bayesian biomass estimation (LBB) method to fit the body length data of C. nasus from the Yangtze River Estuary and its adjacent sea areas before and after the fishing ban (2019-2023), and the resource changes of C. nasus population were evaluated. Additionally, combined the catch production monitoring data from 2020 to 2022, we comprehensively analyzed the impact of the Yangtze River fishing ban on the recovery of C. nasus resources. Results The results showed that: (1) The proportion of quantity, weight and occurrence frequency of C. nasus in catches showed a significant increasing trend year by year. (2) 4,994 C. nasus were caught from 2021–2023, with body lengths ranging from 13–410 mm. In 2023, the average body length and weight of C. nasus had increased by 39.93% and 133.89%, respectively, from those in 2021. (3) ELEFAN estimated that the growth parameters after fishing ban, including asymptotic length, growth coefficient, and the theoretical age at length zero, were determined to be 42.92 cm, 0.43 year -1 , and -0.31 year, respectively. The total mortality rate, fishing mortality rate, and exploitation rate were determined to be 1.47 year -1 , 0.79 year -1 , and 0.54, respectively. (4) LBB estimated that the relative fishing mortality of C. nasus before the fishing ban increased from 1.22 in 2019 to 2.65 in 2020, while the relative biomass decreased from 0.34 to 0.22. After the fishing ban, the relative fishing mortality decreased from 0.85 in 2021 to 0.06 in 2023, and the relative biomass increased from 0.26 in 2021 to 0.90 in 2023, with a significant increase in 2022, indicating a clear recovery trend in C. nasus resources. Discussion By quantifying the resource characteristics of C. nasus before and after the 10-year fishing ban on the Yangtze River, this research revealed the impact of the ban and provided a reference for future systematic evaluations of the C. nasus population.

Does digital economy promote urban land green use efficiency? - Zhaoyang Cai; Ge Song; Weiming Li (Environment, Development and Sustainability, 2024)

Mesomycoplasma (Mycoplasma) ovipneumoniae dihydrolipoamide dehydrogenase is an immunogenic plasminogen binding protein and a putative adhesin - Jiazhen Ge; Tongtong Tian; Yijian Liu; Xuerui Li; Qianqian Li; Guodong Song; Pengcheng Gao; Fuying Zheng; Yuefeng Chu (Veterinary Microbiology, 2024)

Influence of energy-saving devices on the hydrodynamic characteristics of a waterjet-propelled ship: Experimental and numerical investigation - Kewei Song; Pei Xu; Jie Gong; Cong Sun; Shenwei Ge (Ocean Engineering, 2024)

Novel pretreatment technologies for sludge dewatering and dissolution: Humic acid combine with sodium percarbonate and different iron species - Denglong Lu; Shanshan Zhang; Yang Song; Huanying Ge; Zhaoguang Yang; Haipu Li (Journal of Water Process Engineering, 2024)

Association between pyrrolizidine alkaloids exposure and risk of abnormal serum indices—Insights from a descriptive cross-sectional study in Yunnan Province - Xiaoxiang Sun; Zhengyuan Xie; Zheng He; Yisheng He; Zigao Zhao; Xuerong Yan; Xiangjing Song; Zijie Chen; Tao Wang; Quanrui Yue; Yiming Chen; Hanfeng Ye; et al. (Journal of Hazardous Materials, 2024)

Ultrasonication as anaerobic digestion pretreatment to improve sewage sludge methane production: Performance and microbial characterization - Kai Zhao; Ge Song; Chaojie Lu; Jiaqi Wang; Ruiping Liu; Chengzhi Hu (Journal of Environmental Sciences, 2024)

Association of ambient temperature and diurnal temperature range with the outcome of in vitro fertilization in women from Hubei, China: A retrospective cohort study - Guan Cheng; Rui Qu; Ge Song; Xing Li; Feng Zhang; Jingxuan Wang; Wenzhu Li; Jiahui Wen; Yanfei Xiao; Yiqiu Wei; Weiqian Zhang; Xiaofang Yi; et al. (Environmental Research, 2024)

A novel and cost-effective biological denitrification associated with membrane process for treating pesticide wastewater: Excellent nitrogen removal effect and higher environment benefits - Shuya Zhuang; Dongxue Hu; Zhaobo Chen; Zhibo Liang; Junzhe Song; Hui Ge; Bei Jiang; Jian Dong; Fei Han; Jitao Yan; Yifan Wang; Shiming Cui (Desalination, 2024)

Unraveling MOF growth in colloids with controllable dual-doping through ultrafast sintering for wide temperature range LIBs - Bolin Zou; Semi Kim; Xingyu Zhang; Qiang Chang; Weiwei Ping; Daeun Jeong; Binghui Ge; Xingqi Liao; Zhimei Huang; Juyeong Kim; Xuyong Feng; Hongfa Xiang; et al. (Chemical Engineering Journal, 2024)

How to improve the sustainability of food security? A new perspective on competition in the spatial utilization of cultivated land between food crops and cash crops - Ge Song; Zhaoyang Cai (Stochastic Environmental Research and Risk Assessment, 2024)

Combination of magnetite and sodium percarbonate to enhance acetate-enriched short-chain fatty acids production during sludge anaerobic fermentation - Denglong Lu; Yang Song; Huanying Ge; Hongjia Peng; Haipu Li (Science of The Total Environment, 2024)

Temperature changes of the Mid-Late Holocene transition in North China and their implications for regional cultural succession - Jiheng Shi; Shude Ren; Manyue Li; Can-Ge Li; Lili Song; Qinghai Xu; Shengrui Zhang (Quaternary Science Reviews, 2024)

Highly efficient FeS/Fe3O4 @ biomass carbon bifunctional catalyst with enriched oxygen vacancies for heterogeneous electro-Fenton catalysis - Xuechun Wang; Chaohui Zhang; Ge Song; Jiana Jing; Shuaishuai Li; Minghua Zhou; Raf Dewil (Journal of Hazardous Materials, 2024)

Undrained triaxial tests of underconsolidated overlying sediments of hydrate deposits in the South China Sea - Lei Wang; Wenqi Yu; Yang Ge; Shi Shen; Zhaoran Wu; Yiming Zhu; Yongchen Song; Yanghui Li (Gas Science and Engineering, 2024)

The casein in sheep milk processed by cold plasma technology: Phosphorylation degree, functional properties, oxidation characteristics, and structure - Jiaying Zhang; Jiaqing Song; Shuangshuang Wang; Yangyu Su; Linlin Wang; Wupeng Ge (Food Chemistry, 2024)

Hypoxia induces reversible gill remodeling in largemouth bass (Micropterus salmoides) through integrins-mediated cell adhesion - Qiao Liu; Lipeng Guo; Hanwen Zhang; Jiayu Ge; Jie Luo; Kaige Song; Liulan Zhao; Song Yang (Fish & Shellfish Immunology, 2024)

Aquatic plants combined with microbial fuel cells promote sulfamethoxazole and sul genes removal from aquaculture pond sediments via bioelectrochemistry - Qiao Liu; Nisha Zhang; Jiayu Ge; Leji Zhang; Lipeng Guo; Hanwen Zhang; Kaige Song; Jie Luo; Liulan Zhao; Song Yang (Environmental Pollution, 2024)

The evaluation of Small River water pollution caused by tailing spill in the Northeast of China using high-resolution images - Yating Hu; Jingyu Liu; Yu Wang; Ge Liu; Kaishan Song; Shihong Wu; Liqiao Tian; Heng Lyu (Environmental Impact Assessment Review, 2024)

Identification and quantification of reactive species in aqueous medium during application of advanced oxidation processes: A critical review - Wenjing Li; Ge Song; Jiana Jing; Xueying Ren; Chaohui Zhang; Mehmet A. Oturan; Minghua Zhou (Chemical Engineering Journal, 2024)

Electrolyte-triggered in-situ polymerization of multi-site organic cathodes for superior-longevity cation-anion co-storage secondary batteries - Xinmei Song; Yang Ge; Xiaolan Xue; Xingkai Ma; Qianchuan Yu; Mengfei Zhu; Yaoda Wang; Junchuan Liang; Zuoxiu Tie; Jing Ma; Zhong Jin (Chemical Engineering Journal, 2024)

On the properties of lower mid-latitudes ionospheric scintillation observed over Chengdu, China - Shucan Ge; Hailong Li; Song Zhang; Mengyan Zhu; Jinghua Li; Bin Xu; Tong Xu; Shuji Sun; Lin Meng; Jian Wu (Advances in Space Research, 2024)

Leakage mechanisms of an operational underwater shield tunnel and countermeasures: A case study - Chenjie Gong; Mingjin Cheng; Yangyang Ge; Jianrong Song; Zhong Zhou (Tunnelling and Underground Space Technology, 2024)

Influence of soil N availability on priming effects depending on temperature - Jun Cui; Liang Wei; Zhenke Zhu; Yangwu Deng; Song Chen; Yakov Kuzyakov; Tida Ge (Soil and Tillage Research, 2024)

Iron mineral type controls organic matter stability and priming in paddy soil under anaerobic conditions - Shuang Wang; Wei Gao; Zhi Ma; Zhenke Zhu; Yu Luo; Liang Wei; Hongzhao Yuan; Song Chen; Chaoyun Ying; Kyle Mason-Jones; Yakov Kuzyakov; Tida Ge (Soil Biology and Biochemistry, 2024)

Prediction of As and Cd dissolution in various soils under flooding condition - Jingwen Ge; Song Wu; Haotian Wu; Jianyu Lin; Yijun Cai; Dongmei Zhou; Xueyuan Gu (Science of The Total Environment, 2024)

Nanoplastics composite norfloxacin induced changes in conformation and function of lysozyme and differential effects of co-exposure contamination - Hengyu Song; Pin Jiang; Houquan Tang; Zaifeng Wang; Xuan Ge; Xiangxiang Li; Falin He; Shuqi Guo; Guang Tian; Yuntao Qi; Shaoyang Hu; Rutao Liu (Science of The Total Environment, 2024)

Synergy of atomic hydrogen reduction and reactive oxygen species oxidation over confined Mn bifunctional site for electrocatalytic deep mineralization - Pei Su; Xifeng Lu; Ge Song; Qingrui Zhang; Qiuxia Leng; Minghua Zhou (Journal of Hazardous Materials, 2024)

How does coal mining affect land use in townships? A perspective of land use transition - Zhiyuan Song; Xianming Yang; Haiping Zhang; Ziyi Gao; Yuejing Ge (Journal of Cleaner Production, 2024)

Provincial equity and enhanced health are key drivers for China's 2060 carbon neutrality - Jiaxin Dong; Siwei Li; Yisheng Sun; Weishu Gong; Ge Song; Yu Ding; Jie Yang; Mengfan Teng; Ruilin Wang; Jia Xing; Yang Ou; Wei Gong (Journal of Cleaner Production, 2024)

Facilitate nitrogen fixation photoreaction over decorated composited dots on the (001) facet exposed anatase titanium dioxide nanosheets - Huaiwei Zhang; Liang Bao; Qingwei Zhou; Ge Song (Journal of Environmental Chemical Engineering, 2024)

Structure, physicochemical and adsorption properties of insoluble dietary fiber from Lycium barbarum residue: A potential functional factor - Haixuan Sun; Weiben Ge; Deao Song; Yubing Li; Yu Wang; Hongxin Wang (Food Bioscience, 2024)

Successful subduction of oceanic plate after failed attempts in the Late Archean: Petrological and geochemical constraints - Xi Wang; Rong-Feng Ge; Yong-Fei Zheng; Wen-Bin Zhu; San-Zhong Li; Rong-Song Tian; Yue Wang; Yi-Wei Rong (Earth and Planetary Science Letters, 2024)

Superior microplastic removal and gravity-driven membrane filtration optimization: The role of octadecyl-quaternium hybrid coagulant and molecular dynamics insights - Meng Chen; Jun Nan; Langrun Song; Wenxing Jin; Shutong Chen; Zhencheng Ge; Fangmin Wu; Xuesong Ye (Chemical Engineering Journal, 2024)

Deubiquitinating enzyme USP28 inhibitor AZ1 alone and in combination with cisplatin for the treatment of non-small cell lung cancer - Yiqiong Song; Longhao Wang; Yuanyuan Zheng; Lanqi Jia; Chunwei Li; Ke Chao; Lifeng Li; Shilong Sun; Yujie Wei; Yahao Ge; Yaqi Yang; Lili Zhu; et al. (Apoptosis, 2024)

Cyanobacterial blooms in Lake Taihu: Temporal trends and potential drivers - Ting Song; Hujun Zhang; Yanjuan Xu; Ximing Dai; Fan Fan; Yu Wang; Ge Liu (Science of The Total Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Preliminary assessments of carbon release driven by Late Pleistocene Arctic ice sheets - Liming Ye; Xiaoguo Yu; Yeping Bian; Weijia Fan; Zhongqiang Ji; Sai Song; Ziyin Wu; Qian Ge; Dong Xu; Weiyan Zhang; Haiyan Jin; Xiaohu Li; et al. (Quaternary Science Reviews, 2024)

Investigation of oxygen packaging to maintain beef color stability and microbiology safety after periods of long-term superchilled storage - Jun Yang; Xue Chen; Xinxin Duan; Ke Li; Haijian Cheng; Ge Sun; Xin Luo; David L. Hopkins; Benjamin W.B. Holman; Yimin Zhang; Enliang Song (Meat Science, 2024)

Selenium alleviates chromium stress and promotes chromium uptake in As-hyperaccumulator Pteris vittata: Cr reduction and cellar distribution - Qian-Yu Zhou; Wei Li; Si-Xue He; Song-Ge Deng; Shu-Fen Xiao; Chen-Jing Liu; Lena Q. Ma (Journal of Hazardous Materials, 2024)

Foliar-selenium enhances plant growth and arsenic accumulation in As-hyperaccumulator Pteris vittata: Critical roles of GSH-GSSG cycle and arsenite antiporters PvACR3 - Wei Li; Si-Xue He; Qian-Yu Zhou; Zhi-Hua Dai; Chen-Jing Liu; Shu-Fen Xiao; Song-Ge Deng; Lena Q. Ma (Journal of Hazardous Materials, 2024)

In situ U–Pb dating of garnet, vesuvianite, and scheelite from the Nanyangtian tungsten deposit reveals an Early Cretaceous W mineralization event in Southeast Yunnan, China - Xiao-Yu Zhao; Ming-Guo Deng; Wen-Chang Li; Yan-Wen Tang; Ding-Cai Zhang; Sheng-Kang Han; Wen-Bo Song; Qing-Ge Zhang; Jing-Wei Xu (Gondwana Research, 2024)

CircZFR promotes colorectal cancer progression via stabilizing BCLAF1 and regulating the miR-3127-5p/RTKN2 axis - Jiaxin Chen; Huijuan Wang; Jianbin Xu; Engeng Chen; Qing Meng; Jiawei Wang; Haoyi Xiang; Wei Zhou; Ge Shan; Zhenyu Ju; Zhangfa Song (Science China Life Sciences, 2024)

Evaluation of fengyun geosynchronous orbit and GPM satellites precipitation products over the southeastern Tibetan plateau - Yunfan Song; Tao Du; Bo Zeng; Qing Wu; Ge Wang (International Journal of Remote Sensing, 2024)

Influence of earthquake duration on structural collapse capacity: Application to self-centering shear walls - Ge Song; Lili Xing (Soil Dynamics and Earthquake Engineering, 2024)

Regulating the electronic structure by P-doping cobalt-based catalyst for atomic hydrogen mediated electrocatalytic dechlorination - Ge Song; Huizhong Wu; Xuechun Wang; Shuaishuai Li; Ruiheng Liang; Minghua Zhou (Journal of Hazardous Materials, 2024)

Comprehensive source identification of heavy metals in atmospheric particulate matter in a megacity: A case study of Hangzhou - Feili Li; Gaoxiang Zhang; Yifei Jinxu; Tianzheng Ding; Cong-Qiang Liu; Yunchao Lang; Nuohang Liu; Shuang Song; Yasheng Shi; Baozhu Ge (Journal of Environmental Management, 2024)

The chitinase genes TuCht4 and TuCht10 are indispensable for molting and survival of Tetranychus urticae - Ming Liu; Rongchumu Ge; Lihong Song; Yan Chen; Shuo Yan; Chunya Bu (Insect Biochemistry and Molecular Biology, 2024)

Metals/bisulfite system involved generation of 24-sulfonic-25-ene ginsenoside Rg1, a potential quality control marker for sulfur-fumigated ginseng - Hui Liu; Xiao-Qian Wu; Xiang-Ling Qin; Jin-Hao Zhu; Jin-Di Xu; Shan-Shan Zhou; Ming Kong; Hong Shen; Jie-Ge Huo; Song-Lin Li; He Zhu (Food Chemistry, 2024)

Labile organic carbon fractions in the rhizosphere contribute to nitrogen and phosphorus uptake in rice under long-term crop rotations and nitrogen application - Mengjia Wang; Xiangqian Feng; Ziyu Zhou; Hengyu Ma; Tida Ge; Caixian Tang; Danying Wang; Song Chen (Applied Soil Ecology, 2024)

The superiority of hydrophilic polyurethane in comammox-dominant ammonia oxidation during low-strength wastewater treatment - Yunlong Li; Zimin Chai; Chao Song; Jin Chen; Ailu Gu; Guangli Mu; Ruxin Ge; Maosheng Zheng (Science of The Total Environment, 2024)

Activated carbon as a strong DOM adsorbent mitigates antimony and arsenic release in flooded mining-impacted soils - Enze Zhang; Song Wu; Jinsong Liu; Hongbo Li; Xiantang Liu; Yilin Lu; Chenghao Ge; Dongmei Zhou (Journal of Hazardous Materials, 2024)

Reduction of selenite to selenium nanoparticles by highly selenite-tolerant bacteria isolated from seleniferous soil - Meng Ge; Shaofeng Zhou; Daobo Li; Da Song; Shan Yang; Meiying Xu (Journal of Hazardous Materials, 2024)

Cu-MOF-derived Cu nanoparticles decorated porous N-doped biochar for low-temperature H2S desulfurization - Lingwen Song; Yi Yuan; Yuan Wang; Tian C. Zhang; Ge He; Shaojun Yuan (Fuel, 2024)

Influence of seismic duration on performance assessment: application to self-centering concrete frames - Ge Song; Anqi Gu (Bulletin of Earthquake Engineering, 2024)

Revealing the heterogeneity of periodic visiting patterns across different ages and spaces using a flexible detection method: A case study of Beijing - Zidong Fang; Tao Pei; Ci Song; Xiaorui Yan; Le Liu; Sihui Guo; Yaxi Liu; Yong Peng; Dasheng Ge; Jie Chen (Applied Geography, 2024)

Variations in surface area and biogeochemistry of subarctic-arctic lakes established through satellite and in-situ observations: An overview of published research from the past 30 years - Ruixue Zhao; Yingxin Shang; Pierre-André Jacinthe; Sijia Li; Ge Liu; Zhidan Wen; Zijin Wang; Qian Yang; Chong Fang; Kaishan Song (Science of The Total Environment, 2024)

Natural air diffusion electrode modified with metal-organic frameworks derived Fe doped porous carbon for sulfamethazine degradation by heterogeneous electro-Fenton - Xuyang Zhang; Xiuwu Zhang; Ge Song; Ruiheng Liang; Minghua Zhou (Journal of Environmental Chemical Engineering, 2024)

Quality improvement of soybean meal by simultaneous microbial fermentation and enzymolysis and untargeted metabolomic analysis of its metabolites - Hongye Shen; Yongxu Li; Hao Song; Jie Bai; Nan Peng; Xiangyang Ge; Shumiao Zhao (Food Bioscience, 2024)

Integrating untargeted and pseudotargeted metabolomics and network analysis reveals the interventional effects of red yeast rice on rat serum metabolites - Ge Xun; Yingxuan Li; Yifan Zhang; Song Li; Yanhua Gao; Yujuan Chen; Ding Zhang; Hongyang Ni; Fangfang Liu; Yan Fu; Xu Wang; Qiao Wang (Food Bioscience, 2024)

Spatial-temporal-controlled NO gas and PARP1 siRNA delivery for alleviating the dilemma of deeper sonodynamic therapy in pancreatic cancer - Qingshuang Tang; Yuan Wang; Ruiqi Wu; Zexing Yu; Xue Shi; Yang Song; Lulu Zhang; Xin Li; Jinxia Zhang; Suhui Sun; Xiaotu Ma; Shuyu Xu; et al. (Chemical Engineering Journal, 2024)

Delaying crystallization and anchoring the grain boundaries defects via π-π stacked molecules for efficient and stable wide-bandgap perovskite solar cells - Jinliang Shen; Na Li; Yuhang Wang; Xiang Ge; Junlei Tao; Song Yin; Xingkun Ning; Tingwei He; Guangsheng Fu; Shaopeng Yang (Chemical Engineering Journal, 2024)

Intelligent multi-severity nuclear accident identification under transferable operation conditions - Song Xu; Yuantao Yao; Nuo Yong; Dongqin Xia; Daochuan Ge; Jie Yu (Annals of Nuclear Energy, 2024)

Utilizing fMRI to Guide TMS Targets: the Reliability and Sensitivity of fMRI Metrics at 3 T and 1.5 T - Qiu Ge; Matthew Lock; Xue Yang; Yuejiao Ding; Juan Yue; Na Zhao; Yun-Song Hu; Yong Zhang; Minliang Yao; Yu-Feng Zang (Neuroinformatics, 2024)

A Shape-Aware Network for Arctic Lead Detection from Sentinel-1 SAR Images - Wei Song; Min Zhu; Mengying Ge; Bin Liu (Journal of Marine Science and Engineering, 2024)
Accurate detection of sea ice leads is essential for safe navigation in polar regions. In this paper, a shape-aware (SA) network, SA-DeepLabv3+, is proposed for automatic lead detection from synthetic aperture radar (SAR) images. Considering the fact that training data are limited in the task of lead detection, we construct a dataset fusing dual-polarized (HH, HV) SAR images from the C-band Sentinel-1 satellite. Taking the DeepLabv3+ as the baseline network, we introduce a shape-aware module (SAM) to combine multi-scale semantic features and shape information and, therefore, better capture the shape characteristics of leads. A squeeze-and-excitation channel-position attention module (SECPAM) is designed to enhance lead feature extraction. Segmentation loss generated by the segmentation network and shape loss generated by the shape-aware stream are combined to optimize the network during training. Postprocessing is performed to filter out segmentation errors based on the aspect ratio of leads. Experimental results show that the proposed method outperforms the existing benchmarking deep learning methods, reaching 96.82% for overall accuracy, 93.01% for F1-score, and 91.48% for mIoU. It is also found that the fusion of dual-polarimetric SAR channels as the input could effectively improve the accuracy of sea ice lead detection.

How does exotic Spartina alterniflora affect the contribution of iron-bound organic carbon to soil organic carbon in salt marshes? - Weixiang Chen; Weiting Zhang; Ying Qiu; Zihao Shu; Jin-e Liu; Xinhou Zhang; Khan Waqas; Ge Song (Science of The Total Environment, 2024)

Using satellite imagery to estimate CO2 partial pressure and exchange with the atmosphere in the Songhua River - Chunlan Xiong; Hui Tao; Shiwei Liu; Ge Liu; Zhidan Wen; Yingxin Shang; Qiang Wang; Chong Fang; Sijia Li; Kaishan Song (Journal of Hydrology, 2024)

Green environmental protection and sustainable utilization of straw: Investigation for molecular dynamics of highland barley straw fiber to enhancing road performance of asphalt - Tengfei Nian; Piyi Li; Jinguo Ge; Jiaqi Song; Maomin Wang (Journal of Cleaner Production, 2024)

Ecological responses and functional significance of paddy crust in the southern Chinese environment - Xiaolin Kuang; Yiyi Hu; Shaoning Chen; Yili Ge; Yiling Hu; Huijuan Song; Ke Song; Liang Peng (Environmental Pollution, 2024)

A critical review on regulating multi-electron pathways of oxygen reduction reaction on modified carbon-catalysts for organic wastewater treatment - Xifeng Lu; Pei Su; Ge Song; Minghua Zhou (Chemical Engineering Journal, 2024)

Exploring the release mechanism of micro/nanoplastics from different layers of masks in water: towards reduction of plastic contamination in masks - Wei Ge; Hao Liang; Ping Gao; Yan Li; Ningning Song; Juan Wu; Chao Chai (Environmental Science and Pollution Research, 2024)

Rice seed classification by hyperspectral imaging system: A real-world dataset and a credible algorithm - Yufei Ge; Shaozhong Song; Shuang Yu; Xiaoli Zhang; Xiongfei Li (Computers and Electronics in Agriculture, 2024)

The association between artificial light at night and gestational diabetes mellitus: A prospective cohort study from China - Junhao Liao; Chuan Yu; Jiarui Cai; Run Tian; Xingyue Li; Hong Wang; Lin Li; Guishuang Song; Leyao Fu; Xinxi Li; Qiaoyue Ge; Ling Zhang; et al. (Science of The Total Environment, 2024)

Atom-by-atom optimizing the surface termination of Fe-Pt intermetallic catalysts for alkaline hydrogen evolution reaction - Qing Liang; Fanling Meng; Wenwen Li; Xu Zou; Kexin Song; Xin Ge; Zhou Jiang; Yuhua Liu; Meiqi Liu; Zhenyu Li; Taowen Dong; Zhongjun Chen; et al. (Science Bulletin, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Global wild rice germplasm resources conservation alliance: World Wild-Rice Wiring - Xiaoming Zheng; Disna Ratnasekera; Jiayu Fan; Robert J. Henry; Beng-Kah Song; Kenneth M. Olsen; Bal Krishna Joshi; Maria Celeste N. Banaticla-Hilario; Tonapha Pusadee; Adane Getachew Melaku; Yêyinou Laura Estelle Loko; Koukham Vilayheuang; et al. (Molecular Plant, 2024)

Generation estimation and critical metals quantity assessment of retired mobile phones in Japan - Ang Li; Bo Li; Ge Yang; Kronnaphat Khumvongsa; Jingjin Pan; Xiaolong Song; Xuyang Lei; Suxia Hou; Dong Yang; Bin Lu (Journal of Cleaner Production, 2024)

The electro-Fenton/sulfite process with Fe-Mn bimetallic catalyst for diclofenac degradation at neutral pH - Ge Song; Yang Zheng; Minghua Zhou (Journal of Environmental Chemical Engineering, 2024)

Host-guest synergistic hydrogen bond triggered signal amplification for visualizing the plant hormone salicylic acid - A-Ling Tang; Li-Long Zhang; Shuai Tan; Ping Yang; Wei Niu; Mei-Hong Ge; Lin-Lin Yang; Pei-Yi Wang; Li-Wei Liu; Xiang Zhou; Song Yang (Chemical Engineering Journal, 2024)

Understanding the thermal activation behavior of montmorillonite and kaolinite at atomic level by ReaxFF molecular dynamics simulations - Wei Ge; Hengheng Mao; Jun Chen; Fanfei Min; Hui Liu; Shaoxian Song (Applied Clay Science, 2024)

Ecological performance of an integrated ex-situ rice-fish co-culture system - Qiao Liu; Leji Zhang; Yi Yang; Jiacen Zou; Yipeng Yang; Jiayu Ge; Haoxiao Yan; Kuo He; Changjun Yang; Rabia Tahir; Liulan Zhao; Song Yang (Aquaculture, 2024)

Spatial variations of DOM in a diverse range of lakes across various frozen ground zones in China: Insights into molecular composition - Zhidan Wen; Jiarui Han; Yingxin Shang; Hui Tao; Chong Fang; Lili Lyu; Sijia Li; Junbin Hou; Ge Liu; Kaishan Song (Water Research, 2024)

Metamodel-based sensitivity analysis of the optimal outrigger locations for damping outrigger-ATMD systems - Lili Xing; Ge Song; Ying Zhou; Peng Zhang (Soil Dynamics and Earthquake Engineering, 2024)

Performance assessment for self-centering systems considering ground motion duration: Part 1 – Evaluation of structural behaviors and damage development - Ge Song; Ying Zhou (Soil Dynamics and Earthquake Engineering, 2024)

Performance assessment for self-centering systems considering ground motion duration: Part 2 – Evaluation of structural collapse capacity - Ge Song; Ying Zhou (Soil Dynamics and Earthquake Engineering, 2024)

Abrupt diatom assemblage shifts in Lake Baiyangdian driven by distinct hydrological changes and yet more so by gradual eutrophication - Xin Mao; Linjing Liu; Hongmei Zhao; Yawen Ge; Gaolei Jiang; Lei Song; Kai Ning; Hua Zhao; Peng Zhang (Limnologica, 2024)

Preparation of lanthanum-modified bentonite and its combination with oxidant and coagulant for phosphorus and algae removal - Ge Han; Shenshen Cui; Zheng Fu; Xinshan Song; Xiaohua Chen; Yuhui Wang (Journal of Water Process Engineering, 2024)

Natural and anthropogenic dissolved organic matter in landfill leachate: Composition, transformation, and their coexistence characteristics - Jing Zheng; Xian-Ge Wang; Yue Sun; Yu-Xin Wang; Hao-Qun Sha; Xiao-Song He; Xiao-Jie Sun (Journal of Hazardous Materials, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Composition and Distribution of Microeukaryotic Communities in the Surface Sediments of Five Geographic Regions of Bohai Sea Based on 18S rDNA Amplicon Sequencing - Wenquan Zhang; Huameng Ge; Chengbing Song; Chengcheng Li; Shenghao Liu (Journal of Marine Science and Engineering, 2024)
The Bohai Sea is a semi-enclosed shallow water that is influenced by both natural and anthropogenic stressors. However, the microeukaryotic communities and environmental factors that affect them in different regions remain largely unclear. We investigated microeukaryotic communities in surface sediments from five geographic regions using high-throughput sequencing of the 18S rDNA gene. The Miaodao Archipelago, Yellow River Estuary, and Central Bohai Sea had the highest Shannon and Simpson indices of the eukaryotic communities, while the Yellow River Estuary exhibited the highest Chao1 index. The microeukaryotic communities in surface sediments were mainly composed of Dinoflagellata, Bacillariophyta, Ciliophora, Cercozoa, and Protalveolata. Thalassiosira has a relatively high abundance at the Liaodong Bay and Central Bohai Sea, possessing the proportion of 41.70% and 38.10%, respectively, while Gonyaulax was the most abundant taxa in the Bohai Bay, occupying a proportion of 57.77%. Moreover, a negative correlation between diatoms and dinoflagellates was observed. Phosphorus, nitrogen, salinity, temperature, and silicate were major environmental determinants of microeukaryotic composition. Microeukaryotic communities in the surface sediments, especially for the composition and ratio of diatoms to dinoflagellates, reflected the environmental quality of marine ecosystems. Overall, these microeukaryotic community compositions provide a reliable indicator for monitoring the level of marine eutrophication in the Bohai Sea.

Degradation of atrazine by electro-peroxone enhanced by Fe and N co-doped carbon nanotubes with simultaneous catalysis of H2O2 and O3 - Jinyu Gu; Shasha Li; Jinxin Xie; Ge Song; Minghua Zhou (Chemosphere, 2024)

Enzyme-enhanced acidogenic fermentation of waste activated sludge: Insights from sludge structure, interfaces, and functional microflora - Ge Song; Shunan Zhao; Jiaqi Wang; Kai Zhao; Jing Zhao; He Liang; Ruiping Liu; Yu-You Li; Chengzhi Hu; Jiuhui Qu (Water Research, 2024)

Flow-through electrode system (FES): An effective approach for biofouling control of reverse osmosis membranes for municipal wastewater reclamation - Hao-Bin Wang; Yin-Hu Wu; Yi-Ge Sun; Yu-Qing Xu; Zhuo Chen; Song Xue; Zhuo-Wei Zhang; Nozomu Ikuno; Nakata Koji; Hong-Ying Hu (Water Research, 2024)

Anaerobic granular sludge performance in an expanded granular sludge bed reactor treating calcium-rich wastewater by adjusting CaCO3 crystallization: Effect of upflow velocity and Ca2+ concentration - Xiaoji Liu; Dongning Pan; Quan Yuan; Xiyuan Feng; Meixuan Li; Xuening Song; Meiling Li; Yajuan Ge; Yukun Xing; Yuanzhou Yu; Zhengyu Jin (Science of The Total Environment, 2024)

Retrieving hourly seamless PM2.5 concentration across China with physically informed spatiotemporal connection - Yu Ding; Siwei Li; Jia Xing; Xi Li; Xin Ma; Ge Song; Mengfan Teng; Jie Yang; Jiaxin Dong; Shiyao Meng (Remote Sensing of Environment, 2024)

Uptake, accumulation and toxicity of short chain chlorinated paraffins to wheat (Triticum aestivum L.) - Jianzhong Yu; Qing Tang; Ge Yin; Weifang Chen; Jitao Lv; Lingxiangyu Li; Chenghao Zhang; Yunxiang Ye; Xijiao Song; Xueping Zhao; Tao Tang; Changpeng Zhang; et al. (Journal of Hazardous Materials, 2024)

Extraction of eutrophic and green ponds from segmentation of high-resolution imagery based on the EAF-Unet algorithm - Yating Hu; Danyang Zheng; Shuqiong Shi; Yu Wang; Ge Liu; Kaishan Song; Dehua Mao; Shihong Wu; Liqiao Tian (Environmental Pollution, 2024)

Effects of land conversion to cropland on soil organic carbon in montane soils of Northeast China from 1985 to 2020 - Xiang Wang; Kaishan Song; Zongming Wang; Sijia Li; Yingxin Shang; Ge Liu (CATENA, 2024)

A dynamic harmonic regression approach to estimating groundwater evapotranspiration based on diurnal groundwater-level fluctuations - Jinting Huang; Jiawei Wang; Yangxiao Zhou; Tuo Fang; Bohan Ning; Ge Song; Tian Huang; Linghua Li; Zhan Yang; Qiu lv; Fang Pu; Zongze Li; et al. (Hydrogeology Journal, 2024)

Morphological and phylogenetic analyses reveal a new species of Anthracophyllum (Omphalotaceae, Agaricales) in Zhejiang Province, China - Wen-Juan Yang; Miao Xu; Jing Zhang; Fan Zhou; Zhi-Fang Le; Wen-Jun Tong; Hai-Yan Song; Zhuo-Han Jin; Qiu-Ge Cheng; Jian-Ping Zhou; Yang Gao; Zhi-Jun Zhai; et al. (Archives of Microbiology, 2024)

Soil microbial diversity and network complexity drive the ecosystem multifunctionality of temperate grasslands under changing precipitation - Changchun Zhai; Lili Han; Chao Xiong; Anhui Ge; Xiaojing Yue; Ying Li; Zhenxing Zhou; Jiayin Feng; Jingyi Ru; Jian Song; Lin Jiang; Yunfeng Yang; et al. (Science of The Total Environment, 2024)

Performance and mechanism of chromium reduction in denitrification biofilm system with different carbon sources - Ge Cao; Junzhi Gao; Jinxin Song; Xvlong Jia; Yinuo Liu; Jiaojiao Niu; Xin Yuan; Yingxin Zhao (Science of The Total Environment, 2024)

Temporal variations in reactive oxygen species in biofilms of submerged macrophytes: The key role of microbial metabolism mediated by oxygen fluctuations - Zuhan Ge; Zihang Ma; Wenjie Hong; Kexuan Liu; Shuwen Yan; Weihua Song; Jibiao Zhang (Journal of Hazardous Materials, 2024)

Advances and perspectives towards spent LiFePO4 battery recycling - Yunlong Xu; Baichao Zhang; Zhaofei Ge; Shu Zhang; Bai Song; Ye Tian; Wentao Deng; Guoqiang Zou; Hongshuai Hou; Xiaobo Ji (Journal of Cleaner Production, 2024)

Multi-scale structural changes and mechanistic analysis of wheat starch gels with common proteins in short-term retrogradation at low temperature - Jie Bai; Leshan Zhang; Xin Jia; Qiuyu Ye; Jiawen Pei; Qi Song; Junlin Ge; Xuebo Liu; Xiang Duan (Food Hydrocolloids, 2024)

A novel chlorophyll-a retrieval model based on suspended particulate matter classification and different machine learning - Chong Fang; Changchun Song; Zhidan Wen; Ge Liu; Xiaodi Wang; Sijia Li; Yingxin Shang; Hui Tao; Lili Lyu; Kaishan Song (Environmental Research, 2024)

Electrochemical advanced oxidation processes towards carbon neutral wastewater treatment: A review - Wenjing Li; Ge Song; Jiangli Sun; Minghua Zhou (Chemical Engineering Journal, 2024)

Low temperature relaxor, polarization dynamics and energy storage properties of Ca0.28Ba0.72Nb2O6 tungsten bronze ceramics - Lei Cao; Yuanyuan Wang; Ying Yuan; Jianguo Zhu; Hadi Barzegar Bafrooei; Minmin Mao; Bing Liu; Hao Li; Dawei Wang; Zhilun Lu; Ge Wang; Kaixin Song (Chemical Engineering Journal, 2024)

Anti-stokes fluorescence of phycobilisome and its complex with the orange carotenoid protein - Dmitry V. Zlenko; Elena A. Protasova; Georgy V. Tsoraev; Nikolai N. Sluchanko; Dmitry A. Cherepanov; Thomas Friedrich; Baosheng Ge; Song Qin; Eugene G. Maksimov; Andrew B. Rubin (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

White rice consumption and risk of cardiometabolic and cancer outcomes: A systematic review and dose-response meta-analysis of prospective cohort studies - Honghao Lai; Mingyao Sun; Yafei Liu; Hongfei Zhu; Mengting Li; Bei Pan; Qi Wang; Qiuyu Yang; Xiao Cao; Chen Tian; Yao Lu; Xuping Song; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Evaluation of metal pollution characteristics using water and moss in the Luanchuan molybdenum mining area, China - Xiangyi Song; Shilong He; Ruogu Li; Zhen Mao; Sijie Ge; Xiangyu Bai; Chuning Ji (Environmental Science and Pollution Research, 2023)

Construction of floatable flower-like plasmonic Bi/BiOCl-loaded hollow kapok fiber photocatalyst for efficient degradation of RhB and antibiotics - Yankai Song; Anchun Long; Xianlong Ge; Zongqi Bao; Minfeng Meng; Shaohua Hu; Yingying Gu (Chemosphere, 2023)

Luteolin inhibits angiogenesis and enhances radiotherapy sensitivity of laryngeal cancer via downregulating Integrin β1 - Zhen Li; Hongzhou Ge; Yonggang Xie; Yueqin Zhang; Xiaoyan Zhao; Wen Sun; Meiyan Song (Tissue and Cell, 2023)

Primary sources of HONO vary during the daytime: Insights based on a field campaign - Dongyang Chen; Li Zhou; Song Liu; Chaofan Lian; Weigang Wang; Hefan Liu; Chunyuan Li; Yuelin Liu; Lan Luo; Kuang Xiao; Yong Chen; Yang Qiu; et al. (Science of The Total Environment, 2023)

Techno-economic analysis of municipal sludge co-combustion power generation with different fuels - Zhimin Liu; Dongnian Yin; Huijun Ge; Gang Zhou; Tao Song (Journal of Environmental Chemical Engineering, 2023)

Coupling effects of heating pelleting and torrefaction on black pellets production from microalga Nannochloropsis Oceanica residues - Yidong Jiang; Gang Zhou; Haifeng Zhang; Jianzheng Xu; Huijun Ge; Laihong Shen; Tao Song (Fuel, 2023)

Direct recovery of degraded LiFePO4 cathode via mild chemical relithiation strategy - Yunlong Xu; Baichao Zhang; Zhaofei Ge; Haoji Wang; Ningyun Hong; Xiangting Xiao; Bai Song; Yangyang Zhang; Ye Tian; Wentao Deng; Guoqiang Zou; Hongshuai Hou; et al. (Chemical Engineering Journal, 2023)

Evolution characteristics of the rainstorm disaster chains in the Guangdong–Hong Kong–Macao Greater Bay Area, China - Yujie Wang; Ge Gao; Jianqing Zhai; Qiufeng Liu; Lianchun Song (Natural Hazards, 2023)

Correction to: The Domestic Isolation of Terbinafine- and Itraconazole Resistant Trichophyton indotineae in Chinese Mainland - Xue Kong; Ge Song; Huan Mei; Hailin Zheng; Chao Tang; Sybren de Hoog; Xiaofang Li; Xiaodong She; Weida Liu; Guanzhao Liang (Mycopathologia, 2023)

In vitro combination with doxycycline plus antifungals against clinical Mucorales pathogens - Meijie Zhang; Ge Song; Hailin Zheng; Balaji Pathakumari; Weida Liu; Guanzhao Liang (Brazilian Journal of Microbiology, 2023)

Remote estimation of phycocyanin concentration in inland waters based on optical classification - Lili Lyu; Kaishan Song; Zhidan Wen; Ge Liu; Chong Fang; Yingxin Shang; Sijia Li; Hui Tao; Xiang Wang; Yong Li; Xiangyu Wang (Science of The Total Environment, 2023)

Thermal imaging: The digital eye facilitates high-throughput phenotyping traits of plant growth and stress responses - Ting Wen; Jian-Hong Li; Qi Wang; Yang-Yang Gao; Ge-Fei Hao; Bao-An Song (Science of The Total Environment, 2023)

Ship energy-saving device: Influence of the scale effect and hull roughness on the resistance reduction effect of an interceptor - Kewei Song; Jie Gong; Shenwei Ge; Cong Sun; Haiyan Yang; Weiping Zhang (Ocean Engineering, 2023)

Camel milk peptides alleviate hyperglycemia by regulating gut microbiota and metabolites in type 2 diabetic mice - Yongjin Zhang; Ju Wang; Wupeng Ge; Yuxuan Song; Rui He; Zhi Wang; Lili Zhao (Food Research International, 2023)

Quorum sensing in different subcommunities becomes the key factor affecting the humification of the aerobic composting system with sauerkraut fermentation wastewater - Jiaxin Liu; Song Gang; Xu Wang; Shanshan Sun; Jie Kang; Jingping Ge (Bioresource Technology, 2023)

Temporal-spatial Generation of Astrocytes in the Developing Diencephalon - Wentong Hong; Pifang Gong; Xinjie Pan; Zhonggan Ren; Yitong Liu; Guibo Qi; Jun-Liszt Li; Wenzhi Sun; Woo-Ping Ge; Chun-Li Zhang; Shumin Duan; Song Qin (Neuroscience Bulletin, 2023)
Astrocytes are the largest glial population in the mammalian brain. However, we have a minimal understanding of astrocyte development, especially fate specification in different regions of the brain. Through lineage tracing of the progenitors of the third ventricle (3V) wall via in-utero electroporation in the embryonic mouse brain, we show the fate specification and migration pattern of astrocytes derived from radial glia along the 3V wall. Unexpectedly, radial glia located in different regions along the 3V wall of the diencephalon produce distinct cell types: radial glia in the upper region produce astrocytes and those in the lower region produce neurons in the diencephalon. With genetic fate mapping analysis, we reveal that the first population of astrocytes appears along the zona incerta in the diencephalon. Astrogenesis occurs at an early time point in the dorsal region relative to that in the ventral region of the developing diencephalon. With transcriptomic analysis of the region-specific 3V wall and lateral ventricle (LV) wall, we identified cohorts of differentially-expressed genes in the dorsal 3V wall compared to the ventral 3V wall and LV wall that may regulate astrogenesis in the dorsal diencephalon. Together, these results demonstrate that the generation of astrocytes shows a spatiotemporal pattern in the developing mouse diencephalon.

Scale-dependent and driving relationships between spatial features and carbon storage and sequestration in an urban park of Zhengzhou, China - Xiaoli Jia; Haiting Han; Yuan Feng; Peihao Song; Ruizhen He; Yang Liu; Peng Wang; Kaihua Zhang; Chenyu Du; Shidong Ge; Guohang Tian (Science of The Total Environment, 2023)

Sustainable poverty reduction models for the coordinated development of the social economy and environment in China - Yong Ge; Shan Hu; Yongze Song; Hua Zheng; Yansui Liu; Xinyue Ye; Ting Ma; Mengxiao Liu; Chenghu Zhou (Science Bulletin, 2023)

Copper enhanced arsenic-accumulation in As-hyperaccumulator Pteris vittata by upregulating its gene expression for As uptake, translocation, and sequestration - Chen-Jing Liu; You-Jing Peng; Chun-Yan Hu; Si-Xue He; Shu-Fen Xiao; Wei Li; Song-Ge Deng; Zhi-Hua Dai; Lena Q. Ma (Journal of Hazardous Materials, 2023)

Role of garbage classification in air pollution improvement of a municipal solid waste disposal base - Song Gao; Lingning Meng; Xiang Ge; Yuewu Li; Yong Yang; Yusen Duan; Qingyan Fu; Shuwei Zhang; Xuechun Yang; Weiliang Fei; Zheng Jiao (Journal of Cleaner Production, 2023)

Comprehensive investigation of milk oligosaccharides in different mammalian species and the effect of breed and lactation period on sheep milk oligosaccharides - Haiyan Wang; Minghui Zhang; Yucui Huo; Xiuxiu Cui; Rui He; Bei Han; Zhongfu Wang; Yuxuan Song; Xin Lv; Jing Zhang; Wupeng Ge (Food Research International, 2023)

Impacts of an extreme Changjiang flood on variations in carbon cycle components in the Changjiang Estuary and adjacent East China sea - Shuzhen Song; Richard Bellerby; Jing Liu; Wenyun Guo; PeiSong Yu; Jianzhong Ge; Daoji Li (Continental Shelf Research, 2023)

Multi-scale domain and microstructure engineering for the high-energy-storage BCZT based lead-free relaxor ferroelectric ceramics - Jiayue Song; Fei Yan; Jinfeng Lin; Guanglong Ge; Cheng Shi; Jin Qian; Yali Hao; Yongqi Wei; Wu Yao (Chemical Engineering Journal, 2023)

Highly dispersed FeN-CNTs heterogeneous electro-Fenton catalyst for carbamazepine removal with low Fe leaching at wide pH - Jieru Guo; Ge Song; Minghua Zhou (Chemical Engineering Journal, 2023)

Tinea Capitis in Children Younger than Two Years Old: A Retrospective Study and Treatment Recommendations - Ge Song; Meijie Zhang; Xue Kong; Weida Liu; Guanzhao Liang (Mycopathologia, 2023)

Identification of watermelon H3K4 and H3K27 genes and their expression profiles during watermelon fruit development - Yang Qiao; Yan-Ge Li; Tong-Lu Wei; Hai-Nan Liu; Mao-Song Pei; Xue-Jie Zhu; Zhong-Hou Zhu; Da-Long Guo (Molecular Biology Reports, 2023)

Mississippi Valley-type Zn–Pb deposits in orogenic thrust belts: ore formation in response to synorogenic crustal transpression or extension - Yucai Song; Zengqian Hou; Yingchao Liu; Liangliang Zhuang; Ge Hu (Mineralium Deposita, 2023)

Dynamic simulation and analysis of land use competition patterns to support sustainable territorial spatial management: a case study of Shenyang City, Northeast China - Quanxi Wang; Ge Song; Gaofeng Ren; Hongjun Sui; Ruiqing Su (Environmental Science and Pollution Research, 2023)

Salidroside promotes healthy longevity by interfering with HSP90 activity - Jianfei Zhang; Zhiquan Li; Jiangbo Song; Lei Zhou; Xin Chen; Wen Ge; Tianyi Dong; Yuxin Luo; Ting Mao; Zheng Li; Duan Tan; Lene Juel Rasmussen; et al. (GeroScience, 2023)

Silica mitigated calcium mineral scaling in brackish water reverse osmosis - Kai-Ge Lu; Shuanglong Ma; Dangling Hua; Hongen Liu; Chang Li; Jia Song; Haiou Huang; Yuchen Qin (Water Research, 2023)

Response of total suspended matter to natural and anthropogenic factors since 1990 in China's large lakes - Hui Tao; Kaishan Song; Ge Liu; Zhidan Wen; Yang Lu; Junbin Hou; Lili Lyu; Qiang Wang; Yingxin Shang; Sijia Li; Chong Fang (Science of The Total Environment, 2023)

The behavior of microplastics and nanoplastics release from UV-aged masks in the water - Hao Liang; Ruiyang Guo; Di Liu; Ningning Song; Fangli Wang; Yan Li; Wei Ge; Chao Chai (Science of The Total Environment, 2023)

3D printing MOF nanozyme hydrogel with dual enzymatic activities and visualized glucose monitoring for diabetic wound healing - Ziyan Chen; Shen Song; Huajing Zeng; Zhenlin Ge; Bin Liu; Zengjie Fan (Chemical Engineering Journal, 2023)

Molecular mechanisms of miR172a and its target gene LbrTOE3 regulating maturation in Lilium - Xiaoshan Wang; Qing Li; Haoran Zhu; Meiqi Song; Kezhong Zhang; Wei Ge (Planta, 2023)

Responses of soil carbon cycling microbial functional genes to nitrogen and phosphorus addition in saline-sodic soils - Xuejun Du; Yanning Ge; Yun Zhang; Hao Hu; Yiying Zhang; Ziye Yang; Xueqin Ren; Shuwen Hu; Haojie Feng; Yuling Song (Plant and Soil, 2023)

Application of an energy-based design procedure in self-centering shear wall systems - Ge Song; Lili Xing (Bulletin of Earthquake Engineering, 2023)

Multi-year nitrogen accumulation weakens the stabilizing effect of species asynchrony on drought resistance in a Tibetan alpine meadow - Ge Hou; Tiancai Zhou; Peili Shi; Jian Sun; Ning Zong; Jialuo Yu; Minghua Song (Agricultural and Forest Meteorology, 2023)

Determination of Earth rotation parameters by Beidou navigation satellite system - Song Jia; Bofeng Li; Haibo Ge; Jing Qiao (Advances in Space Research, 2023)

Comparative genomics predict specific genes in potential mucorales identification - Meijie Zhang; Wenqi Xu; Huan Mei; Ge Song; Naicen Ge; Ye Tao; Weida Liu; Guanzhao Liang (Archives of Microbiology, 2023)

High‐frequency variability of carbon dioxide fluxes in tidal water over a temperate salt marsh - Shuzhen Song; Zhaohui Aleck Wang; Kevin D. Kroeger; Meagan Eagle; Sophie N. Chu; Jianzhong Ge (Limnology and Oceanography, 2023)
Existing analyses of salt marsh carbon budgets rarely quantify carbon loss as CO 2 through the air–water interface in inundated marshes. This study estimates the variability of partial pressure of CO 2 ( p CO 2 ) and air–water CO 2 fluxes over summer and fall of 2014 and 2015 using high‐frequency measurements of tidal water p CO 2 in a salt marsh of the U.S. northeast region. Monthly mean CO 2 effluxes varied in the range of 5.4–25.6 mmol m −2 marsh d −1 (monthly median: 4.8–24.7 mmol m −2 marsh d −1 ) during July to November from the tidal creek and tidally‐inundated vegetated platform. The source of CO 2 effluxes was partitioned between the marsh and estuary using a mixing model. The monthly mean marsh‐contributed CO 2 effluxes accounted for a dominant portion (69%) of total CO 2 effluxes in the inundated marsh, which was 3–23% (mean 13%) of the corresponding lateral flux rate of dissolved inorganic carbon (DIC) from marsh to estuary. Photosynthesis in tidal water substantially reduced the CO 2 evasion, accounting for 1–86% (mean 31%) of potential CO 2 evasion and 2–26% (mean 11%) of corresponding lateral transport DIC fluxes, indicating the important role of photosynthesis in controlling the air–water CO 2 evasion in the inundated salt marsh. This study demonstrates that CO 2 evasion from inundated salt marshes is a significant loss term for carbon that is fixed within marshes.

Decreasing O2 availability reduces cellular protein contents in a marine diatom - Bokun Chen; Hui Song; Xue Yang; Ge Xu; Wei Zhao; Yue Meng; Gang Li (Science of The Total Environment, 2023)

Recent advances in the control of volatile organic compounds emissions from indoor wood-based panels: A comprehensive review - Yang Yang; Zhongfeng Zhang; Lei Zhang; Feifei Song; Yi Ren; Xu Zhang; Jijuan Zhang; Rock Keey Liew; Shin Ying Foong; William Woei Fong Chong; Su Shiung Lam; Meenakshi Verma; et al. (Science of The Total Environment, 2023)

Fibrillation of whey protein isolate by radio frequency heating for process efficiency: Assembly behavior, structural characteristics, and in-vitro digestion - Shuangshuang Wang; Yuxia Xie; Yi Ding; Zhenquan Huo; Jiaming Li; Jiaqing Song; Yucui Huo; Lili Zhao; Jing Zhang; Shaojin Wang; Jiaying Zhang; Wupeng Ge (Innovative Food Science & Emerging Technologies, 2023)

A new insight into the polar lipid composition in mature breast milk and ewe milk with comparative lipidomics analysis - Shuangshuang Wang; Yuxuan Song; Rui He; Guanli Du; Lei Zhang; Bangjun Zhang; Jiaying Zhang; Lili Zhao; Jing Zhang; Wupeng Ge (Food Research International, 2023)

Fate of selenium in a Se-enriched region of North China: Translocation, bioaccumulation, source, and health benefits - Kui Cai; Yan Zhao; Zefeng Song; Wenlou Luan; Jian Yang; Li Hu; Xin Liu; Ge Lei; Avelino Núñez Delgado (Environmental Research, 2023)

Human response to the bed thermal environment generated by a ventilated mattress combined with local heating - Ge Song; Arsen Krikor Melikov; Guoqiang Zhang; Mariya Petrova Bivolarova (Building and Environment, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

The Domestic Isolation of Terbinafine- and Itraconazole-Resistant Trichophyton indotineae in Chinese Mainland - Xue Kong; Ge Song; Huan Mei; Hailin Zheng; Chao Tang; Sybren de Hoog; Xiaofang Li; Xiaodong She; Weida Liu; Guanzhao Liang (Mycopathologia, 2023)

EGFL6 promotes bone metastasis of lung adenocarcinoma by increasing cancer cell malignancy and bone resorption - Xiaoting Song; Xu Cheng; Xiangang Jin; Shengyu Ruan; Xianquan Xu; Feng Lu; Xinhui Wu; Fangying Lu; Mingxuan Feng; Liwei Zhang; Renshan Ge; Haixiao Chen; et al. (Clinical & Experimental Metastasis, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

A stabilizing benders decomposition method for the accessibility-oriented charging station location problem - Maocan Song; Lin Cheng; Huimin Ge; Yan Li; Chao Sun (Sustainable Cities and Society, 2023)

Ecosystem sustainability of rice and aquatic animal co-culture systems and a synthesis of its underlying mechanisms - Lei Ge; Yu Sun; Yujie Li; Luyao Wang; Guanqing Guo; Lili Song; Cui Wang; Guogan Wu; Xiaoyun Zang; Xiaomei Cai; Shuangxi Li; Peng Li (Science of The Total Environment, 2023)

Nonagricultural emissions enhance dimethylamine and modulate urban atmospheric nucleation - Yunhua Chang; Qingyang Ling; Xinlei Ge; Xiangyang Yuan; Shengqian Zhou; Kai Cheng; Jianjiong Mao; Dandan Huang; Qingyao Hu; Jun Lu; Shijie Cui; Yaqing Gao; et al. (Science Bulletin, 2023)

Coupling activation and curing to tune the permselectivity of poly(piperazine amide) nanofiltration membranes - Dongsheng Zhao; Jiyu Song; Yiwen Zhang; Zhiquan Lin; Bo He; Nanfu Qiao; Kangping Huang; Wei Zhang; Shuang Ge; Yuying Li; B. Larry Li; Kang Xie; et al. (Journal of Water Process Engineering, 2023)

Sentinel-3 OLCI observations of Chinese lake turbidity using machine learning algorithms - Yong Li; Sijia Li; Kaishan Song; Ge Liu; Zhidan Wen; Chong Fang; Yingxin Shang; Lili Lyu; Lele Zhang (Journal of Hydrology, 2023)

Promoting sensitive colorimetric detection of hydroquinone and Hg2+ via ZIF-8 dispersion enhanced oxidase-mimicking activity of MnO2 nanozyme - Na Liang; Xinyue Ge; Yan Zhao; Lian Xia; Zhi-Ling Song; Rong-Mei Kong; Fengli Qu (Journal of Hazardous Materials, 2023)

Species-specific CgCaspase-Cg-5 in the pacific oyster induces haemocyte apoptosis by regulating the mRNA expression of apoptosis-related genes in the early stage of immune response - Lei Gao; Qingsong Li; Ziyang Zhang; Pingan Ge; Jiejie Sun; Xue Qiao; Lingling Wang; Linsheng Song (Fish & Shellfish Immunology, 2023)

A new creep contact model for frozen soils and its application - Ge Zhang; Enlong Liu; Ruihong Wang; Bingtang Song (Computers and Geotechnics, 2023)

CALIPSO-observed Southeast Asia biomass-burning influences on aerosol vertical structure in Guangdong-Hong Kong-Macao Greater Bay Area - Xiaoyue Zeng; Siwei Li; Jia Xing; Jie Yang; Qingxin Wang; Ge Song; Mengfan Teng; Dong Zhou; Jinjun Lu (Atmospheric Research, 2023)

Phosphorus amendment alters soil arbuscular mycorrhizal fungal functional guild compositions in a subtropical forest - Quan-Cheng Wang; Sheng-Sheng Jin; Shanshan Liu; Ge Song; Chunjian Duan; Peng-Peng Lü; Pulak Maitra; Lin Xie; Yongxin Lin; Hang-Wei Hu; Ji-Zheng He; Yong Zheng (Journal of Soils and Sediments, 2023)

Risk control of antibiotics, antibiotic resistance genes (ARGs) and antibiotic resistant bacteria (ARB) during sewage sludge treatment and disposal: A review - Jiaqi Wang; Siqi Xu; Kai Zhao; Ge Song; Shunan Zhao; Ruiping Liu (Science of The Total Environment, 2023)

Tracing magnesium flows in China: A dynamic material flow analysis - Tianjiao Guo; Yong Geng; Xiaoqian Song; Xue Rui; Zewen Ge (Resources Policy, 2023)

Magnetic MnFe2O4 nanoparticles anchored on sludge-derived biochar in activating peroxydisulfate for levofloxacin degradation: Mechanism, degradation pathways and cost analysis - Xiaoyan Meng; Tingting Song; Chao Zhang; Huayu Wang; Ming Ge; Changsheng Guo (Journal of Environmental Chemical Engineering, 2023)

Evaluation of a novel carbon-based micro-nano zero-valent iron composite for immobilization of heavy metals in soil - Song Guo; Huifen Yang; Qiwei Sun; Ge Zhang; Tong Zhao; Yichen Zhou; Xuan Li; Pu Gao (Journal of Environmental Chemical Engineering, 2023)

Biomass derived S, N self-doped catalytic Janus cathode for flow-through metal-free electrochemical advanced oxidation process: Better removal efficiency and lower energy consumption under neutral conditions - Xuechun Wang; Qizhan Zhang; Jiana Jing; Ge Song; Minghua Zhou (Chemical Engineering Journal, 2023)

The Subsurface and Surface Indian Ocean Dipoles and Their Association with ENSO in CMIP6 models - Ge Song; Rongcai Ren (Advances in Atmospheric Sciences, 2023)

Ultrasonication-enhanced biogas production in anaerobic digestion of waste active sludge: A pilot scale investigation - Kai Zhao; Shunan Zhao; Ge Song; Chaojie Lu; Ruiping Liu; Chengzhi Hu; Jiuhui Qu (Resources, Conservation and Recycling, 2023)

NH3 and N2O emission durability of the heavy-duty diesel engine with DOC, DPF, SCR, and ASC through the accelerated aging method - Liqun Lyu; Wenqiang Sun; Ping Feng; Huaiyu Wang; Lijun Hao; Jianwei Tan; Xin Wang; Chao Song; Haixia Li; Zhao Li; Jiaxing Wang; Yunshan Ge (Fuel, 2023)

Aerobic composting with sauerkraut fermentation waste water: Increasing the stability and complexity of bacterial community and changing bacterial community assembly processes - Jie Kang; Gang Song; Xu Wang; Wei Qiu; Fangyi Pei; Hongzhi Ling; Wenxiang Ping; Jingping Ge (Bioresource Technology, 2023)

Sulfur dioxide may predominate in the adverse effects of ambient air pollutants on semen quality among the general population in Hefei, China - Feng Zhang; Hang Li; Wenting Xu; Ge Song; Zhanpeng Wang; Xiaohong Mao; Yiqiu Wei; Mengyang Dai; Yuying Zhang; Qunshan Shen; Feifei Fu; Jing Tan; et al. (Science of The Total Environment, 2023)

Evaluating response mechanisms of soil microbiomes and metabolomes to Bt toxin additions - Lei Ge; Lili Song; Luyao Wang; Yujie Li; Yu Sun; Cui Wang; Jun Chen; Guogan Wu; Aihu Pan; Yunfei Wu; Zhexue Quan; Peng Li (Journal of Hazardous Materials, 2023)

Structural change and functional improvement of wheat germ protein promoted by extrusion - Chaofan Gao; Junqiang Jia; Yi Yang; Shuangmei Ge; Xinyu Song; Jiahong Yu; Qiongying Wu (Food Hydrocolloids, 2023)

Transcriptomic and proteomic analysis reveals (E)-2-hexenal modulates tomato resistance against Botrytis cinerea by regulating plant defense mechanism - Jihong Zhang; Yuqiong Li; Shenglong Du; Zhiping Deng; Quanwu Liang; Ge Song; Haihua Wang; Mingli Yan; Xuewen Wang (Plant Molecular Biology, 2023)

Inhibitory effect of volatile organic compounds from Bacillus flexus TR-1 against Aspergillus flavus and aflatoxins in grains during storage - An-Dong Gong; Meng-Ge Song; Hua-Ling Wang; Gao-Zhan Wang; Jian-Hua Wang; Jing-Bo Zhang (BioControl, 2023)

Applications of bioremediation and phytoremediation in contaminated soils and waters: CREST publications during 2018–2022 - Chen-Jing Liu; Song-Ge Deng; Chun-Yan Hu; Peng Gao; Eakalak Khan; Chang-Ping Yu; Lena Q. Ma (Critical Reviews in Environmental Science and Technology, 2023)

Application of a novel Ca-Fe-Si-S composite for the synchronous stabilization of As, Zn, Cu, and Cd in acidic arsenic slag - Ge Zhang; Huifen Yang; Xuan Li; Yichen Zhou; Song Guo; Tong Zhao (Environmental Science and Pollution Research, 2023)

A continuous paleorecord of vegetation and environmental change from Erxianyan Wetland over the past 60,000 years in central China - Menglin Song; John Dodson; Fengyan Lu; Ge Shi; Hong Yan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Transcriptomic analysis of polyketide synthesis in dinoflagellate, Prorocentrum lima - Xiukun Wan; Ge Yao; Kang Wang; Shaoheng Bao; Penggang Han; Fuli Wang; Tianyu Song; Hui Jiang (Harmful Algae, 2023)

Bifunctional carbon nanofibrous interlayer embedded with cobalt single atoms for polysulfides trapping and catalysis in lithium-sulfur batteries - Beibei Song; Haoyue Zhao; Gang Zhao; Han Li; Can Ge; Guilong Yan; Jian Fang (Chemical Engineering Journal, 2023)

Trace elements in outdoor and indoor PM2.5 in urban schools in Xi’an, Western China: characteristics, sources identification and health risk assessment - Runyu Wang; Xinxin Ding; Jingzhi Wang; Zhibao Dong; Hongmei Xu; Ge Ma; Bo Gao; Han Song; Menghan Yang; Junji Cao (Environmental Geochemistry and Health, 2023)

Targeting erythrocyte-mediated hypoxia to alleviate lung injury induced by pyrrolizidine alkaloids - Zijing Song; Wei Lian; Yisheng He; Chunyuan Zhang; Ge Lin (Archives of Toxicology, 2023)

Immobilizing arsenic in soil via amine metal complex: a case study using iron-ethylenediamine - Qilin Lv; Tairan Zhou; Tianhao Wang; Shuhan Wang; Yanning Ge; Yuling Song; Xueqin Ren; Shuwen Hu (Environmental Science and Pollution Research, 2023)

Decoupling of N and P aggravated upward along food chains in an urban river ecosystem - Shenqun An; Zhengbing Yan; Ying Song; Qiang Fu; Feiyang Ge; Zehao Wu; Wei An; Wenxuan Han (Chemosphere, 2023)

Remote sensing of fluorescent humification levels and its potential environmental linkages in lakes across China - Yingxin Shang; Kaishan Song; Fengfa Lai; Lili Lyu; Ge Liu; Chong Fang; Junbin Hou; Sining Qiang; Xiangfei Yu; Zhidan Wen (Water Research, 2023)

Spatiotemporal variation of cultivated land ecosystem stability in typical regions of Lower Liaohe Plain China based on stress - buffer - response - Hongjun Sui; Ge Song; Wanying Liu; Yuxin Zhang; Ruiqing Su; Quanxi Wang; Gaofeng Ren; Yuqi Mi (Science of The Total Environment, 2023)

Revisiting UV/sulfite exposed to air: A redox process for reductive dechlorination and oxidative mineralization - Ge Song; Pei Su; Qizhan Zhang; Xuechun Wang; Minghua Zhou (Science of The Total Environment, 2023)

Effect of Manila clam Ruditapes philippinarum on burial depth of eelgrass Zostera marina seeds and sediment porosity - Xiangtao Wei; Zhaojun Liu; Guoqiang Huang; Jianda Song; Xujia Liu; Fengying Zheng; Changzi Ge (Regional Studies in Marine Science, 2023)

Coumaronochromones, flavanones, and isoflavones from the twigs and leaves of Erythrina subumbrans inhibit PTP1B and nitric oxide production - Cai-Ying Liu; Pan Deng; Bin Wang; Ai-Hong Liu; Meng-Ge Wang; Song-Wei Li; Li-Li Chen; Shui-Chun Mao (Phytochemistry, 2023)

Multiple-functionalized biochar affects rice yield and quality via regulating arsenic and lead redistribution and bacterial community structure in soils under different hydrological conditions - Xing Yang; Zhinan Dai; Chengjun Ge; Huamei Yu; Nanthi Bolan; Daniel C.W. Tsang; Hocheol Song; Deyi Hou; Sabry M. Shaheen; Hailong Wang; Jörg Rinklebe (Journal of Hazardous Materials, 2023)

Floating sandwich-type electro-Fenton: A feasible process to remove micro-pollutants through adsorption enrichment and enhanced oxidation efficiency - Qizhan Zhang; Xuechun Wang; Jinxin Xie; Haoran Yin; Ge Song; Minghua Zhou (Journal of Hazardous Materials, 2023)

Iron-modified phosphorus- and silicon-based biochars exhibited various influences on arsenic, cadmium, and lead accumulation in rice and enzyme activities in a paddy soil - Xing Yang; Ergang Wen; Chengjun Ge; Ali El-Naggar; Huamei Yu; Shengsen Wang; Eilhann E. Kwon; Hocheol Song; Sabry M. Shaheen; Hailong Wang; Jörg Rinklebe (Journal of Hazardous Materials, 2023)

Reclaimed water use improved polluted water's self-purification capacity --Evidenced by water quality factors and bacterial community structure - Shenqun An; Ying Song; Qiang Fu; Rong Qi; Zehao Wu; Feiyang Ge; Xiaoqian Lu; Wei An; Wenxuan Han (Journal of Cleaner Production, 2023)

Recent advances in persulfate activation by magnetic ferrite-carbon composites for organic contaminants degradation: Role of carbon materials and environmental application - Tingting Song; Xiaoxuan Kang; Changsheng Guo; Zhangxing He; Ming Ge (Journal of Environmental Chemical Engineering, 2023)

Solvent-free oxidation of toluene to benzaldehyde using electron-rich Au clusters confined in Silicalite-1 - He Huang; Huahua Fan; Yuzhen Ge; Wanyue Ye; Yingcen Liu; Caicheng Song; Hua Lin; Xiaotong Zhang; Bing Li; Xiaowa Nie; Shufen Zhang; Rongwen Lu (Chemical Engineering Journal, 2023)

Chronic hypoxia and Cu2+ exposure induce gill remodeling of largemouth bass through endoplasmic reticulum stress, mitochondrial damage and apoptosis - Qiao Liu; Hong Wang; Jiayu Ge; Lisen Li; Jie Luo; Kuo He; Haoxiao Yan; Xin Zhang; Rabia Tahir; Wei Luo; Shiyi Chen; Zhang Cheng; et al. (Aquatic Toxicology, 2023)

Trimmed L-Moments of the Pearson Type III Distribution for Flood Frequency Analysis - Yifan Jia; Songbai Song; Liting Ge (Water Resources Management, 2023)

Genome-wide association study identifies GhSAL1 affects cold tolerance at the seedling emergence stage in upland cotton (Gossypium hirsutum L.) - Qian Shen; Siping Zhang; Changwei Ge; Shaodong Liu; Jing Chen; Ruihua Liu; Huijuan Ma; Meizhen Song; Chaoyou Pang (Theoretical and Applied Genetics, 2023)

Degradation of carbamazepine over MOFs derived FeMn@C bimetallic heterogeneous electro-Fenton catalyst - Yang Zheng; Xuedong Du; Ge Song; Jinyu Gu; Jieru Guo; Minghua Zhou (Chemosphere, 2023)

Nitrogen fertilization modulates rice seed endophytic microbiomes and grain quality - Yuanhui Liu; Guang Chu; Erinne Stirling; Haoqing Zhang; Song Chen; Chunmei Xu; Xiufu Zhang; Tida Ge; Danying Wang (Science of The Total Environment, 2023)

Winter warming alleviates the severely negative effects of nitrogen addition on ecosystem stability in a Tibetan alpine grassland - Ning Zong; Ge Hou; Peili Shi; Minghua Song (Science of The Total Environment, 2023)

Characterization and comparison of lipids from human and ewe colostrum based on lipidomics analysis - Shuangshuang Wang; Zhaojun Liu; Yuxuan Song; Yan Zhang; Lili Zhao; Lei Zhang; Xin Lü; Haiyan Wang; Ximei Zhang; Jiaying Zhang; Wupeng Ge (Food Chemistry, 2023)

Fluidized nanoparticles catalyzed oxygen evolution reaction: Enhanced stability, kinetics and electrocatalytic activity - Dianmei Song; Hailong Yan; Wei Xu; Yi-Ge Zhou (Chemical Engineering Journal, 2023)

Engineered anti-cancer nanomedicine for synergistic ferroptosis-immunotherapy - Xinyu Zhang; Haiyan Ge; Yanling Ma; Linlin Song; Yansong Ma; Guanglong Tian; Lei Wang; Qingwei Meng; Xiao Sun (Chemical Engineering Journal, 2023)

Highly efficient electro-peroxone enhanced by oxygen-doped carbon nanotubes with triple role of in-situ H2O2 generation, activation and catalytic ozonation - Jinyu Gu; Jinxin Xie; Shasha Li; Ge Song; Minghua Zhou (Chemical Engineering Journal, 2023)

Targeted delivery of platelet membrane modified extracellular vesicles into atherosclerotic plaque to regress atherosclerosis - Qiyu Li; Zheyong Huang; Zhiqing Pang; Qiaozi Wang; Jinfeng Gao; Jing Chen; Zhengmin Wang; Haipeng Tan; Su Li; Fei Xu; Jinxiang Chen; Muyin Liu; et al. (Chemical Engineering Journal, 2023)

Three-dimensional porous aerogel-bead absorbent with high dispersibility of lanthanum active sites to boost phosphorus scavenging - Bohan Liu; Jun Nan; Ruixue Jiang; Fangmin Wu; Langrun Song; Zhencheng Ge; Xuesong Ye; Xinhui Zhang; Wei Wang (Chemical Engineering Journal, 2023)

Transcription factor TaGAMYB from wheat (Triticum aestivum L.) regulates flowering time and fertility in transgenic Arabidopsis thaliana - Xuetong Yang; Kai Wang; Limeng Ge; Xianning Chen; Lingli Zhang; Xiyue Song (Planta, 2023)

Simple and Commercially Available 6-chloroimidazo[1,2-a]pyridine-2-carboxylic Acid-based Fluorescent Probe for Monitoring pH Changes - Yunlong Gao; Guangle Song; Guowei Shi; Jixiang Xiao; Chunhao Yuan; Yanqing Ge (Journal of Fluorescence, 2023)

A perspective from the past in conservation of plant biodiversity in central China - John Dodson; Ge Shi; Menglin Song (Environmental Monitoring and Assessment, 2023)

Evaluation of housekeeping genes as references for quantitative real‐time PCR analysis of European eel, Anguilla anguilla - Ying‐Ying Li; Xi Chen; Jin‐Xian Yang; Qiang Chen; Tie‐Ying Song; Jun‐Qing Ge (Journal of Fish Biology, 2023)
Eels are important aquaculture species for which an increasing number of reference genes are being identified and applied. In this study, five housekeeping genes [RPL7 (ribosomal protein L7), 18 S (18 S ribosomal RNA), EF1A (elongation factor 1α), ACTB (β‐actin) and GAPDH (glyceraldehyde‐3‐phosphate dehydrogenase)] were chosen to evaluate their reliability as reference genes for quantitative real‐time PCR (qPCR) for the study of Anguilla anguilla . The expression of the selected genes in different eel tissues was determined using qPCR at different growth stages or upon challenge by Anguillid herpesvirus (AngHV), and the expression levels of these genes were then compared and evaluated using the geNorm and NormFinder algorithms. Then, RefFinder was used to comprehensively rank the examined housekeeping genes. Interestingly, the expression of the evaluated housekeeping genes exhibited tissue‐dependent and treatment‐dependent variations. In different growth periods A. anguilla tissues, the most stable genes were the following: ACTB in mucus; 18 S in skin and kidney; RPL7 in muscle, gill, intestine and brain; EF1A in heart and liver; and GAPDH in spleen. In contrast, in AngHV‐challenged A. anguilla tissues, the most stable genes were the following: 18 S in mucus; RPL7 in skin, gill, heart, spleen, kidney and intestine; EF1A in muscle and liver; and ACTB in brain. Further comparison analysis indicated that the expression of RPL7 and EF1A was stable in multiple A. anguilla tissues in different growth periods and in eels challenged by AngHV. Nonetheless, the expression level of GAPDH in eel tissues was lower, and it was unstable in several tissues. These results indicated that the selection of reference genes for qPCR analysis in A. anguilla should be made in accordance with experimental parameters, and both RPL7 and EF1A could be used as reference genes for qPCR study of A. anguilla at different growth stages or upon challenge by AngHV. The reference genes identified in this study could improve the accuracy of qPCR data and facilitate further studies aimed at understanding the biology of eels.

Darwin's naturalization conundrum reconciled by changes of species interactions - Jiang Wang; Shao‐Peng Li; Yuan Ge; Xiao‐Yan Wang; Song Gao; Tong Chen; Fei‐Hai Yu (Ecology, 2023)
Although phylogenetic distance between native and exotic species has a close link with their interactions, it is still unclear how environmental stresses and species interactions influence the relationship between phylogenetic distance and biological invasions. Here we assessed the effect of invader–native phylogenetic distance on the growth of the invader ( Symphyotrichum subulatum ) under three levels of drought (no, moderate, or intense drought). Under no drought, interspecific competition between close relatives was the dominant process and native communities more closely related to the invader showed higher resistance to invasion, supporting Darwin's naturalization hypothesis. In contrast, under intense drought, facilitation between close relatives by mutualism with arbuscular mycorrhizal fungi (AMF) became more important, and the invader became more successful in their more closely related native communities, supporting the preadaptation hypothesis. The colonization rate of AMF of the invader was higher in more closely related native communities regardless of the drought treatment, but it was only positively related to invader biomass under intense drought. Therefore, the shift of species interactions from competition to facilitation may be ascribed to the promotion of AMF to invasion occurring under intense drought, which leads to the effect of closely related natives on the invader shifting from negative to positive. Our results provide a new angle to resolve Darwin's naturalization conundrum from the change of species interactions along a stress gradient, and provide important clues for invasion management when species interactions change in response to global climatic change.

How can the positive Indian Ocean Dipole events co‐occur with La Niña? - Ge Song; Rongcai Ren (International Journal of Climatology, 2022)
Positive/negative Indian Ocean Dipole (IOD) tends to co‐occur with El Niño/La Niña. Five positive IODs, however, are observed under La Niña condition in 1961, 1966, 1967, 2007, and 2011. This study uses the monthly ocean temperature and atmospheric reanalysis datasets from ECMWF to investigate how these positive IOD events occurred. It is found that the five positive IODs are consistently accompanied by a moderately strong positive subsurface IOD (Sub‐IOD) event that initiated earlier. The Sub‐IOD‐related oceanic dynamical processes including oceanic Kelvin and Rossby waves help to promote the development of the positive IODs. More specifically, the equatorial easterly anomalies in the Tropical Indian Ocean (TIO) that are crucial for the development of the positive Sub‐IODs and IODs in 1961/2011 are triggered by an anticyclonic curl over South Indian Ocean that is induced by a Southern Hemispheric Indian Ocean Subtropical Dipole mode. The crucial equatorial easterly anomalies in 1967 are triggered by a thermocline warming in the southwestern TIO induced by westward downwelling oceanic Rossby waves, while in 1966/2007, the equatorial easterly anomalies are connected with the anomalous Walker circulation resulting from the certain sea surface temperature anomaly pattern over the equatorial Pacific. On the other hand, the remote effects of La Niña on TIO are relatively weaker, being overwhelmed by the above triggering processes.

Mitochondrial Localization of SARM1 in Acrylamide Intoxication Induces Mitophagy and Limits Neuropathy - Shuai Wang; Mingxue Song; Hui Yong; Cuiqin Zhang; Kang Kang; Zhidan Liu; Yiyu Yang; Zhengcheng Huang; Shu’e Wang; Haotong Ge; Xiulan Zhao; Fuyong Song (Molecular Neurobiology, 2022)

Enhance energy supply of largemouth bass (Micropterus salmoides) in gills during acute hypoxia exposure - Qiao Liu; Hong Wang; Jiayu Ge; Jie Luo; Kuo He; Haoxiao Yan; Xin Zhang; Rabia Tahir; Wei Luo; Zhiqiong Li; Song Yang; Liulan Zhao (Fish Physiology and Biochemistry, 2022)

Infestation and distribution of chigger mites on Confucian white-bellied rat (Niviventer confucianus) in Southwest China - Yan-Ling Chen; Xian-Guo Guo; Wen-Yu Song; Tian-Guang Ren; Lei Zhang; Rong Fan; Cheng-Fu Zhao; Zhi-Wei Zhang; Wen-Ge Dong; Xiao-Bin Huang (Biologia, 2022)

Synergistic removal of organic pollutants from water by CTF/BiVO4 heterojunction photocatalysts - Yan Yu; Yanan Sun; Beixiao Ge; Jiawen Yan; Kaili Zhang; Hui Chen; Jinxing Hu; Juntao Tang; Shuang Song; Tao Zeng (Environmental Science and Pollution Research, 2022)

Evolutions of upwelling and terrestrial organic matter input in the inner shelf of the East China Sea in the last millennium revealed by long-chain alkyl diols proxies - Chuanhui Song; Tianxiang Dang; Ting Zhang; Tiantian Ge; Rong Xiang; Lei Xing; Rui Bao; Yang Zhou; Rui Xiao; Baojin Wu (Frontiers in Marine Science, 2022)
Long-chain alkyl diols (LCDs) can be used as organic geochemical proxies for paleoceanographic change, especially in marginal sea areas where large volumes of sediments are deposited rapidly and continuously. However, little is known about the applicability and response on a millennium scale in relation with existing records in those sediments. We reconstruct changes in upwelling and terrestrial organic matter (OM) input in core sediments from the Zhejiang Fujian coastal station (T08) and Yangtze River Estuary station (T06) in the inner shelf of the East China Sea (ECS) over the last millennium, using the LCD based proxies: diol index 2 (DI-2), and FC 32 1,15-diol. Our results show that DI-2 values ([(C 28 +C 30 )1,14-diols]/([(C 28 +C 30 )1,13-diols]+[(C 28 +C 30 )1,14-diols])) at T08 decrease significantly during 600–400 yr BP but increase gradually after 400 yr BP. The FC 32 1,15-diol proxy ([C 32 1,15-diol]×100/([(C 28 +C 30 )1,13-diols]+[(C 30 +C 32 )1,15-diols])) at T06 shows marked fluctuations during 1000–800 yr BP, followed by a significant decline during 800–500 yr BP but a subsequent increase from 500 to 300 yr BP. We find that variations in DI-2 values are broadly consistent with changes in the strength of the East Asian Summer Monsoon (EASM) and the Kuroshio Current and are likely linked to changes in the frequency and intensity of the El Niño-Southern Oscillation (ENSO). The increased strength of the EASM causes greater offshore movement of the upper layer of seawater, which in turn triggers upwelling of bottom waters formed by Kuroshio subsurface waters. We find that variations in FC 32 1,15-diol proxy are controlled mainly by the East Asian Winter Monsoon (EAWM) and the Yangtze River discharge. By increasing the strength of the EAWM, southward transportation of material deposited in the estuary of the Yangtze River by the ECS coastal currents is promoted. In addition, we synthesize records of other organic geochemical indicators nearby core sediments in the ECS; these records emphasize the importance of reconstructing the evolutionary history of upwelling and subdividing the relative inputs of terrestrial OM. Our study provides a new means for reconstructing the evolution of upwelling and terrestrial OM input in the inner shelf of the ECS over the last millennium.

The DRD2 Taq1A polymorphism moderates the effect of PTSD symptom severity on the left hippocampal CA3 volume: a pilot study - Minlan Yuan; Hongru Zhu; Yuchen Li; Fenfen Ge; Su Lui; Qiyong Gong; Changjian Qiu; Huan Song; Wei Zhang (Psychopharmacology, 2022)
Rationale and objectives The hippocampus, especially the CA1, CA3, and dentate gyrus (DG) subfields, is reported to be associated with post-traumatic stress disorder (PTSD) after trauma. However, neuroimaging studies of the associations between PTSD and hippocampal subfield volumes have failed to yield consistent findings. The aim of this study is to examine whether the dopamine D2 receptor (DRD2) Taq1A polymorphism, which is associated with both hippocampal function and PTSD, moderated the association between PTSD severity and hippocampal CA1, CA3 and DG volumes. Methods T1-weighted images were acquired from 142 trauma survivors from the 2008 Wenchuan earthquake using a 3.0-T magnetic resonance imaging system. Hippocampal subfield segmentations were performed with FreeSurfer v6.0. We used the simple moderation model from the PROCESS v3.4 tool for SPSS 23.0 to examine the association between the rs1800497 polymorphism, PTSD severity, and hippocampal CA3 and DG volumes. Results A significant genotype × PTSD symptom severity interaction was found for the left CA3 volume (Δ F = 5.01, p = 0.008, Δ R 2 = 0.05). Post hoc, exploratory analyses deconstructing the interaction revealed that severe PTSD symptomatology were associated with reduced left CA3 volume among TC heterozygotes ( t = − 2.86, p = 0.005). Conclusions This study suggests that DRD2 Taq1A polymorphism moderates the association between PTSD symptomatology and left CA3 volume, which promotes an etiological understanding of the hippocampal atrophy at the subfield level. This highlights the complex effect of environmental stress, and provides possible mechanism for the relationship between the dopaminergic system and hippocampal function in PTSD.

Comprehensive comparison of the prognostic value of systemic inflammation biomarkers for cancer cachexia: a multicenter prospective study - Hailun Xie; Guotian Ruan; Lishuang Wei; Heyang Zhang; Yizhong Ge; Qi Zhang; Shiqi Lin; Mengmeng Song; Xi Zhang; Xiaoyue Liu; Ming Yang; Meng Tang; et al. (Inflammation Research, 2022)

Effects of biochar application on the loss characteristics of Cd from acidic soil under simulated rainfall conditions - Zaijian Yuan; Yueyan Song; Dingqiang Li; Bin Huang; Yunhui Chen; Xiaojun Ge; Mingguo Zheng; Yishan Liao; Zhenyue Xie (Environmental Science and Pollution Research, 2022)

Transposon insertions within alleles of BnaFT.A2 are associated with seasonal crop type in rapeseed - Qingdong Jin; Gengdong Gao; Chaocheng Guo; Taihua Yang; Ge Li; Jurong Song; Na Zheng; Shuai Yin; Licong Yi; Zhen Li; Xianhong Ge; Graham J. King; et al. (Theoretical and Applied Genetics, 2022)

Facile synthesis of magnetic ZnFe2O4/AC composite to activate peroxydisulfate for dye degradation under visible light irradiation - Tingting Song; Quanbao He; Xiaoyan Meng; Zhangxing He; Ming Ge (Environmental Science and Pollution Research, 2022)

Differentiation of Algal Blooms and Aquatic Vegetation in Chinese Lakes Using Modified Vegetation Presence Frequency Index Method - Jing Pu; Kaishan Song; Ge Liu; Zhidan Wen; Chong Fang; Junbing Hou; Yunfeng Lv (Chinese Geographical Science, 2022)

RETRACTED: Amplitude and Phase Computable Ocean Wave Real-Time Modeling with GPU Acceleration - Guigui Wang; Shihan Tan; Ge Song; Sheng Wang (Journal of Marine Science and Engineering, 2022)
The CBATS (carrier-based aircraft take-off and landing training system) is an important application of virtual reality technology in the simulation field. Large-scale, real-time ocean simulations are the biggest challenge to the authenticity of the visual system of CBATS and are also currently the main research hotspot in the field of computer graphics. In this paper, a hybrid Ocean Modeling Method based on wavelet transform is presented. This method introduces an accurate phase calculation and a wind-field model solution to compensate for the randomness of wave generation and the lack of physical mechanism in spectral methods. The computational cost is greatly reduced by using a rough spatial grid to calculate the amplitude and phase values at any point in space, which effectively avoids Nyquist–Shannon Theorem limitations caused by the numerical solutions of PDEs (partial differential equations), and a high-fidelity simulation of high frequency, detailed sea surface and coherent phase-dependent wave effects is achieved. Practical verification shows that the method can fully meet the real-time simulation training requirements of CBATS with a strong real-time performance and good stability. Thus, it could play a significant role in improving the performance of the visual system.

Epidemiology of Onychomycosis in Chinese Mainland: A 30-year Retrospective Study - Ge Song; Meijie Zhang; Weida Liu; Guanzhao Liang (Mycopathologia, 2022)

Incorporating coastal blue carbon into subnational greenhouse gas inventories - Peng Zhao; Song Ge; Dinghua He; Cairong Zhong; Boyan Wang; Xiaokang Wang; Fengxia Wang; Shuhji Kao (Frontiers in Marine Science, 2022)
The climate mitigation potential of coastal blue carbon including mangroves, seagrasses and tidal marshes have been widely recognized, and guidelines for incorporating coastal wetlands into greenhouse gas inventories released by IPCC in 2014 make it possible to bring coastal blue carbon into multilevel climate governance regimes. However, the intricate guidelines and inadequate data block governments from accounting and reporting their coastal blue carbon in inventories. In this research, we integrated and simplified the equations and assumptions of IPCC inventory guidance on coastal wetlands, and took Hainan province of China as a case study by (1) formulating a land use change matrix from high resolution satellite imagery for the years of 2010 to 2020, (2) compiling dataset of emission factors for coastal wetlands of Hainan, and (3) estimating CO 2 , CH 4 , and N 2 O emissions from coastal wetlands in Hainan. We reveal that the mangroves’ area increased from 4,190.7 ha in 2010 to 4,644.1 ha in 2020, with a net increase of 483.9 ha from tidal flats and aquaculture ponds. The weighted average EF AGB and EF soil of Hainan is 61.7 MgC ha -1 and 227.4 MgC ha -1 , respectively,estimated from peer-reviewed literature in both Chinese and English. The annual average net CO 2 emission of mangroves of Hainan is -26974.3 MgCO 2 e yr -1 . CO 2 emission from mangrove deforestation and N 2 O emission from shrimp aquaculture in coastal aeras may offset the efforts of coastal wetlands conservation and restoration. Countries and sub-country regions are encouraged to bring coastal blue carbon into greenhouse gases inventories as soon as possible, and to take a bottom-up strategy to initiate the task at a local level.

Climate change and ecological engineering jointly induced vegetation greening in global karst regions from 2001 to 2020 - Jing Huang; Zhongxi Ge; Yuqing Huang; Xuguang Tang; Zhan Shi; Peiyu Lai; Zengjing Song; Binfei Hao; Hong Yang; Mingguo Ma (Plant and Soil, 2022)

Identification and management of GCK-MODY complicating pregnancy in Chinese patients with gestational diabetes - Yanyan Jiang; Fusong Jiang; Ming Li; Qingkai Wu; Chenming Xu; Rong Zhang; Mingqiang Song; Yanzhong Wang; Ying Wang; Yating Chen; Juan Zhang; Xiaoxu Ge; et al. (Molecular and Cellular Biochemistry, 2022)

Professional chess expertise modulates whole brain functional connectivity pattern homogeneity and couplings - Limei Song; Huadong Yang; Mingdong Yang; Dianmei Liu; Yanming Ge; Jinfeng Long; Peng Dong (Brain Imaging and Behavior, 2022)

Isolation, Identification, and Quantitative Determination of Saponin in Apostichopus japonicus by HPLC-DAD - Guiying Liu; Xuda Wang; Kun Ge; Jinhao Wu; Zhaohui Wang; Jing Du; Lun Song; Zunchun Zhou (Journal of Ocean University of China, 2022)

Global divergent trends of algal blooms detected by satellite during 1982–2018 - Chong Fang; Kaishan Song; Hans W Paerl; Pierre‐Andre Jacinthe; Zhidan Wen; Ge Liu; Hui Tao; Xiaofeng Xu; Tiit Kutser; Zongming Wang; Hongtao Duan; Kun Shi; et al. (Global Change Biology, 2022)
Algal blooms (ABs) in inland lakes have caused adverse ecological effects, and health impairment of animals and humans. We used archived Landsat images to examine ABs in lakes (>1 km 2 ) around the globe over a 37‐year time span (1982–2018). Out of the 176032 lakes with area >1 km 2 detected globally, 863 were impacted by ABs, 708 had sufficiently long records to define a trend, and 66% exhibited increasing trends in frequency ratio (FRQR, ratio of the number of ABs events observed in a year in a given lake to the number of available Landsat images for that lake) or area ratio (AR, ratio of annual maximum area covered by ABs observed in a lake to the surface area of that lake), while 34% showed a decreasing trend. Across North America, an intensification of ABs severity was observed for FRQR ( p p p p

Adaptive Network Design for Multiple Gliders Observation of Mesoscale Eddy - Zhanwen Gao; Ge Chen; Yang Song; Jie Zheng; Chunyong Ma (Frontiers in Marine Science, 2022)
With its excellent endurance, good maneuverability and track controllability, glider has become one of the important equipment to obtain ocean field data. The network observation of multiple gliders will be the main approach of ocean observation in the future. However, how to plan the glider path in a reasonable way and how to design the optimal observation network consisting of multiple gliders in an eddy have not been well solved. As an effort to tackle this problem, an adaptive network design algorithm for multiple gliders in mesoscale eddies observation which referred as “Optimal Sampling” is proposed in this paper. Simulation experiments of tracking a target eddy in the South China Sea (SCS) show that the proposed algorithm cannot only realize the adaptive network design for multiple gliders, but also ensure the uniform sampling inside the eddy. Compared with the traditional method which samples eddy along a fixed path, the observation data obtained by the solution proposed in this paper are more valuable to describe the essential temperature characteristics of eddies. The residual errors computed from the interpolation of the sampled field is also smaller.

The role of currently used medicinal plants in aquaculture and their action mechanisms: A review - Dawit Adisu Tadese; Changyou Song; Cunxin Sun; Bo Liu; Bo Liu; Qunlan Zhou; Pao Xu; Xianping Ge; Mingyang Liu; Xiaodi Xu; Metekia Tamiru; Zhigang Zhou; et al. (Reviews in Aquaculture, 2022)
Global aquaculture development increased rapidly in recent years, and the sector has become one of the fastest‐growing industries in the animal‐derived food production system. However, disease outbreak remains a major challenge that hinders sustainable production through an advanced level of intensification. Recently, antibiotics applied have been restricted globally against aquatic disease outbreaks due to their apparent accumulation in the tissues, which imposes on the development of resistant bacteria. Naturally available medicinal plants were tested to combat some pathogens affecting humans and animals, as they contain a wide range of active substances that can induce biological functions. Currently, medicinal plants are being tested in aquaculture as a safe and eco‐friendly substance to modulate immune status, enhance growth performance and prevent fish disease. Moreover, different parts (e.g. leaf, flower and rhizome) and forms (e.g. crude, extract and active ingredient) of plants are used to modulate specific biological functions (e.g. growth promoter, anti‐stress, immunostimulants, appetite stimulation, antibacteria, anti‐parasite and anti‐virus). Medicinal plants are also used to defend the aquaculture animal from external stressors, such as poor water quality, high environmental temperature and overcrowding. This paper aims to provide information on the role of currently used medicinal plants on aquaculture animals and their action mechanisms. In conclusion, the current review suggested that the utilisation of medicinal plants remained untapped in uncovering the biological activities of active substances against a variety of diseases across diverse species of aquaculture animals.

Litter nitrogen concentration changes mediate effects of drought and plant species richness on litter decomposition - Jiang Wang; Yuan Ge; Johannes H. C. Cornelissen; Xiao-Yan Wang; Song Gao; Yi Bai; Tong Chen; Zhong-Wang Jing; Chong-Bang Zhang; Wen-Li Liu; Jun-Min Li; Fei-Hai Yu (Oecologia, 2022)

Prediction and validation of cross-protective candidate antigen of Hyalomma asiaticum cathepsin L between H. asiaticum and H. anatolicum - Ruiqi Song; Xuejie Zhai; Xinli Fan; Yongchang Li; Huercha; Ting Ge; Caishan Li; Min Li; Wenwen He; Huizhen Zheng; Lu Gan; Yang Zhang; et al. (Experimental and Applied Acarology, 2022)

Providencia heimbachae Associated with Post-weaning Diarrhea in Piglets: Identification, Phenotype, and Pathogenesis - Zhuo Zhang; Lili Zhao; Manman Song; Jilong Luo; Hanghang Liu; Kun Xue; Chengshi Huang; Hongyan Chen; Junwei Ge (Current Microbiology, 2022)

Enhanced nitrogen and phosphorus removal by natural pyrite–based constructed wetland with intermittent aeration - Liya Li; Jingwei Feng; Liu Zhang; Hao Yin; Chunli Fan; Zechun Wang; Menglei Zhao; Chengchang Ge; Hao Song (Environmental Science and Pollution Research, 2021)

Unraveling the multi-scalar residential segregation and socio-spatial differentiation in China: A comparative study based on Nanjing and Hangzhou - Weixuan Song; Qinshi Huang; Yue Gu; Ge He (Journal of Geographical Sciences, 2021)

Isolation of a novel adomavirus from cultured American eels, Anguilla rostrata , with haemorrhagic gill necrosis disease - Jin‐Xian Yang; Xi Chen; Ying‐Ying Li; Tie‐Ying Song; Jun‐Qing Ge (Journal of Fish Diseases, 2021)
Recently, the culture of American eels (Anguilla rostrate) in China has been impacted by emergence of a disease with signs of haemorrhagic gill necrosis. The gills of diseased eels are covered with petecchia and they bleed when the operculum is pressed. In this study, a novel American eel adomavirus (AEAdoV) was isolated from the diseased eels using the eel ovary cell line (EO). The virus proliferated in the EO cells with a maximum TCID 50 /ml of 10 6.29 ± 0.23 at 6 days post‐infection. The virions were non‐enveloped with a diameter of 75–85 nm and shown to be a DNA virus upon 5‐iodo‐2’‐deoxyuridine (IDU) treatment. PCR assays showed that AEAdoV encodes a superfamily 3 helicases (S3H) replicase and shared high similarities with Anguilla marmorata adomavirus (MEAdoV). Although no clinical signs or mortality was observed among the eels injected with AEAdoV, the virus was reisolated from livers, kidneys and gills of injected eels at 35 days post‐injection. Our results suggested that AEAdoV exhibited a latent infection in A. rostrata . The pathogenicity of the AEAdoV needs to be confirmed further.

Energy-based seismic design for self-centering concrete frames - Ge Song; T. Y. Yang; Ying Zhou (Bulletin of Earthquake Engineering, 2021)

Establishment of a visualized isothermal nucleic acid amplification method for on‐site diagnosis of acute hepatopancreatic necrosis disease in shrimp farm - Xiaohan Yang; Yu Dong; Chao Ma; Yi Qiao; Ge Jiang; Shiqi Chen; Jingquan Dong; Hui Shen; Song Gao (Journal of Fish Diseases, 2021)
Acute hepatopancreatic necrosis disease (AHPND) is a significant deadly infectious disease in the shrimp farming industry, causing serious economic losses globally every year. Because of the rapid progress speed, lack of effective treatment and high mortality rate of AHPND, monitoring with frequent diagnostic tests is vital for a successful prevention. The conventional histopathological diagnosis fell far short of the requirement for efficient monitoring, and the polymerase chain reaction (PCR)‐based molecular diagnostic methods that rely on sophisticated thermocycler and trained personnel are hardly applicable in the field. Combining the recombinase polymerase amplification (RPA) and the lateral flow strips (LFSs), a diagnostic method suitable for on‐site everyday monitoring of AHPND has been established in this study. This RPA‐LFS method targeted the binary toxic photorhabdus insect‐related genes PirA and PirB on a virulence plasmid of the AHPND‐causative Vibrio parahaemolyticus strains. The diagnostic test was completed within 30 min at 37°C and showed good specificity and good sensitivity of 20 fg DNA of the AHPND shrimp or one colony‐forming unit of the causative bacterium per reaction, which was better than the administration‐approved standard AP4 assay. Crude templates from sample boiling could be directly used. Tests of clinical samples showed 100% consistency of this method with the standard AP4 assay. This RPA‐LFS method can be a good choice for on‐site diagnosis of AHPND with quick response time, easy procedure and low demand for resources, and should have significant value for the control of spreading of this dangerous disease in farmed shrimp.

Study on the Effect and Mechanism of Water Immersion on the Characteristic Temperature during Coal Low-Temperature Oxidation - Xiaowei Zhai; Bobo Song; Bo Wang; Teng Ma; Hui Ge (Natural Resources Research, 2021)

Precise Control and Experimental Evaluation of a Novel Endoscopic Suturing Device for Large Perforations - Liaoyuan Ai; Chengli Song; Shuchen Ge; Shiju Yan; Lin Mao; Alfred Cuschieri (Journal of Medical and Biological Engineering, 2021)

Biosynthesis and preparation of phycoerythrobilin in recombinant Escherichia coli - Wenjun Li; Chengbo Ma; Baosheng Ge; Fan Zang; Song Qin; Jian Lin (Journal of Applied Phycology, 2021)

Pollution risk assessment of heavy metals in the sediments of upstream Hanjiang River, China - Fengmin Song; Hong-Guang Ge; Hangang Zhao; Zhifeng Liu; Juan Si; Bo Tang (Earth Science Informatics, 2021)

Altered structural and functional connectivity in CSF1R-related leukoencephalopathy - Fei-Xia Zhan; Ze-Yu Zhu; Qing Liu; Hai-Yan Zhou; Xing-Hua Luan; Xiao-Jun Huang; Xiao-Li Liu; Wo-Tu Tian; Shi-Ge Wang; Xiao-Xuan Song; Guang Chen; Ming-Liang Zhao; et al. (Brain Imaging and Behavior, 2021)

Anguillid herpesvirus 1 (AngHV) ORF95 encodes a late, structural envelope protein - Xi Chen; Jin-Xian Yang; Ying-Ying Li; Tie-Ying Song; Jun-Qing Ge (Virus Genes, 2021)

Ring distribution patterns—diversification or speciation? Comparative phylogeography of two small mammals in the mountains surrounding the Sichuan Basin - Yanqun Wang; Anderson Feijó; Jilong Cheng; Lin Xia; Zhixin Wen; Deyan Ge; Jian Sun; Liang Lu; Song Li; Qisen Yang (Molecular Ecology, 2021)
Studying the genetic differentiation in a unique geographical area contributes to understanding the process of speciation. Here, we explore the spatial genetic structure and underlying formation mechanism of two congeneric small mammal species ( Apodemus draco and A. chevrieri ), which are mainly distributed in the mountains surrounding the lowland Sichuan Basin, southwest China. We applied a set of comparative phylogeographical analyses to determine their genetic diversification patterns, combining mitochondrial ( Cytb and COI ) and nuclear (microsatellite loci) markers, with dense sampling throughout the range (411 A . draco from 21 sites and 191 A . chevrieri from 22 sites). Moreover, we performed three complementary statistical methods to investigate the correlation between genotype and geographical and environmental components, and predicted the potential suitable distributional range under the present and historical climate conditions. Our results suggest that both species have experienced allopatric differentiation and admixture in historical periods, resulting in a ring‐shape diversification, under the barrier effect of the Sichuan Basin. We infer that the tectonic events of the Qinghai–Tibetan Plateau and climatic oscillations during the Quaternary played an important role on the genetic divergence of the two species by providing environmental heterogeneity and geographical variation. Our study reveals a case of two sympatric small mammals following a ring‐shaped diversification pattern and provides insight into the process of differentiation.

Adsorption of Nitrate and Ammonium from Water Simultaneously Using Composite Adsorbents Constructed with Functionalized Biochar and Modified Zeolite - Yifei Wang; Xinshan Song; Zhongshuo Xu; Xin Cao; Jing Song; Wei Huang; Xiaoyan Ge; Huaping Wang (Water, Air, & Soil Pollution, 2021)

Projections from D2 Neurons in Different Subregions of Nucleus Accumbens Shell to Ventral Pallidum Play Distinct Roles in Reward and Aversion - Yun Yao; Ge Gao; Kai Liu; Xin Shi; Mingxiu Cheng; Yan Xiong; Sen Song (Neuroscience Bulletin, 2021)

HSV-1 H129-Derived Anterograde Neural Circuit Tracers: Improvements, Production, and Applications - Hong Yang; Feng Xiong; Yi-Ge Song; Hai-Fei Jiang; Hai-Bin Qin; Jing Zhou; Sha Lu; Steven F. Grieco; Xiangmin Xu; Wen-Bo Zeng; Fei Zhao; Min-Hua Luo (Neuroscience Bulletin, 2021)

Efficient photocatalytic degradation of volatile organic compounds over carbon quantum dots decorated Bi2WO6 under visible light - Yangqing Liu; Changjun Zhu; Jingwen Sun; Yan Ge; Fujiao Song; Guanzhong Wang; Qi Xu (Environmental Science and Pollution Research, 2021)

Observation and analysis of morphology abnormalities in development of Oryzias melastigma embryos - Jingjing Song; Haiyi Wu; Kaikai Liu; Wendan Chi; Shanshan Ge; Zhipeng Zhang; Mingqi Wang; Yi Yu; Daode Yu (Journal of Oceanology and Limnology, 2021)

Long-term remote sensing of total suspended matter using Landsat series sensors in Hulun Lake, China - Qiang Wang; Kaishan Song; Zhidan Wen; Yingxin Shang; Sijia Li; Chong Fang; Jia Du; Fangrui Zhao; Ge Liu (International Journal of Remote Sensing, 2021)

Quantitative Determination of Glymphatic Flow Using Spectrophotofluorometry - Yu Zhang; Jian Song; Xu-Zhong He; Jian Xiong; Rong Xue; Jia-Hao Ge; Shi-Yu Lu; Die Hu; Guo-Xing Zhang; Guang-Yin Xu; Lin-Hui Wang (Neuroscience Bulletin, 2020)

Recent Progress in Impacts of Mixing State on Optical Properties of Black Carbon Aerosol - Xiaodong Wei; Yanhong Zhu; Jianlin Hu; Chao Liu; Xinlei Ge; Song Guo; Dantong Liu; Hong Liao; Huijun Wang (Current Pollution Reports, 2020)

Nuclear Factor-κB Pathway Mediates the Molecular Pathogenesis of LMNA-Related Muscular Dystrophies - Yanbin Fan; Dandan Tan; Xu Zhang; Danyu Song; Xingzhi Chang; Shuang Wang; Hui Yan; Lin Ge; Haipo Yang; Carsten Bönnemann; Jingying Liu; Suxia Wang; et al. (Biochemical Genetics, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

What factors determine the mass elevation effect of the Tibetan Plateau? - Fang Han; Li Wan; Hong-zhi Wu; Bai-ping Zhang; Lan Gao; Ge Song (Journal of Mountain Science, 2020)

Low Serum Uric Acid Levels Promote Hypertensive Intracerebral Hemorrhage by Disrupting the Smooth Muscle Cell-Elastin Contractile Unit and Upregulating the Erk1/2-MMP Axis - Ning Xiao; Tian-long Liu; Hao Li; Hao-chen Xu; Jing Ge; Hong-yan Wen; Cong-xia Bai; Li Song; Ying-ying Sun; Yin-hui Zhang; Ru-tai Hui; Wei-hua Song; et al. (Translational Stroke Research, 2020)

Estimating the burden of lung cancer in Canada attributed to occupational radon exposure using a novel exposure assessment method - C. B. Ge; J. Kim; F. Labrèche; E. Heer; C. Song; V. H. Arrandale; M. Pahwa; C. E. Peters; P. A. Demers (International Archives of Occupational and Environmental Health, 2020)
Objective Exposure to radon causes lung cancer. The scope and impact of exposure among Canadian workers have not been assessed. Our study estimated occupational radon exposure in Canada and its associated lung cancer burden. Methods Exposed workers were identified among the working population during the risk exposure period (1961–2001) using data from the Canadian Census and Labour Force Survey. Exposure levels were assigned based on 12,865 workplace radon measurements for indoor workers and assumed to be 1800 mg/m 3 for underground workers. Lung cancer risks were calculated using the Biological Effects of Ionizing Radiation (BEIR) VI exposure-age-concentration model. Population attributable fractions were calculated with Levin’s equation and applied to 2011 Canadian lung cancer statistics. Results Approximately 15.5 million Canadian workers were exposed to radon during the risk exposure period. 79% of exposed workers were exposed to radon levels < 50 Bq/m 3 and 4.8% were exposed to levels > 150 Bq/m 3 . We estimated that 0.8% of lung cancers in Canada were attributable to occupational radon exposure, corresponding to approximately 188 incident lung cancers in 2011. Conclusions The lung cancer burden associated with occupational radon exposure in Canada is small, with the greatest burden occurring among those exposed to low levels of radon.

Experimental Research of Excavation Disturbance Effect Due to Trenchless Construction by Using Distributed Strain Sensing Technique - Yue Li; Ge Song; Jing Cai (Geotechnical and Geological Engineering, 2020)

Fungal Co-infections Associated with Global COVID-19 Pandemic: A Clinical and Diagnostic Perspective from China - Ge Song; Guanzhao Liang; Weida Liu (Mycopathologia, 2020)

Exosomes derived from human exfoliated deciduous teeth ameliorate adult bone loss in mice through promoting osteogenesis - Jizhen Wei; Yeqing Song; Zhihao Du; Feiyan Yu; Yimei Zhang; Nan Jiang; Xuejun Ge (Journal of Molecular Histology, 2020)

Examining two sets of introgression lines across multiple environments reveals background-independent and stably expressed quantitative trait loci of fiber quality in cotton - Yuzhen Shi; Aiying Liu; Junwen Li; Jinfa Zhang; Shaoqi Li; Jinfeng Zhang; Liujun Ma; Rui He; Weiwu Song; Lixue Guo; Quanwei Lu; Xianghui Xiang; et al. (Theoretical and Applied Genetics, 2020)
Key message Background-independent (BI) and stably expressed (SE) quantitative trait loci (QTLs) were identified using two sets of introgression lines across multiple environments. Genetic background more greatly affected fiber quality traits than environmental factors. Sixty-one SE-QTLs, including two BI-QTLs, were novel and 48 SE-QTLs, including seven BI-QTLs, were previously reported. Abstract Cotton fiber quality traits are controlled by QTLs and are susceptible to environmental influence. Fiber quality improvement is an essential goal in cotton breeding but is hindered by limited knowledge of the genetic basis of fiber quality traits. In this study, two sets of introgression lines of Gossypium hirsutum × G. barbadense were used to dissect the QTL stability of three fiber quality traits (fiber length, strength and micronaire) across environments using 551 simple sequence repeat markers selected from our high-density genetic map. A total of 76 and 120 QTLs were detected in the CCRI36 and CCRI45 backgrounds, respectively. Nine BI-QTLs were found, and 78 (41.71%) of the detected QTLs were reported previously. Thirty-nine and 79 QTLs were SE-QTLs in at least two environments in the CCRI36 and CCRI45 backgrounds, respectively. Forty-eight SE-QTLs, including seven BI-QTLs, were confirmed in previous reports, and 61 SE-QTLs, including two BI-QTLs, were considered novel. These results indicate that genetic background more strongly impacts on fiber quality traits than environmental factors. Twenty-three clusters with BI- and/or SE-QTLs were identified, 19 of which harbored favorable alleles from G. barbadense for two or three fiber quality traits. This study is the first report using two sets of introgression lines to identify fiber quality QTLs across environments in cotton, providing insights into the effect of genetic backgrounds and environments on the QTL expression of fiber quality and important information for the genetic basis underlying fiber quality traits toward QTL cloning and molecular breeding.

Interspecific difference in N:P stoichiometric homeostasis drives nutrient release and soil microbial community composition during decomposition - Hanxiong Song; Jingjing Huang; Leming Ge; Changhui Peng; Pengxiang Zhao; Xinyi Guo; Tong Li; Xiaojuan Shen; Qiuan Zhu; Weiguo Liu; Hua Wei; Meng Wang (Plant and Soil, 2020)

Identification of Ala2Thr mutation in insulin gene from a Chinese MODY10 family - Juan Zhang; Yanjun Liu; Ming Li; Xiaoxu Ge; Ying Wang; Xin Huang; Di Yang; Rong Zhang; Yating Chen; Ming Lu; Jun Yin; Mingqiang Song; et al. (Molecular and Cellular Biochemistry, 2020)

Micro-aeration with hollow fiber membrane enhanced the nitrogen removal in constructed wetlands - Xinshan Song; Yufeng Zhao; Yuhui Wang; Zhihao Si; Xiaoyan Ge; Zhijie Gong; Juan Zhou; Xin Cao (Environmental Science and Pollution Research, 2020)

Determination of nitenpyram dissipation and residue in kiwifruit by LC-MS/MS - Shijia Ge; Ye Wang; Qingmei Song; Lingzhu Chen; Yuping Zhang; Deyu Hu (Food Additives & Contaminants: Part A, 2020)

Study on Low-Temperature SCR Denitration Mechanisms of Manganese-Based Catalysts with Different Carriers - Yongfeng Qi; Xiaowei Shan; Meiting Wang; Dandan Hu; Yubao Song; Panle Ge; Jiang Wu (Water, Air, & Soil Pollution, 2020)

Performance-based damage evaluation of hybrid joints - Ying Zhou; Ge Song; Wei Huang (Bulletin of Earthquake Engineering, 2020)

Evaluation of Shear Strength Parameters of Rocks by Preset Angle Shear, Direct Shear and Triaxial Compression Tests - Fengqiang Gong; Song Luo; Ge Lin; Xibing Li (Rock Mechanics and Rock Engineering, 2020)

A novel research on isolation and characterization of Photobacterium damselae subsp . damselae from Pacific white shrimp, Penaeus vannamei , displaying black gill disease cultured in China - Ziyan Wang; Chengyin Shi; Hailiang Wang; Xiaoyuan Wan; Qingli Zhang; Xiaoling Song; Ge Li; Miao Gong; Shigen Ye; Guosi Xie; Jie Huang (Journal of Fish Diseases, 2020)
In June 2019, massive mortalities of cultured Penaeus vannamei occurred in a local farm in Hainan Province, China. The diseased shrimp displayed evident black gills. Three bacterial strains 20190611001, 20190611007 and 20190611022 were isolated from hepatopancreas and gills of the diseased shrimp and identified as Photobacterium damselae subsp. damselae based on the sequence analysis of 16S rRNA and toxR genes. These three isolates showed haemolytic activities. Of them, strain 20190611022 isolated from hepatopancreas was selected and processed for pathogenic analysis. The calculated median lethal dose (LD 50 ) was 9.75 ± 4.29 × 10 5 CFU/g (body weight) by challenging P. vannamei via reverse gavage. The diseased shrimp displayed enlarged hepatopancreatic tubules and sloughing of epithelial cells in tubular lumens. The strain 20190611022 was also characterized by the testing of API 20NE systems and antibiotic susceptibility. The results of disc diffusion test showed that strain 20190611022 was sensitive to chloramphenicol, compound sulfamethoxazole, cefoperazone, ceftriaxone, ceftazidime and cefuroxime. To our knowledge, this is the first report of isolation and characterization of Photobacterium damselae subsp. damselae from natural diseased P. vannamei . Our findings can serve as a basis for further studies of its pathogenicity and provide technological support for disease controlling in shrimp aquaculture.

Evolution of genes and genomes in the genomics era - Song Ge; Ya-Long Guo (Science China Life Sciences, 2020)

Use of Tripterygium wilfordii Hook F for immune-mediated inflammatory diseases: progress and future prospects - Cong-ying Song; Ying-ge Xu; Yuan-qiang Lu (Journal of Zhejiang University-SCIENCE B, 2020)

Disruption of the lactate dehydrogenase and acetate kinase genes in Klebsiella pneumoniae HD79 to enhance 2,3-butanediol production, and related transcriptomics analysis - Jingping Ge; Jiawang Wang; Guangbin Ye; Shanshan Sun; Rui Guo; Gang Song; Wenxiang Ping (Biotechnology Letters, 2020)

Genomic and biological characterization of a pandemic norovirus variant GII.4 Sydney 2012 - Lili Ge; Xuhui Chen; Jinjin Liu; Lijun Zheng; Chongfen Chen; Shuying Luo; Pengbo Guo; Jinghui Kong; Yinsen Song; Yuqi Huo (Virus Genes, 2020)

Biosynthesis of phycocyanobilin in recombinant Escherichia coli - Chengbo Ma; Wenjun Li; Baosheng Ge; Jian Lin; Song Qin (Journal of Oceanology and Limnology, 2020)

Enhanced biomass and lipid production by co-cultivation of Chlorella vulgaris with Mesorhizobium sangaii under nitrogen limitation - Zhijin Wei; Haonan Wang; Xiao Li; Qianqian Zhao; Yonghao Yin; Lijun Xi; Baosheng Ge; Song Qin (Journal of Applied Phycology, 2020)

Assembly of root-associated microbial community of typical rice cultivars in different soil types - Yan Xu; Yi Ge; Jianxiao Song; Christopher Rensing (Biology and Fertility of Soils, 2020)

Metformin prevents against oxidative stress-induced senescence in human periodontal ligament cells - Yunchun Kuang; Bo Hu; Ge Feng; Mingli Xiang; Yuejia Deng; Minmin Tan; Jie Li; Jinlin Song (Biogerontology, 2020)

Methamphetamine-Induced Cognitive Deficits and Psychiatric Symptoms Are Associated with Serum Markers of Liver Damage - Tingting Zhao; Changping Zhai; Hongmei Song; Yanhai Wu; Chuanhui Ge; Yonglin Zhang; Hongxia Xu; Zhengsuo Chi; Hui Chu; Wei Shi; Xiaodong Cheng; Xin Li; et al. (Neurotoxicity Research, 2020)

Angiotensin II induces apoptosis of cardiac microvascular endothelial cells via regulating PTP1B/PI3K/Akt pathway - Yanyan Wang; Yuyuan Fan; Yu Song; Xueting Han; Mingqiang Fu; Jingfeng Wang; Xiaotong Cui; Juan Cao; Li Chen; Kai Hu; Aijun Sun; Jingmin Zhou; et al. (In Vitro Cellular & Developmental Biology - Animal, 2019)

Genomic characterization of a novel astrovirus identified in Amur tigers from a zoo in China - Hui-Hui Zhang; Qi-Guan Qiu; Shu-Jing Liu; Wen-Qin Hu; Jie-Yu Li; Tian-Ning Liu; You-Song Peng; Xing-Yi Ge; Chao-Ting Xiao (Archives of Virology, 2019)

Natural Frequency Characteristics of Rock Masses Containing a Complex Geological Structure and Their Effects on the Dynamic Stability of Slopes - Danqing Song; Ailan Che; Renjie Zhu; Xiurun Ge (Rock Mechanics and Rock Engineering, 2019)

Morphological characters and molecular data reveal three new species of Fomitopsis (Basidiomycota) - Shun Liu; Chang-Ge Song; Bao-Kai Cui (Mycological Progress, 2019)

Burden of non-melanoma skin cancer attributable to occupational sun exposure in Canada - Cheryl E. Peters; J. Kim; C. Song; E. Heer; V. H. Arrandale; M. Pahwa; F. Labrèche; C. B. McLeod; H. W. Davies; C. B. Ge; P. A. Demers (International Archives of Occupational and Environmental Health, 2019)

Investigation of low-temperature selective catalytic reduction of NOx with ammonia over Cr-promoted Fe/AC catalysts - Tingting Ge; Baozhong Zhu; Yunlan Sun; Weiyi Song; Qilong Fang; Yuxiu Zhong (Environmental Science and Pollution Research, 2019)

Estimation of Kd(PAR) in inland waters across China in relation to the light absorption of optically active components - Zhidan Wen; Kaishan Song; Chong Fang; Qian Yang; Ge Liu; Yingxin Shang; Xiaodi Wang (Environmental Science and Pollution Research, 2019)

Choline, not folate, can attenuate the teratogenic effects ofdibutyl phthalate (DBP) during early chick embryo development - Rui Wang; Da-Guang Sun; Ge Song; Chun Yi Guan; Yi Cui; Xu Ma; Hong-Fei Xia (Environmental Science and Pollution Research, 2019)

Associations of brain entropy (BEN) to cerebral blood flow and fractional amplitude of low-frequency fluctuations in the resting brain - Donghui Song; Da Chang; Jian Zhang; Qiu Ge; Yu-Feng Zang; Ze Wang (Brain Imaging and Behavior, 2019)

Protective effects of Ganoderma lucidum triterpenoids on oxidative stress and apoptosis in the spleen of chickens induced by cadmium - Xiangqi Teng; Weiqian Zhang; Yangyang Song; Haibin Wang; Ming Ge; Ruili Zhang (Environmental Science and Pollution Research, 2019)

Is phosphorus a limiting factor to regulate the growth of phytoplankton in Daya Bay, northern South China Sea: a mesocosm experiment - Xingyu Song; Meiting Tan; Ge Xu; Xinying Su; Jihua Liu; Gaungyan Ni; Yao Li; Yehui Tan; Liangmin Huang; Pingping Shen; Gang Li (Ecotoxicology, 2019)

Whole RNA-sequencing and gene expression analysis of Trichoderma harzianum Tr-92 under chlamydospore-producing condition - Min Yuan; Yuanyuan Huang; Zhenhua Jia; Weina Ge; Lan Zhang; Qian Zhao; Shuishan Song; Yali Huang (Genes & Genomics, 2019)

Synthesis and antitumor activity of cyclic octapeptide, samoamide A, and its derivatives - Fei Ge; Chi Zhang; Longbao Zhu; Wanzhen Li; Ping Song; Yugui Tao; Guocheng Du (Medicinal Chemistry Research, 2019)

Fabrication of Fluorescence Turn-off-on Sensor Based on g-C3N4 Quantum Dots and MgFe Layered Double Hydroxide for the Detection of Citrate - Qiao Cheng; Xinyi Liu; Yu He; Yili Ge; Jiangang Zhou; Gongwu Song (Journal of Fluorescence, 2019)

Genetic and epigenetic alterations in hybrid and derived hexaploids between Brassica napus and B. oleracea revealed by SSR and MSAP analysis - Qinfei Li; Kusum Rana; Zhiyong Xiong; Xianhong Ge; Zaiyun Li; Hongyuan Song; Wei Qian (Acta Physiologiae Plantarum, 2019)

Two new Neofomitella species (Polyporaceae, Basidiomycota) based on morphological and molecular evidence - Xing Ji; Dong-Mei Wu; Chang-Ge Song; Shun Liu; Jing Si; Bao-Kai Cui (Mycological Progress, 2019)

Agricultural Development and Implication for Wetlands Sustainability: A Case from Baoqing County, Northeast China - Chong Fang; Zhidan Wen; Lin Li; Jia Du; Ge Liu; Xiaodi Wang; Kaishan Song (Chinese Geographical Science, 2019)

Fish assemblage structure in relation to seasonal environmental variation in sub‐lakes of the Poyang Lake floodplain, China - Bin‐Song Jin; Kirk O. Winemiller; Bo Shao; Ji‐Ke Si; Jie‐Feng Jin; Gang Ge (Fisheries Management and Ecology, 2019)
The Yangtze River and its watershed have undergone vast changes resulting from centuries of human impacts, yet ecological knowledge of the system is limited. The seasonal variation and spatial variation of three sub‐lakes of Poyang Lake, a huge wetland in the middle Yangtze Basin, were investigated to examine how fish assemblages respond to seasonal hydrology and associated environmental conditions. In all three sub‐lakes, fish assemblage structure revealed strong variations associated with seasonal water level fluctuation. Fish species richness in all sub‐lakes was highest during the middle of the monsoon season and lowest during the dry season. Fish numerical abundance and biomass varied significantly, with several of the most common species having inconsistent patterns of seasonal variation among sub‐lakes. Fish assemblage structure was significantly associated with environmental gradients defined by water level, aquatic macrophyte coverage, conductivity and dissolved oxygen concentration. Assemblage composition in all three sub‐lakes underwent strongest shifts between December and April, the period when water levels were lowest and fishing has the greatest impact on fish stocks. Future impacts that change the hydrology of the middle Yangtze would alter the dynamics of habitat connectivity and affect environmental conditions and fish assemblages of the Poyang Lake wetland system.

Relationships between body weight and other morphological traits in young sea cucumbers Apostichopus japonicas - Yaoyao Zhan; Weijie Zhang; Chen Ge; Kai Lin; Guang Li; Jian Song; Yaqing Chang (Journal of Oceanology and Limnology, 2019)

Suboptimal health status as an independent risk factor for type 2 diabetes mellitus in a community-based cohort: the China suboptimal health cohort study - Siqi Ge; Xizhu Xu; Jie Zhang; Haifeng Hou; Hao Wang; Di Liu; Xiaoyu Zhang; Manshu Song; Dong Li; Yong Zhou; Youxin Wang; Wei Wang (EPMA Journal, 2019)

Fractal dimension analysis for seismicity spatial and temporal distribution in the circum-Pacific seismic belt - Lirong Yin; Xiaolu Li; Wenfeng Zheng; Zhengtong Yin; Lihong Song; Lijun Ge; Qingchuan Zeng (Journal of Earth System Science, 2019)

Protective Effect of Ganoderma Triterpenoids on Cadmium-Induced Testicular Toxicity in Chickens - Hongmei Wang; Ruili Zhang; Yangyang Song; Tianqi Li; Ming Ge (Biological Trace Element Research, 2019)

The role of formation of pyrrole–ATP synthase subunit beta adduct in pyrrolizidine alkaloid-induced hepatotoxicity - Yao Lu; Jiang Ma; Zijing Song; Yang Ye; Peter P. Fu; Ge Lin (Archives of Toxicology, 2018)

NbGIS regulates glandular trichome initiation through GA signaling in tobacco - Yihua Liu; Dongdong Liu; Ali Raza Khan; Bohan Liu; Minjie Wu; Linli Huang; Junyu Wu; Ge Song; Hongwei Ni; Haiming Ying; Hao Yu; Yinbo Gan (Plant Molecular Biology, 2018)

Protective Effect of Agaricus blazei Polysaccharide Against Cadmium-Induced Damage on the Testis of Chicken - Yangyang Song; Ruili Zhang; Hongmei Wang; Yan Yan; Ge Ming (Biological Trace Element Research, 2018)

Nitrogen Budget in Recirculating Aquaculture and Water Exchange Systems for Culturing Litopenaeus vannamei - Zhao Chen; Hongxing Ge; Zhiqiang Chang; Xiefa Song; Fazhen Zhao; Jian Li (Journal of Ocean University of China, 2018)

Dynamic response characteristics of a rock slope with discontinuous joints under the combined action of earthquakes and rapid water drawdown - Danqing Song; Ailan Che; Renjie Zhu; Xiurun Ge (Landslides, 2018)

Recent advances in enhanced enzyme activity, thermostability and secretion by N-glycosylation regulation in yeast - Fei Ge; Longbao Zhu; Anna Aang; Ping Song; Wanzhen Li; Yugui Tao; Guocheng Du (Biotechnology Letters, 2018)

Two new species of Pustula (Albuginales, Oomycota) from Junggar Basin in China based on morphology and molecular data - Biao Xu; Young Joon Choi; Jia Ge Song; Shan He Zhang; Ping Gen Xi; Hyeon Dong Shin; Zi De Jiang (Mycological Progress, 2018)

Effect of temperature on development and reproduction of the carmine spider mite, Tetranychus cinnabarinus (Acari: Tetranychiae), fed on cassava leaves - Zhiwen Zou; Jianfei Xi; Ge Liu; Shuxian Song; Tianrong Xin; Bin Xia (Experimental and Applied Acarology, 2018)

Lead-induced changes of cytoskeletal protein is involved in the pathological basis in mice brain - Yaming Ge; Lingli Chen; Xianghe Sun; Zhihong Yin; Xiaochao Song; Chong Li; Junwei Liu; Zhixing An; Xuefeng Yang; Hongmei Ning (Environmental Science and Pollution Research, 2018)

Phthalate esters in surface water of Songhua River watershed associated with land use types, Northeast China - Zhidan Wen; Xiaoli Huang; Dawen Gao; Ge Liu; Chong Fang; Yingxin Shang; Jia Du; Ying Zhao; Lili Lv; Kaishan Song (Environmental Science and Pollution Research, 2018)

Functional analysis of spinach CONSTITUTIVE EXPRESSOR OF PATHOGENESIS-RELATED GENES5 (SoCPR5) in plant immunity - Teng Song; Yuxia Lou; Chenxi Xu; Xiaofeng Cai; Xiaoli Wang; Huimin Ma; Tianhua Wang; Jianjian Zhou; Chenhui Ge; Quanhua Wang; Shui Wang (European Journal of Plant Pathology, 2018)

A WTLS-based rational function model for orthorectification of remote-sensing imagery - Yong Ge; Yongzhao Wei; Yongze Song; Tianjun Wu; Alfred Stein; Xian Guo; Chenghu Zhou; Jianghong Ma (International Journal of Remote Sensing, 2017)

Monoclonal antibody-based serological assays for detection of Potato virus S in potato plants - Ge Song; Jia-yu Wu; Yan Xie; Yong Liu; Ya-juan Qian; Xue-ping Zhou; Jian-xiang Wu (Journal of Zhejiang University-SCIENCE B, 2017)

Aberrant Axonal Arborization of PDF Neurons Induced by Aβ42-Mediated JNK Activation Underlies Sleep Disturbance in an Alzheimer’s Model - Qian Song; Ge Feng; Zehua Huang; Xiaoman Chen; Zhaohuan Chen; Yong Ping (Molecular Neurobiology, 2017)

Mechanical Response Analysis of Airport Flexible Pavement Above Underground Infrastructure Under Moving Wheel Load - Yue Li; Ge Song; Jing Cai (Geotechnical and Geological Engineering, 2017)

Synthesis of ternary rGO–ZnO–Fe3O4 nanocomposites and their application for visible light photocatalytic degradation of dyes - Jiaqi You; Ying Xiang; Yili Ge; Yu He; Gongwu Song (Clean Technologies and Environmental Policy, 2017)

Phenotypic Variation and Genetic Diversity in the Collections of Erianthus Arundinaceus (Retz.) Jesw. - Xi-Hui Liu; Huan-Zhong Song; Ge-Min Zhang; Wei-Xing Duan; Rong-Hua Zhang; Yang-Rui Li (Sugar Tech, 2017)

Fluorescence Detection of p-Nitrophenol in Water Using Bovine Serum Albumin Capped ag Nanoclusters - Mi Mao; Chun Deng; Yu He; Yili Ge; Gongwu Song (Journal of Fluorescence, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

“Turn-Off-On” Fluorescence Switching of Ascorbic Acid-Reductive Silver Nanoclusters: a Sensor for Ascorbic Acid and Arginine in Biological Fluids - Na Li; Yu He; Yili Ge; Gongwu Song (Journal of Fluorescence, 2017)

Fluorescent Detection of Phosphate in Aqueous Solution Based on Near Infrared Emission Ag2S QDs/Metal − Organic Shell Composite - Dan Yan; Yu He; Yili Ge; Gongwu Song (Journal of Fluorescence, 2017)

Characteristics and sources of atmospheric composition based on precipitation chemistry in the Shiyang River Basin, Northwestern China - Li Zong-Jie; Song Ling-Ling; Tian Qing; Li Yong-ge (Arabian Journal of Geosciences, 2017)

Genome-wide identification and functional analysis of the TIFY gene family in response to drought in cotton - Ge Zhao; Yun Song; Caixiang Wang; Hamama Islam Butt; Qianhua Wang; Chaojun Zhang; Zuoren Yang; Zhao Liu; Eryong Chen; Xueyan Zhang; Fuguang Li (Molecular Genetics and Genomics, 2016)

Measuring the spatiotemporal variation and evolution of transport network of China’s megaregions - Ge Song; Jiawen Yang (Journal of Geographical Sciences, 2016)

Sensitive Naked Eye and Autofluorescence Detection of Cu2+ in Biological Fluids by Polyethyleneimine Microspheres - Dan Yan; Chun Deng; Yu He; Yili Ge; Gongwu Song (Journal of Fluorescence, 2016)

High-level expression of a novel recombinant human plasminogen activator (rhPA) in the milk of transgenic rabbits and its thrombolytic bioactivity in vitro - Shaozheng Song; Xin Ge; Yaobin Cheng; Rui Lu; Ting Zhang; Baoli Yu; Xueqiao Ji; Zhengqiang Qi; Yao Rong; Yuguo Yuan; Yong Cheng (Molecular Biology Reports, 2016)

Enhanced Neuroprotection of Acetyl-11-Keto-β-Boswellic Acid (AKBA)-Loaded O-Carboxymethyl Chitosan Nanoparticles Through Antioxidant and Anti-Inflammatory Pathways - Yi Ding; Youbei Qiao; Min Wang; Huinan Zhang; Liang Li; Yikai Zhang; Jie Ge; Ying Song; Yuwen Li; Aidong Wen (Molecular Neurobiology, 2016)

Effects of fish meal replacement by soybean peptide on growth performance, digestive enzyme activities, and immune responses of yellow catfish Pelteobagrus fulvidraco - Zhen-xin Zhao; Chang-you Song; Jun Xie; Xian-ping Ge; Bo Liu; Si-lei Xia; Shun Yang; Qing Wang; Sai-hua Zhu (Fisheries Science, 2016)

The Oldest Cranium of Sinomastodon (Proboscidea, Gomphotheriidae), Discovered in the Uppermost Miocene of Southwestern China: Implications for the Origin and Migration of This Taxon - Shi-Qi Wang; Xue-Ping Ji; Nina G. Jablonski; Denise F. Su; Jun-Yi Ge; Chang-Fen Ding; Teng-Song Yu; Wen-Qi Li; Jaroon Duangkrayom (Journal of Mammalian Evolution, 2016)

Curcumin Affects Phase II Disposition of Resveratrol Through Inhibiting Efflux Transporters MRP2 and BCRP - Shufan Ge; Taijun Yin; Beibei Xu; Song Gao; Ming Hu (Pharmaceutical Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Up-regulation of PSMB4 is associated with neuronal apoptosis after neuroinflammation induced by lipopolysaccharide - Jiansheng Shi; Xiaorong Liu; Changde Xu; Jianbin Ge; Jianbing Ren; Jun Wang; Xinjian Song; Shirong Dai; Weidong Tao; Hongjian Lu (Journal of Molecular Histology, 2015)

Biotransformation of 20(S)-protopanaxatriol by Mucor racemosus and the anti-cancer activities of some products - Guangtong Chen; Hongjuan Ge; Yan Song; Jianlin Li; Xuguang Zhai; Juanjuan Wu; Xiang Ling (Biotechnology Letters, 2015)

Population genetic structure of Oryza rufipogon and Oryza nivara : implications for the origin of O. nivara - Rong Liu; Xiao‐Ming Zheng; Lian Zhou; Hai‐Fei Zhou; Song Ge (Molecular Ecology, 2015)
Ecological speciation plays a primary role in driving species divergence and adaptation. Oryza rufipogon and Oryza nivara are two incipient species at the early stage of speciation with distinct differences in morphology, life history traits and habitat preference, and therefore provide a unique model for the study of ecological speciation. However, the population genetic structure of the ancestral O. rufipogon has been controversial despite substantial study, and the origin of the derivative O. nivara remains unclear. Here, based on sequences of 10 nuclear and two chloroplast loci from 26 wild populations across the entire geographic ranges of the two species, we conducted comprehensive analyses using population genetics, phylogeography and species distribution modelling ( SDM ) approaches. In addition to supporting the two previously reported major subdivisions, we detected four genetically distinct groups within O. rufipogon and found no correlation between the genetic groups and either species identity or geographical regions. The SDM clearly showed substantial change in the distribution range of O. rufipogon in history, demonstrating that the repeated extinction and colonization of local populations due to multiple glacial–interglacial cycles during the Quaternary was most likely the main factor shaping the confounding population genetic structure of O. rufipogon . Moreover, we found significant differences between the two species in climate preferences, suggestive of an important role for climatic factors in the adaptation, persistence and expansion of O. nivara . Finally, based on the genetic pattern and dynamics of the O. nivara populations, we hypothesize that O. nivara might have independently originated multiple times from different O. rufipogon populations.

Enhanced Phytoextraction of Heavy Metals from Contaminated Soil by Plant Co-cropping Associated with PGPR - Zhi-feng Liu; Hong-guang Ge; Chen Li; Zuo-ping Zhao; Feng-min Song; Shi-bin Hu (Water, Air, & Soil Pollution, 2015)

Treatment of turtle aquaculture effluent by an improved multi-soil-layer system - Ying Song; Yu-ting Huang; Hong-fang Ji; Xin-jun Nie; Zhi-yuan Zhang; Chuan Ge; An-cheng Luo; Xin Chen (Journal of Zhejiang University-SCIENCE B, 2015)

Microbial transformation of 20(S)-protopanaxatriol by Mucor spinosus - Xue Yang; Hongjuan Ge; Yan Song; Jianlin Li; Guangtong Chen (Biotechnology Letters, 2015)

Snail regulated by PKC/GSK-3β pathway is crucial for EGF-induced epithelial-mesenchymal transition (EMT) of cancer cells - Zong-cai Liu; Xiao-hui Chen; Hai-xing Song; Hong-sheng Wang; Ge Zhang; Hao Wang; Dan-yang Chen; Rui Fang; Hao Liu; Shao-hui Cai; Jun Du (Cell and Tissue Research, 2014)

Detection and sequence analysis of two novel co-infecting double-strand RNA mycoviruses in Ustilaginoidea virens - Jie Zhong; Xiang Hua Lei; Jun Zi Zhu; Ge Song; Ya Dong Zhang; Yi Chen; Bi Da Gao (Archives of Virology, 2014)

Glial Cell-Derived Neurotrophic Factor Attenuates Neuropathic Pain in a Mouse Model of Chronic Constriction Injury: Possible Involvement of E-cadherin/p120ctn Signaling - Cunjin Wang; Hongjun Wang; Jun Pang; Li Li; Suming Zhang; Ge Song; Na Li; Junping Cao; Licai Zhang (Journal of Molecular Neuroscience, 2014)

A DEAD-box RNA helicase produces two forms of transcript that differentially respond to cold stress in a cryophyte (Chorispora bungeana) - Yu Yang; Zhenglong Sun; Chenchen Ding; Linna Ge; Likun Sun; Muqun Bai; Yuan Song; Shuyan Chen; Lizhe An (Planta, 2014)

NCAM Signaling Mediates the Effects of GDNF on Chronic Morphine-Induced Neuroadaptations - Li Li; Junping Cao; Suming Zhang; Cunjin Wang; Jinfeng Wang; Ge Song; Hongjun Wang; Licai Zhang (Journal of Molecular Neuroscience, 2014)

A field study of the relationship between sulfide-bound metals and bioaccumulation by Limnodrilus sp. in a heavily polluted river - Feng Li; Xiang-yun Zeng; Yun-jun Yu; Chang-hua Wu; Ge Mai; Wei-wei Song; Yan-mao Wen; Zhi-peng Duan; Jia-yu Yang (Environmental Monitoring and Assessment, 2014)

Microarray analysis of differentially expressed genes engaged in fruit development between table and wine grape - Xicheng Wang; Emrul Kayesh; Jian Han; Chonghuai Liu; Chen Wang; Changnian Song; Anjing Ge; Jinggui Fang (Molecular Biology Reports, 2014)

The comparison of sensitivity of motion sickness between retinal degeneration fast mice and normal mice - Xiao-Cheng Wang; Zhao-Hui Shi; Ka Bian; Lei Zhang; Jun-Hui Xue; Guo-Qing Yang; Xue-Song Ge; Zuo-Ming Zhang (Journal of Comparative Physiology A, 2014)

Isolation, Culture, and Identification of Amniotic Fluid-Derived Mesenchymal Stem Cells - Xuetao Fei; Shan Jiang; Song Zhang; Yigang Li; Junbo Ge; Ben He; Steven Goldstein; George Ruiz (Cell Biochemistry and Biophysics, 2013)

Molecular basis for insecticide‐enhanced thermotolerance in the brown planthopper N ilaparvata lugens S tål ( H emiptera: D elphacidae) - Lin‐Quan Ge; Liu‐Juan Huang; Guo‐Qin Yang; Qi‐Sheng Song; David Stanley; G. M. Gurr; Jin‐Cai Wu (Molecular Ecology, 2013)
Climate change is likely to have marked ecological effects on terrestrial ecosystems, including the activities of insect pests. Most attention has focused on the increasing geographical ranges of pests; however, if extrinsic factors enhance their thermotolerance, populations may express increased voltinism and longer daily and annual activity periods. These changes in pest populations have the potential for severe consequences, including increased crop losses and decreased food security at the global level. The brown planthopper ( BPH ) Nilaparvata lugens Stål (Hemiptera: Delphacidae) is a serious pest of rice crops in temperate and tropical regions of Asia. It is often present in rice microclimates at temperatures close to its maximum thermotolerance. Recent BPH outbreaks in tropical Asia are considered to be associated with excess use of pesticides and increasing temperature. This study tested whether exposure to sublethal concentrations of triazophos (tzp), an insecticide widely used in Asian rice production, enhances thermotolerance of BPH . Tzp exposure (40 ppm at 40 °C) significantly decreased mortality (from 94% in controls to 50% at 48 h post‐treatment) and increased lethal mean time ( LT 50 ) of adults by 17.2 h. To investigate the underlying molecular mechanism of this tzp‐enhanced thermotolerance, we selected Hsp70 and Arginine kinase (Argk) for detailed study. Transcripts encoding both proteins in third‐instar nymphs and brachypterous adult females were up‐regulated, compared with controls, after exposure to tzp. RNA i silencing of both genes demonstrated that Hsp70 and Argk are essential for survival and tzp‐increased thermotolerance. We propose that tzp induces thermotolerance in BPH s by increasing the expression of genes that act in cell protection mechanisms. The significance of our proposal relates to the importance of understanding the influence of sublethal concentrations of insecticides on pest biology. In addition to its influence on thermotolerance, tzp also enhances BPH reproduction. We infer that exposure to a pesticide stressor can produce cross‐tolerance, that is, increased tolerance to one stressor also increases tolerance to other stressors, including temperature. Aside from needing a better understanding of these effects in nature and in other pest/cropping systems, we suggest that pest management programmes can be improved with better understanding of the influences of stressors, including increased environmental temperatures and sublethal concentrations of insecticides, on pest biology.

An integrated East China Sea–Changjiang Estuary model system with aim at resolving multi-scale regional–shelf–estuarine dynamics - Jianzhong Ge; Pingxing Ding; Changsheng Chen; Song Hu; Gui Fu; Lunyu Wu (Ocean Dynamics, 2013)

Decreased expression of the DBC2 gene and its clinicopathological significance in breast cancer: correlation with aberrant DNA methylation - Linlin Han; Lin Hou; Jinlian Song; Dongliang Lin; Li Wu; Yinlin Ge; Zhongliang Ma (Biotechnology Letters, 2013)

Combinational biosynthesis of phycocyanobilin using genetically-engineered Escherichia coli - Baosheng Ge; Yan Li; Haixiang Sun; Shuai Zhang; Peijie Hu; Song Qin; Fang Huang (Biotechnology Letters, 2013)

Characteristics, causes and mitigation of catastrophic debris flow hazard on 21 July 2011 at the Longda Watershed of Songpan County, China - Yong-gang Ge; Peng Cui; Xiao-jun Guo; Guo-hu Song; Wei-ming Liu (Journal of Mountain Science, 2013)

The Effect of c-fos on Acute Myocardial Infarction and the Significance of Metoprolol Intervention in a Rat Model - Song Zhang; Meiqi Zhang; Steven Goldstein; Yigang Li; Junbo Ge; Ben He; George Ruiz (Cell Biochemistry and Biophysics, 2013)

The Evolution and Paleobiogeography of Flying Squirrels (Sciuridae, Pteromyini) in Response to Global Environmental Change - Xuefei Lu; Deyan Ge; Lin Xia; Zhaoqun Zhang; Song Li; Qisen Yang (Evolutionary Biology, 2013)

Seasonal migration by a large forest ungulate: a study on takin (Budorcas taxicolor) in Sichuan Province, China - Tian-Pei Guan; Bao-Ming Ge; William J. McShea; Sheng Li; Yan-Ling Song; Chad M. Stewart (European Journal of Wildlife Research, 2013)

Molecular characterization and phylogenetic analysis of porcine epidemic diarrhea virus (PEDV) samples from field cases in Fujian, China - Xi Chen; Jinxian Yang; Fusong Yu; Junqing Ge; Tianlong Lin; Tieying Song (Virus Genes, 2012)

Isolation of yellow catfish β-actin promoter and generation of transgenic yellow catfish expressing enhanced yellow fluorescent protein - Jiachun Ge; Zhangji Dong; Jingyun Li; Zhiqiang Xu; Wei Song; Jie Bao; Dong Liang; Junbo Li; Kui Li; Wenshuang Jia; Muzi Zhao; Yongxiang Cai; et al. (Transgenic Research, 2012)

Sixteen microsatellite markers developed from Bretschneidera sinensis (Bretschneideraceae) - Bi-Cai Guan; Guang-Rong Song; Gang Ge (Conservation Genetics Resources, 2012)

A new approach to estimating the T-year return-period wave height - Jun Zhang; Wenpeng Song; Yong Ge (Journal of Ocean University of China, 2011)

Genetic diversity and domestication history of African rice (Oryza glaberrima) as inferred from multiple gene sequences - Zhi-Ming Li; Xiao-Ming Zheng; Song Ge (Theoretical and Applied Genetics, 2011)

A mutant of infectious Asia 1 serotype foot-and-mouth disease virus with the deletion of 10-amino-acid in the 3A protein - Shuang Li; Mingchun Gao; Runxiang Zhang; Ge Song; Jun Song; Dandan Liu; Yongsheng Cao; Tingting Li; Bo Ma; Xiangtao Liu; Junwei Wang (Virus Genes, 2010)

Genome duplication effects on pollen development and the interrelated physiological substances in tetraploid rice with polyploid meiosis stability - Yuchi He; Qiong Wei; Jie Ge; Aiming Jiang; Lu Gan; Zhaojian Song; Detian Cai (Planta, 2010)

Detrital zircon and apatite fission track data in the Liaoxi basins: Implication to Meso-Cenozoic thermo-tectonic evolution of the northern margin of the North China Craton - Yi Yan; Xiaoqiong Hu; Ge Lin; Weiliang Liu; Zhengjiang Song (Journal of Earth System Science, 2010)

Ecological divergence in the presence of gene flow in two closely related Oryza species (Oryza rufipogon and O. nivara) - XIAO-MING ZHENG; SONG GE (Molecular Ecology, 2010)

Cholinergic neuronal differentiation of bone marrow mesenchymal stem cells in rhesus monkeys - Ying Qi; FengYan Zhang; Ge Song; XueRong Sun; RuZhang Jiang; MengFei Chen; Jian Ge (Science China Life Sciences, 2010)

In vitro synergistic activity between 8-methoxypsoralen and ethambutol, isoniazid, and rifampin when used in combination against Mycobacterium tuberculosis - Fa Ge; Fanli Zeng; Na Guo; Junwen Fan; Yu Song; Siguo Liu; Xiuping Wu; Xuelin Wang; Xuming Deng; Qi Jin; Lu Yu (World Journal of Microbiology and Biotechnology, 2010)

Analysis of the genetic diversity in Saccharum spontaneum L. accessions from Guangxi Province of China with RAPD-PCR - Ge-min Zhang; Yang-Rui Li; Wei-Zhong He; Hong He; Xi-Hui Liu; Huan-Zhong Song; Hai-Bin Liu; Ru-Cai Zhu; Wei-Kuan Fang (Sugar Tech, 2010)

Foraging Response of Turkish Honey Bee Subspecies to Flower Color Choices and Reward Consistency - Ibrahim Cakmak; Daniel S. Song; T. Andrew Mixson; Eduardo Serrano; Meredith L. Clement; Amy Savitski; Ge’Andra Johnson; Tugrul Giray; Charles I. Abramson; John F. Barthell; Harrington Wells (Journal of Insect Behavior, 2010)

Molecular evidence for glacial expansion and interglacial retreat during Quaternary climatic changes in a montane temperate pine (Pinus kwangtungensis Chun ex Tsiang) in southern China - Shuang Tian; Jordi López-Pujol; Hong-Wei Wang; Song Ge; Zhi-Yong Zhang (Plant Systematics and Evolution, 2010)

HRGD: a database for mining potential heterosis-related genes in plants - Shuhui Song; Yuefeng Huang; Xuan Wang; Gang Wei; Hongzhu Qu; Weiwei Wang; Xiaomeng Ge; Songnian Hu; Guozhen Liu; Yanchun Liang; Jun Yu (Plant Molecular Biology, 2009)

Contrasting population genetic structure and gene flow between Oryza rufipogon and Oryza nivara - Hai-Fei Zhou; Xiao-Ming Zheng; Ruo-Xun Wei; Gerard Second; Duncan A. Vaughan; Song Ge (Theoretical and Applied Genetics, 2008)

Molecular Evolution and Phylogenetic Utility of the Internal Transcribed Spacer 2 (ITS2) in Calyptratae (Diptera: Brachycera) - Zhong-kui Song; Xun-zhang Wang; Ge-qiu Liang (Journal of Molecular Evolution, 2008)

No Correlation Between Heterozygosity and Vegetative Fitness in the Narrow Endemic and Critically Endangered Clematis acerifolia (Ranunculaceae) - Jordi López-Pujol; Fu-Min Zhang; Song Ge (Biochemical Genetics, 2008)

Combinational biosynthesis of a fluorescent cyanobacterial holo-α-allophycocyanin in Escherichia coli - Yu Yang; Baosheng Ge; Xiangyu Guan; Weijie Zhang; Song Qin (Biotechnology Letters, 2008)

A preliminary study on population genetic structure and phylogeography of the wild and cultivated Zizania latifolia (Poaceae) based on Adh1a sequences - Xin-wei Xu; Wei-dong Ke; Xiao-ping Yu; Jun Wen; Song Ge (Theoretical and Applied Genetics, 2008)

Chloroplast phylogeography of Dipentodon (Dipentodontaceae) in southwest China and northern Vietnam - QING‐JUN YUAN; ZHI‐YONG ZHANG; HUA PENG; SONG GE (Molecular Ecology, 2008)
The evolutionary history of plants in the southeast Tibetan Plateau might be the most complicated around the world because of the area's extremely complex topography and climate induced by strong tectonic activity in recent history. In this research, we implemented a phylogeographical study using chloroplast sequences ( psb A‐ trn H and trn Q‐ rps 16 intergenic spacer) on Dipentodon , a monotypic or ditypic genus ( D. sinicus and D. longipedicellatus ) distributed in southwest China and adjacent areas including Myanmar (Burma), northeast India and northern Vietnam. A total of 257 samples from 16 populations from the southeast Tibetan Plateau ( D. longipedicellatus ) and the Yungui Plateau ( D. sinicus ) were collected. The results revealed that Dipentodon had 11 haplotypes for the two intergenic spacers, high genetic diversity ( h T = 0.902) and high genetic differentiation ( N ST = 0.987 and G ST = 0.948). amova analysis showed that the component of among‐population within region/species (55.25%) was unexpectedly larger than the among‐species/region component (43.69%), which indicates that there is no justification for recognizing two species in Dipentodon . Correlation of pairwise genetic and geographical distances showed that Dipentodon populations in the southeast Tibetan Plateau may have suffered more habitat fragmentation than populations in the Yungui Plateau because of the uplift of the Tibetan Plateau than populations in the Yungui Plateau have. Nested clade analysis showed that 11 haplotypes formed two 3‐level, three 2‐level and seven 1‐level clades, with eight clades showing significant geographical association. However, clade 2‐1 and 2‐2 did not cluster together, although they are distributed in the same region (Yungui Plateau) and belong to the same species ( D. sinicus ). This led not only to incongruence between haplotype network and geographical distribution of 2‐level clades, but also to paraphyly of D. sinicus to D. longipedicellatus . We concluded that the incongruence and paraphyly may result from incomplete lineage sorting during the rapid and extreme tectonic events of the Tibetan Plateau. The results reported here will no doubt provide new insights into the evolution of biodiversity on the Tibetan Plateau and adjacent areas, and a historical framework for the conservation of biodiversity in this area, including Dipentodon .

Plant Biodiversity in China: Richly Varied, Endangered, and in Need of Conservation - Jordi López-Pujol; Fu-Min Zhang; Song Ge (Biodiversity and Conservation, 2006)

Phylogeography of the endangered Cathaya argyrophylla (Pinaceae) inferred from sequence variation of mitochondrial and nuclear DNA - HONG‐WEI WANG; SONG GE (Molecular Ecology, 2006)
Cathaya argyrophylla is an endangered conifer restricted to subtropical mountains of China. To study phylogeographical pattern and demographic history of C . argyrophylla , species‐wide genetic variation was investigated using sequences of maternally inherited mtDNA and biparentally inherited nuclear DNA. Of 15 populations sampled from all four distinct regions, only three mitotypes were detected at two loci, without single region having a mixed composition ( G ST = 1). Average nucleotide diversity (θ ws = 0.0024; π s = 0.0029) across eight nuclear loci is significantly lower than those found for other conifers (θ ws = 0.003∼0.015; π s = 0.002∼0.012) based on estimates of multiple loci. Because of its highest diversity among the eight nuclear loci and evolving neutrally, one locus (2009) was further used for phylogeographical studies and eight haplotypes resulting from 12 polymorphic sites were obtained from 98 individuals. All the four distinct regions had at least four haplotypes, with the Dalou region (DL) having the highest diversity and the Bamian region (BM) the lowest, paralleling the result of the eight nuclear loci. An AMOVA revealed significant proportion of diversity attributable to differences among regions (13.4%) and among populations within regions (8.9%). F ST analysis also indicated significantly high differentiation among populations ( F ST = 0.22) and between regions ( F ST = 0.12–0.38). Non‐overlapping distribution of mitotypes and high genetic differentiation among the distinct geographical groups suggest the existence of at least four separate glacial refugia. Based on network and mismatch distribution analyses, we do not find evidence of long distance dispersal and population expansion in C . argyrophylla . Ex situ conservation and artificial crossing are recommended for the management of this endangered species.

Genetic Variation in Hippophae rhamnoides ssp. sinensis (Elaeagnaceae) Revealed by RAPD Markers - Kun Sun; Wen Chen; Ruijun Ma; Xuelin Chen; Ang Li; Song Ge (Biochemical Genetics, 2006)

Genetic diversity and evolutionary relationships ofOryza species with the B- and C-genomes as revealed by SSR markers - Ying Bao; Hai Fei Zhou; De Yuan Hong; Song Ge (Journal of Plant Biology, 2006)

A lower specificity PhaC2 synthase from Pseudomonas stutzeri catalyses the production of copolyesters consisting of short-chain-length and medium-chain-length 3-hydroxyalkanoates - Jing-Yu Chen; Ge Song; Guo-Qiang Chen (Antonie van Leeuwenhoek, 2006)

Genetic Diversity in Accessions of Wild Rice Oryza granulata from South and Southeast Asia - Wei Qian; Song Ge; De-yuan Hong (Genetic Resources and Crop Evolution, 2006)

Pilot-Scale Fermentation and Purification of the Recombinant Allophycocyanin Over-Expressed in Escherichia coli - Baosheng Ge; Zhihong Tang; Liping Lin; Yuhong Ren; Yu Yang; Song Qin (Biotechnology Letters, 2005)

Signal role for activation of caspase-3-like protease and burst of superoxide anions during Ce4+-induced apoptosis of cultured Taxus cuspidata cells - Zhi-Qiang Ge; Song Yang; Jing-Sheng Cheng; Ying-Jin Yuan (BioMetals, 2005)

Genetic Diversity and Population Differentiation of Liaoning Weedy Rice Detected by RAPD and SSR Markers - Guo-qin Yu; Ying Bao; Chun-hai Shi; Chang-qin Dong; Song Ge (Biochemical Genetics, 2005)

Identification of genomic constitutions of Oryza species with the B and C genomes by the PCR-RFLP method - Ying Bao; Bao-Rong Lu; Song Ge (Genetic Resources and Crop Evolution, 2005)

Construction and characterization of a bacterial artificial chromosome library of marine macroalgaPorphyra yezoensis (Rhodophyta) - Dai Yong Deng; Ge Zhao; Jin Song Xuan; Ji Liang Yang; Lin De Duan; Man Li Weng; Bin Wang (Plant Molecular Biology Reporter, 2004)

Microsatellite analysis of genetic diversity and population genetic structure of a wild rice (Oryza rufipogon Griff.) in China - Hai-fei Zhou; Zhong-wen Xie; Song Ge (Theoretical and Applied Genetics, 2003)

Allozyme Variation and Population Differentiation of the Aconitum delavayi Complex (Ranunculaceae) in the Hengduan Mountains of China - Fumin Zhang; Hongzhi Kong; Song Ge (Biochemical Genetics, 2003)

Note: A Preliminary Study on Conservation Genetics of an Endangered Orchid (Paphiopedilum micranthum) from Southwestern China - Ang Li; Yi-bo Luo; Song Ge (Biochemical Genetics, 2002)

Allozyme variation and conservation genetics of common wild rice (Oryza rufipogon Griff.) in Yunnan, China - Lizhi Gao; Song Ge; Deyuan Hong; Rushun Lin; Guoda Tao; Zaifu Xu (Euphytica, 2002)

Note: Genetic Structure and Heterozygosity Variation Between Generations of Ophiopogon xylorrhizus (Liliaceae s.l.), an Endemic Species in Yunnan, Southwest China - Tianhua He; Guangyuan Rao; Ruilin You; Song Ge; Daming Zhang (Biochemical Genetics, 2001)

Allozyme Diversity and Population Genetic Structure of Pinus densata Master in Northwestern Yunnan, China - Hong Yu; Song Ge; De-yuan Hong (Biochemical Genetics, 2000)

Comparisons of Genetic Diversity in the Endangered Adenophora lobophylla and Its Widespread Congener, A. potaninii - Song Ge; Ke‐Qing Wang; De‐Yuan Hong; Wen‐Hui Zhang; Yuan‐Gang Zu (Conservation Biology, 1999)
Starch‐gel electrophoresis was used to examine the levels and distribution of genetic diversity in two Adenophora species: the narrow endangered Adenophora lobophylla and its widespread congener, A. potaninii . Based on allozyme variation at 18 putative loci, we measured high levels of genetic variability both in the endangered and the widespread species, with 83.3% of the loci being polymorphic. The mean expected heterozygosity within populations ( H ep ) and within species ( H es ) were 0.234 and 0.244 for A. potaninii and were as high as 0.210 and 0.211 for A. lobophylla . There was higher differentiation among populations in A. potaninii ( F ST = 0.155) than in A. lobophylla ( F ST = 0.071). The high levels of genetic diversity in the present allozyme survey are consistent with the morphological variation observed in these species and may be attributed to high outcrossing rates in the Adenophora species. In addition, A. lobophylla was identified as a distinct species on the basis of Nei’s genetic distances and thus should be given a high priority for protection. It is noteworthy that the endangered A. lobophylla maintains much higher genetic diversity than most endemic or narrowly distributed plant species in spite of its restricted distribution. We hypothesize that A. lobophylla has become endangered for ecological and stochastic reasons, including habitat destruction or environmental changes, mud slides, and human disturbance such as grazing and mowing. Consequently, habitat protection is of particular importance for conserving this endangered species.

Allozyme variation in the diploid (A genome) populations ofScilla scilloides (Hyacinthaceae) - Kaiyu Ding; Song Ge; Zhihui Yu; Deyuan Hong (Plant Systematics and Evolution, 1999)

Allozyme Variation in Ophiopogon xylorrhizus , an Extreme Endemic Species of Yunnan, China - Song Ge; Da‐Ming Zhang; Hai‐Qun Wang; Guang‐Yuan Rao (Conservation Biology, 1997)